Ultra-high molecular weight polyethylene powder and molded article

By adjusting parameters such as intrinsic viscosity, particle size and dissolution time in ultra-high molecular weight polyethylene powder and dissolving it in liquid paraffin, the problems of bubble residues and strain residues in molded bodies are solved, and high-quality molded bodies are achieved and excellent molding processability.

CN119431631APending Publication Date: 2025-02-14ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202410925967.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-07-01
Filing Date
2024-07-11
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

When molding ultra-high molecular weight polyethylene powder, there are problems of bubble residue and strain residue, which leads to deformation of the molded body after cooling. The prior art still has room for improvement in regulating the characteristics of the powder, especially in terms of solubility and molding processability.

Method used

By dissolving the ultra-high molecular weight polyethylene powder in liquid paraffin within a specified time, the intrinsic viscosity, average particle size, dissolution time, communication hole ratio, surface wall thickness and communication hole diameter of the powder are adjusted to optimize its molding processability.

Benefits of technology

The uniform gel is made in a short time and the quality of the molded body is improved, for example, the film thickness unevenness and the puncture strength are reduced, and the high-speed winding of the fiber is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_10
    Figure SMS_10
Patent Text Reader

Abstract

The invention relates to an ultra-high molecular weight polyethylene powder and a molded body. Provided is an ultra-high molecular weight polyethylene powder or the like which is capable of greatly shortening the kneading time, producing a uniform gel in a short time, and producing a gel having a high polymer concentration, and which has excellent moldability. An ultra-high molecular weight polyethylene powder in which the intrinsic viscosity (IV) of the ultra-high molecular weight polyethylene powder is 1.0 dL / g to 38.0 dL / g inclusive, the average particle diameter (D50) is 50 [mu] m to 400 [mu] m inclusive, and the dissolution time of the powder having the particle diameter (D50) is 5 seconds to 80 seconds inclusive.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to ultra-high molecular weight polyethylene powder and a molded body. Background Art

[0002] Polyethylene is used in a variety of applications such as films, sheets, microporous films, fibers, foams, and tubes. The reason for using polyethylene is that it is easy to melt-process, and the resulting molded product has high mechanical strength, excellent chemical resistance, and excellent rigidity. Among them, ultra-high molecular weight polyethylene has a higher mechanical strength due to its large molecular weight, excellent sliding properties and wear resistance, and excellent chemical stability and long-term reliability.

[0003] However, ultra-high molecular weight polyethylene has low fluidity even when melted at a temperature above its melting point. Therefore, it is applied in a compression molding method in which polyethylene powder is compressed and molded under heating and then cut; a molding method in which polyethylene powder is dissolved in a solvent such as liquid paraffin, then stretched and the solvent is removed to form a sheet or filament.

[0004] Ultra-high molecular weight polyethylene is molded in a powder form, but the surface area of ​​the powder is larger than that of the pellets, and the powder has fine pores.

[0005] Regarding the pore state of polyethylene powder, for example, Patent Document 1 discloses a polyethylene powder in which the specific surface area determined by the BET method and the pore volume determined by the mercury intrusion method are adjusted within appropriate ranges so that the powder can be rapidly dissolved in a solvent and a molded body with little undissolved matter can be obtained.

[0006] For example, Patent Document 2 discloses a polyethylene powder in which a molded body with less generation of undissolved matter can be obtained by adjusting the ratio of the median diameter of pores measured by mercury intrusion porosimetry to the modal diameter within an appropriate range.

[0007] In recent years, polyethylene powders have been proposed that are excellent in molding processability and can produce high-quality molded products.

[0008] For example, Patent Document 3 discloses a polyethylene powder having excellent solubility by simultaneously giving the polyethylene powder a predetermined particle size distribution and a predetermined swelling ratio, thereby improving productivity and product quality in processing and molding (particularly wet extrusion molding).

[0009] For example, Patent Document 4 discloses a polyethylene polymer powder in which the intrinsic viscosity IV and the contents of Al, Mg and Si are controlled within specific ranges, thereby improving oxidation resistance and effectively improving film uniformity and smoothness of a thin film.

[0010] In addition, for example, Patent Document 5 discloses an ethylene-based polymer, wherein, by containing a non-magnetic material that meets specific conditions, the ethylene-based polymer has less entanglement during processing and stretching, and when made into high-strength fibers, the low-temperature tensile strength is excellent. Furthermore, when made into a microporous membrane, the membrane shrinkage rate and low-temperature puncture strength are excellent.

[0011] In addition, for example, Patent Document 6 discloses that by adjusting the difference between the swelling start temperature and the dissolution start temperature of the ultra-high molecular weight polyethylene powder and adjusting the impregnation rate of liquid paraffin into the ultra-high molecular weight polyethylene powder, a molded body with excellent processability and dimensional accuracy can be obtained.

[0012] In addition, for example, Patent Document 7 discloses that 10 , D 50 and D 90 The swelling start temperature of the ultra-high molecular weight polyethylene powder is controlled within a specific range, and an ultra-high molecular weight polyethylene powder having excellent molding processability when pre-swelled at a low temperature and a high-quality molded body obtained by molding the ultra-high molecular weight polyethylene powder can be obtained.

[0013] Prior art literature

[0014] Patent Literature

[0015] Patent Document 1: Japanese Patent Application Publication No. 2017-088773

[0016] Patent Document 2: Japanese Patent Application Publication No. 2017-145306

[0017] Patent Document 3: Japanese Patent Application Publication No. 2019-019265

[0018] Patent Document 4: Japanese Patent Application Publication No. 2019-070117

[0019] Patent Document 5: Japanese Patent Application Publication No. 2019-123777

[0020] Patent Document 6: WO2021 / 193544

[0021] Patent Document 7: WO2023-054514 Summary of the invention

[0022] Problems to be solved by the invention

[0023] As described above, the surface area of ​​ultra-high molecular weight polyethylene powder is larger than that of particles, and the powder has fine pores. Therefore, since the shape, surface state, crystal state, pore state, etc. of the powder change during heating, when the ultra-high molecular weight polyethylene powder is molded, it is required to adjust to an appropriate temperature before dissolving, compressing, and other processing. In the case of compression molding of ultra-high molecular weight polyethylene powder, if the preheating temperature before compression is not appropriate, there is a tendency that bubbles remain in the molded body or strain remains in the molded body and deforms after cooling.

[0024] The polyethylene powder described in Patent Document 1 has only its specific surface area and pore volume adjusted as powder properties. However, the properties of the powder vary greatly at the temperature at which the powder is actually dissolved or melted, and there is room for improvement in molding processability.

[0025] Also, the polyethylene powder described in Patent Document 2 only specifies the pore diameter of the powder, and the pore diameter changes significantly during heating. Therefore, there is room for improvement in molding processability, and it is sometimes difficult to obtain a uniform molded body.

[0026] On the other hand, the polyethylene powders described in Patent Documents 3 to 5 have relatively excellent molding processability, but have not been studied to obtain a uniform gel in a short time, and there is room for improvement in molding processability and quality of molded products.

[0027] Furthermore, the polyethylene powders described in Patent Documents 6 and 7 have not been studied for their dissolution time in liquid paraffin (the time from the start of dissolution to the end of dissolution), and thus there is room for improvement in terms of molding processability and the quality of molded products.

[0028] The present invention has been completed in view of the above-mentioned situation, and its purpose is to provide an ultra-high molecular weight polyethylene powder that can significantly shorten the mixing time when using ultra-high molecular weight polyethylene powder for the preparation of a molded body, produce a uniform gel in a short time, and can produce a gel with a high polymer concentration, and has excellent molding processability, as well as a high-quality molded body obtained by molding the ultra-high molecular weight polyethylene powder (for example, a secondary battery separator with uneven film thickness and excellent puncture strength; and a fiber with uneven wire diameter and excellent high-speed winding properties).

[0029] Means used to solve problems

[0030] The present inventors have conducted intensive studies to solve the above problems and have found that the above problems can be solved by using ultra-high molecular weight polyethylene powder that dissolves in liquid paraffin within a predetermined time, thereby completing the present invention.

[0031] That is, the present invention is as follows.

[0032] [1] An ultra-high molecular weight polyethylene powder, wherein:

[0033] The ultra-high molecular weight polyethylene powder has an intrinsic viscosity IV of 1.0 dL / g or more and 38.0 dL / g or less,

[0034] The average particle size D50 of the ultra-high molecular weight polyethylene powder is 50 μm or more and 400 μm or less.

[0035] The dissolution time of the powder having a particle size of D50 is 5 seconds or more and 80 seconds or less.

[0036] [2] The ultra-high molecular weight polyethylene powder according to [1], wherein the intrinsic viscosity IV of the ultra-high molecular weight polyethylene powder is 13.5 dL / g or more and 38.0 dL / g or less.

[0037] [3] The ultra-high molecular weight polyethylene powder according to [1] or [2], wherein the dissolution time of the ultra-high molecular weight polyethylene powder is 5 seconds to 40 seconds.

[0038] [4] The ultrahigh molecular weight polyethylene powder according to any one of [1] to [3], wherein the ratio of interconnected pores in the powder having a particle size of D50 is 3% or more and 70% or less.

[0039] [5] The ultrahigh molecular weight polyethylene powder according to any one of [1] to [4], wherein the surface wall thickness of the powder at a particle size D50 is 3 μm or more and 60 μm or less.

[0040] [6] The ultrahigh molecular weight polyethylene powder according to any one of [1] to [5], wherein the diameter of the continuous pores of the powder with a particle size D50 is 3 μm or more and 30 μm or less.

[0041] [7] The ultra-high molecular weight polyethylene powder according to any one of [1] to [6], wherein the ultra-high molecular weight polyethylene powder has a titanium content of 5 ppm or less.

[0042] [8] The ultra-high molecular weight polyethylene powder according to any one of [1] to [7], wherein the aluminum content of the ultra-high molecular weight polyethylene powder is 5 ppm or less.

[0043] [9] A molded product, wherein the molded product is a molded product of the ultra-high molecular weight polyethylene powder according to any one of [1] to [8].

[0044]

[10] The molded article according to [9], wherein the molded article is a separator for a secondary battery.

[0045]

[11] The molded article according to [9], wherein the molded article is a fiber.

[0046]

[12] A method for producing a high-strength fiber, wherein the method for producing a high-strength fiber comprises the following steps:

[0047] a slurry step, wherein an ultra-high molecular weight polyethylene powder is mixed with a first liquid paraffin, and the mixture is stirred at a temperature below the melting point of the ultra-high molecular weight polyethylene powder to obtain a slurry;

[0048] A gelling step, wherein the slurry is mixed with a second liquid paraffin having a temperature of 150° C. to 300° C., thereby obtaining a raw silk gel having a temperature of 140° C. to 200° C.;

[0049] an extrusion process, wherein the precursor is extruded through the gel to obtain the precursor;

[0050] an extraction step, wherein the first liquid paraffin and the second liquid paraffin are extracted from the raw yarn to obtain the raw yarn for drawing; and

[0051] a raw yarn stretching step, wherein the raw yarn for stretching is heated and stretched,

[0052] The ultra-high molecular weight polyethylene powder has an intrinsic viscosity IV of 13.5 dL / g or more and 38.0 dL / g or less,

[0053] The average particle size D50 of the ultra-high molecular weight polyethylene powder is 50 μm or more and 400 μm or less.

[0054] The dissolution time of the powder having a particle size of D50 of the ultra-high molecular weight polyethylene powder is 5 seconds to 80 seconds.

[0055]

[13] The method for producing a high-strength fiber according to

[12] , wherein a kneading step of kneading the precursor gel is included before the extrusion step.

[0056]

[14] A method for producing a microporous membrane, wherein the method for producing a microporous membrane comprises the following steps:

[0057] a slurry step, wherein an ultra-high molecular weight polyethylene powder is mixed with a first liquid paraffin, and the mixture is stirred at a temperature below the melting point of the ultra-high molecular weight polyethylene powder to obtain a slurry;

[0058] a gelling step, wherein the slurry is mixed with a second liquid paraffin having a temperature of 150° C. to 300° C., thereby obtaining a gel for pressing having a temperature of 140° C. to 200° C.;

[0059] A pressing step, wherein the pressing gel is hot-pressed to obtain a gel sheet;

[0060] a film stretching step, wherein the gel sheet is stretched to obtain a stretched film; and

[0061] an extraction step, wherein the first liquid paraffin and the second liquid paraffin are extracted from the stretched film,

[0062] The ultra-high molecular weight polyethylene powder has an intrinsic viscosity IV of 1.0 dL / g or more and 13.0 dL / g or less,

[0063] The average particle size D50 of the ultra-high molecular weight polyethylene powder is 50 μm or more and 400 μm or less.

[0064] The dissolution time of the powder having a particle size of D50 of the ultra-high molecular weight polyethylene powder is 5 seconds to 80 seconds.

[0065]

[15] The method for producing a microporous membrane according to

[14] , wherein a kneading step of kneading the gel for pressing is included before the pressing step.

[0066]

[16] The method for producing a high-strength fiber according to

[12] or

[13] , wherein in the slurry step, the stirring temperature is 25° C. or higher and 120° C. or lower.

[0067] In the gelling step, the polyethylene concentration of the precursor gel is 3 mass % or more and 20 mass % or less.

[0068]

[17] The method for producing a high-strength fiber as described in

[13] or

[16] , wherein in the kneading step, the temperature is greater than 140°C and less than 200°C, the time is greater than 5 minutes and less than 180 minutes, and the rotation speed is greater than 3 rpm and less than 50 rpm.

[0069]

[18] The method for producing a high-strength fiber as described in any one of

[12] ,

[13] ,

[16] and

[17] , wherein a rapid cooling step is performed after the extrusion step.

[0070] The time from the extrusion step to the rapid cooling step is 0 seconds or more and 10 seconds or less,

[0071] The temperature of the rapid cooling step is 5° C. or higher and 30° C. or lower.

[0072]

[19] The method for producing a high-strength fiber according to any one of

[12] ,

[13] , and

[16] to

[18] , wherein an extrusion preparation step is included before the extrusion step.

[0073] The temperature of the extrusion preparation step is 140° C. or higher and 200° C. or lower.

[0074] The extrusion preparation step takes 5 minutes to 90 minutes.

[0075]

[20] A method for producing high-strength fibers as described in any one of

[12] ,

[13] and

[16] to

[19] , wherein, in the extrusion step, the extrusion speed is greater than 5 mm / min and less than 20 mm / min, the winding speed is greater than 200 mm / min and less than 1600 mm / min, the discharge amount is greater than 0.2 g / min and less than 1.5 g / min, and the spinneret diameter is greater than 0.8 mm and less than 1.5 mm.

[0076]

[21] The method for producing a high-strength fiber according to any one of

[12] ,

[13] , and

[16] to

[20] , wherein in the extraction step, an extraction solvent is used.

[0077] The extraction solvent is hexane or dichloromethane,

[0078] The extraction time is 3 hours or more and 24 hours or less.

[0079]

[22] The method for producing a high-strength fiber according to any one of

[12] ,

[13] , and

[16] to

[21] , wherein multi-stage drawing is performed in the precursor drawing step.

[0080]

[23] The method for producing a high-strength fiber as described in

[22] , wherein the multi-stage stretching is a two-stage stretching.

[0081]

[24] The method for producing a high-strength fiber according to

[23] , wherein the secondary stretching comprises a primary stretching step and a secondary stretching step,

[0082] In the primary stretching step, the feeding speed is 50 mm / min to 200 mm / min, the winding speed is 1000 mm / min to 4000 mm / min, and the temperature is 110° C. to 155° C.,

[0083] In the secondary stretching step, the feeding speed is 50 mm / min to 200 mm / min, the winding speed is 100 mm / min to 500 mm / min, and the temperature is 130° C. to 155° C.

[0084]

[25] The method for producing a microporous membrane according to

[14] or

[15] , wherein in the slurry step, the stirring temperature is 25° C. or higher and 120° C. or lower.

[0085] In the gelling step, the polyethylene concentration of the pressing gel is 20 mass % or more and 55 mass % or less.

[0086]

[26] The method for producing a microporous membrane as described in

[15] or

[25] , wherein in the kneading step, the temperature is 140°C to 250°C, the time is 5 minutes to 60 minutes, and the rotation speed is 30 rpm to 100 rpm.

[0087]

[27] The method for producing a microporous membrane as described in any one of

[14] ,

[15] ,

[25] and

[26] , wherein in the pressing step, a 1.0 mm metal frame is used so that the thickness of the gel sheet is 1.0 mm, and the temperature and pressure are adjusted in multiple stages,

[0088] In the first stage, heating is performed at a temperature of 180°C to 220°C, a pressure of 1 MPa, and a time of 3 minutes.

[0089] In the second stage, heating is performed at a temperature of 180°C to 220°C, a pressure of 10 MPa, and a time of 2 minutes.

[0090] In the third stage, cooling was performed under the conditions of a temperature of 20° C. or higher and 35° C. or lower, a pressure of 10 MPa, and a time of 5 minutes.

[0091]

[28] A method for manufacturing a microporous membrane as described in any one of

[14] ,

[15] and

[25] to

[27] , wherein in the membrane stretching step, the stretching is simultaneous biaxial stretching, and the membrane is stretched to a value of 5 to 20 times in the longitudinal direction and a value of 5 to 20 times in the transverse direction at a temperature of 110°C to 130°C.

[0092]

[29] The method for producing a microporous membrane according to any one of

[14] ,

[15] and

[25] to

[28] , wherein in the extraction step, an extraction solvent is used.

[0093] The extraction solvent is hexane or dichloromethane,

[0094] The extraction time is 3 hours or more and 24 hours or less.

[0095] Effects of the Invention

[0096] According to the present invention, it is possible to provide an ultra-high molecular weight polyethylene powder having excellent molding processability and a high-quality molded product obtained by molding the ultra-high molecular weight polyethylene powder. BRIEF DESCRIPTION OF THE DRAWINGS

[0097] Figure 1An image showing a powder (particle) with a particle size of D50. The area surrounded by the dotted line marked on the outer periphery of the particle is called the "outer diameter of the particle". The diameter of the largest circle (recorded by the dotted line) contained in the communicating hole is called the "communication hole diameter". The diameter of the largest circle (recorded by the dotted line) contained in the resin area is called the "wall thickness".

[0098] Figure 2 A tomographic image showing a powder with a particle size of D50. DETAILED DESCRIPTION

[0099] Hereinafter, a mode for implementing the present invention (hereinafter also referred to as "this embodiment") will be described in detail. It should be noted that the present invention is not limited to this embodiment, and can be implemented with various modifications within the scope of the gist thereof.

[0100] [Ultra-high molecular weight polyethylene powder]

[0101] The ultrahigh molecular weight polyethylene powder (hereinafter also simply referred to as "powder" or "polymer") of the present embodiment has an intrinsic viscosity IV of 1.0 dL / g to 38.0 dL / g, preferably 1.5 dL / g to 33.0 dL / g, and more preferably 2.4 dL / g to 31.0 dL / g.

[0102] The ultrahigh molecular weight polyethylene powder of the present embodiment has a further improved strength when the intrinsic viscosity IV is equal to or greater than the above lower limit, and has a further improved moldability when the intrinsic viscosity IV is equal to or less than the above upper limit.

[0103] In addition, although there is no particular limitation on the ultra-high molecular weight polyethylene powder of the present embodiment, for example, in the case of a molded body for a secondary battery separator, the intrinsic viscosity IV is preferably 1.0 dL / g or more and 13.0 dL / g or less, more preferably 1.5 dL / g or more and 11.5 dL / g or less, and further preferably 2.4 dL / g or more and 9.5 dL / g or less. The secondary battery separator obtained by molding the ultra-high molecular weight polyethylene powder having an intrinsic viscosity IV within the above range tends to have excellent film strength and heat shrinkage.

[0104] In addition, although there are no particular limitations on the ultra-high molecular weight polyethylene powder of the present embodiment, for example, in the case of a molded body for fiber, the intrinsic viscosity IV is preferably 13.5 dL / g or more and 38.0 dL / g or less, more preferably 15.0 dL / g or more and 33.0 dL / g or less, and further preferably 16.5 dL / g or more and 31.0 dL / g or less. Fibers obtained by molding (e.g., molding in the case of kneading in a normal time or a short time) an ultra-high molecular weight polyethylene powder having an intrinsic viscosity IV within the above range tend to have excellent filament strength and the like.

[0105] As a method for controlling the intrinsic viscosity IV within the above range, there is no particular restriction, for example, it can be cited as: changing the polymerization temperature of the reactor when ethylene is homopolymerized or when ethylene is copolymerized with olefins other than ethylene that can copolymerize with ethylene. Regarding the intrinsic viscosity IV, there is a tendency that the higher the polymerization temperature, the lower the intrinsic viscosity IV, and there is a tendency that the lower the polymerization temperature, the higher the intrinsic viscosity IV. In addition, as other methods for adjusting the intrinsic viscosity IV to the above range, there is no particular restriction, for example, it can be cited as: changing the type of organic metal compound used as a cocatalyst when ethylene is homopolymerized or when ethylene is copolymerized with olefins other than ethylene that can copolymerize with ethylene. In addition, as other methods for adjusting the intrinsic viscosity IV to the above range, there is no particular restriction, for example, it can be cited as: adding a chain transfer agent when ethylene is homopolymerized or when ethylene is copolymerized with olefins other than ethylene that can copolymerize with ethylene. By adding a chain transfer agent, there is a tendency that the intrinsic viscosity IV of the generated ultra-high molecular weight polyethylene is reduced even at the same polymerization temperature.

[0106] In addition, in this embodiment, the intrinsic viscosity IV is not particularly limited, and can be obtained by, for example, the method described in the examples described later.

[0107] The ultrahigh molecular weight polyethylene powder of the present embodiment is preferably a powder containing an ethylene homopolymer and / or a copolymer of ethylene and an olefin copolymerizable with ethylene other than ethylene (hereinafter also referred to as a "comonomer") (hereinafter also referred to as an "ethylene-based polymer").

[0108] The comonomer copolymerizable with ethylene is not particularly limited, and specifically, for example, it can be selected from α-olefins having 3 to 15 carbon atoms, cyclic olefins having 3 to 15 carbon atoms, and olefins of the formula CH 2 =CHR 1 (Here, R 1is an aryl group having 6 to 12 carbon atoms) and at least one comonomer selected from the group consisting of a linear, branched or cyclic diene having 3 to 15 carbon atoms. Among them, α-olefins having 3 to 15 carbon atoms are preferred.

[0109] The α-olefin is not particularly limited, and examples thereof include propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, and 1-tetradecene.

[0110] The ultra-high molecular weight polyethylene powder of the present embodiment may be, for example, an ultra-high molecular weight polyethylene powder made from ethylene produced from naphtha derived from biomass or ethanol derived from biomass. For example, the ultra-high molecular weight polyethylene powder derived from biomass may be produced by a method of using naphtha derived from biomass as a raw material and cracking it.

[0111] The average particle size (D50) of the ultra-high molecular weight polyethylene powder of this embodiment is 50 μm or more and 400 μm or less, preferably 70 μm or more and 300 μm or less, more preferably 90 μm or more and 250 μm or less, further preferably 100 μm or more and 200 μm or less, and most preferably 120 μm or more and 180 μm or less.

[0112] By adjusting the average particle size (D50) to 50 μm or more, clogging in the extruder hopper associated with reduced fluidity can be suppressed, thereby improving productivity. In addition, by adjusting the average particle size (D50) to 400 μm or less, a sufficient amount of liquid paraffin can be incorporated into the powder, and a uniform gel with no entanglement can be produced. That is, the inhomogeneity of the gel caused by insufficient incorporation of liquid paraffin can be suppressed.

[0113] There are no particular limitations on the method for controlling the average particle size (D50) within the above range, and one method includes appropriately adjusting the conditions in the polymerization system (polymerization temperature, ethylene pressure, etc.). Specifically, there are methods of increasing the polymerization temperature and / or the polymerization pressure.

[0114] It should be noted that the measurement of the average particle size (D50) of the ultra-high molecular weight polyethylene powder is not particularly limited, and can be carried out, for example, by the method described in the Examples described later.

[0115] [Dissolution time of ultra-high molecular weight polyethylene powder]

[0116] The dissolution time of the ultrahigh molecular weight polyethylene powder of this embodiment is 5 seconds to 80 seconds, preferably 5 seconds to 70 seconds, more preferably 5 seconds to 60 seconds, further preferably 5 seconds to 40 seconds, and most preferably 5 seconds to 35 seconds.

[0117] It should be noted that the dissolution time was calculated according to the following method 1 and method 2.

[0118] [Method 1: Determination method of D50]

[0119] The particle size of the target ultrahigh molecular weight polyethylene powder was measured using a laser particle size distribution analyzer with methanol as a dispersion medium. Based on the measurement, a cumulative particle size distribution from the small particle size side was prepared, and the particle size when the cumulative distribution reached 50% was defined as D50.

[0120] [Method 2: Determination of dissolution time]

[0121] Calculate the dissolution time of the powder with a particle size of D50. First, while confirming the long axis diameter and the short axis diameter (for the plane figure of the particle observed using an optical microscope, the distance between the parallel lines with the shortest interval is the short axis diameter of the particle, and the distance between the parallel lines with the longest interval in the perpendicular direction is the long axis diameter of the particle) in the range of D50±10% by using an optical microscope, arbitrarily select one ultra-high molecular weight polyethylene powder. The selected one ultra-high molecular weight polyethylene powder (hereinafter also recorded as "measurement particle") is set on a slide, 0.05mL of liquid paraffin is dripped onto the measurement particle using a 1mL syringe, and then a cover glass is placed and the measurement particle is clamped. Then, the slide is set on a heating table and heated from room temperature to 150°C under the following heating conditions. The appearance of the measurement particle during heating is photographed every 5 seconds using an optical microscope with a camera. The equivalent circle diameter of the measurement particle is calculated from each observed image obtained, and the time from the state with the largest equivalent circle diameter to the disappearance of the powder is taken as the dissolution time. This operation was repeated 10 times, and the average value of the 8 points after removing the maximum and minimum values ​​was calculated to calculate the final dissolution time.

[0122] (Temperature rising conditions)

[0123] Heating rate from room temperature to 35°C: 5°C / min

[0124] Heating rate within the range of 35℃~80℃: 8℃ / min

[0125] Heating rate within the range of 80℃~150℃: 5℃ / min

[0126] For the ultra-high molecular weight polyethylene powder of this embodiment, by keeping the dissolution time within the above-mentioned range, for example, when it is wet extruded into fibers (e.g., high-strength fibers) or secondary battery separators (e.g., microporous membranes), the energy consumed in the wet extrusion process can be reduced, thereby reducing the environmental load and significantly improving the production efficiency of the molded body.

[0127] Generally, wet extrusion processing refers to mixing the slurry obtained by impregnating liquid paraffin into powder while heating it in an extruder, and processing the gel-like slurry into various molded bodies. Here, the factor affecting the processability of the molded body is the amount of entanglement of the molecular chains in the gel. The amount of entanglement of the molecular chains in the amorphous part of the ultra-high molecular weight polyethylene powder is large, and it is difficult to obtain a uniform gel that has been entangled. That is, even if the wet extrusion processing conditions (temperature, time, screw speed) are adjusted, it is difficult to obtain a uniform gel that has been entangled with the molecular chains, and it is important to reduce the amount of entanglement of the amorphous part of the powder itself.

[0128] Here, the dissolution behavior of polyethylene powder is described. When polyethylene powder is immersed in liquid paraffin, the liquid paraffin enters (dissolves) into the polyethylene powder, and the polyethylene powder swells. Liquid paraffin cannot easily enter the crystal part of the polyethylene powder, so it is believed that the liquid paraffin enters the amorphous part, and it is confirmed that the crystal long period of the polyethylene powder is actually extended with swelling. That is, swelling is considered to be a phenomenon in which the liquid paraffin enters between the lamellae of the polyethylene powder and expands the amorphous part.

[0129] At this time, when the amount of entanglement of the molecular chains in the amorphous part is large, swelling is hindered and the amount of liquid paraffin entering the powder is reduced, thereby the solubility of the powder becomes worse (long dissolution time = more than 80 seconds). Even if kneading is carried out for a long time, a uniform gel with entanglement cannot be obtained.

[0130] On the other hand, when the amount of entanglement of the molecular chains of the amorphous part is small, the amount of liquid paraffin entering the powder also increases, so the solubility of the powder becomes good (short dissolution time = more than 5 seconds and less than 80 seconds), and a uniform gel that has been entangled by short-time mixing can be obtained. As a result, when wet extrusion is performed, a high-quality molded body can be obtained, such as a secondary battery separator with suppressed thickness unevenness and high breaking strength; a fiber that suppresses uneven wire diameter and can be stretched at high speed. However, when the amount of entanglement of the molecular chains of the amorphous part is too small (the dissolution time is too short = less than 5 seconds), it is believed that the thermal shrinkage of the molded body after wet extrusion processing cannot be suppressed, resulting in reduced strength. It is believed that this is because, by leaving moderate entanglement, the straight chain shrinkage can be suppressed, resulting in a relaxation of thermal shrinkage.

[0131] As can be seen from the above, it is not good for the molecular chains in the amorphous part to be too much or too little entangled, and it is important to set it within an appropriate range. To this end, the dissolution time of the powder needs to be controlled to be more than 5 seconds and less than 80 seconds.

[0132] There are no particular restrictions on the method for controlling the dissolution time of the ultra-high molecular weight polyethylene powder within the above range, and examples thereof include: a method in which the powder is immersed in liquid paraffin and vacuum degassed while heating (hereinafter also referred to as control method 1); a method in which a polymer obtained by adding liquid paraffin to a polymerization solvent during prepolymerization and polymerizing the mixture is used as a prepolymerization catalyst and a main polymerization is performed (hereinafter also referred to as control method 2).

[0133] The mechanism by which the dissolution time of the ultra-high molecular weight polyethylene powder can be controlled within the above range by the above method is not clear, but the present inventors speculate as follows, but are not limited thereto.

[0134] Regarding the method of the above-mentioned control method 1, the reason is not clear, but it is not limited to the following reasons. It is important to immerse the powder in liquid paraffin, and while applying a temperature (50°C to 100°C) at which the powder does not melt and the molecular chains can move, place it under vacuum (300Pa to 400Pa) for 1 hour to 6 hours, so that the liquid paraffin fully enters the inside of the powder pores and takes time to untangle the molecular chains little by little. Then, immerse in hexane for 5 hours to 24 hours, extract the liquid paraffin from the powder, and dry it at a temperature of 25°C to 50°C for 24 hours, thereby obtaining a powder with a short dissolution time (5 seconds to 80 seconds).

[0135] Regarding the method of the above-mentioned control method 2, the reason is not yet clear, and is not limited to the following reasons. It can be considered that the polymer obtained by adding 55% to 70% by mass of liquid paraffin to the polymerization solvent during the prepolymerization and polymerizing is used as a prepolymerization catalyst and the main polymerization is carried out, and the liquid paraffin is removed from the powder after the polymerization is completed, thereby obtaining a powder with a short dissolution time (more than 5 seconds and less than 80 seconds). It can be considered that the liquid paraffin added to the polymerization solvent is adjusted to a temperature equal to the polymerization temperature, and during the growth reaction of the molecular chain, the liquid paraffin has the effect of inhibiting the entanglement of the molecular chains.

[0136] [Ratio of interconnected pores in ultra-high molecular weight polyethylene powder]

[0137] The ratio of the connected pores of the ultra-high molecular weight polyethylene powder of the present embodiment is, for example, 3% to 70%, preferably 5% to 70%, more preferably 7% to 70%, further preferably 10% to 50%, and most preferably 15% to 40%.

[0138] By adjusting the ratio of the interconnected pores to 3% or more, the liquid paraffin can be fully incorporated into the powder, and a uniform gel can be produced by kneading in a short time. In addition, by adjusting the ratio of the interconnected pores to 70% or less, the filling rate into the packaging bag can be suppressed from decreasing due to the high porosity structure of the powder, thereby avoiding an increase in production costs.

[0139] It should be noted that the ratio of the communicating holes is calculated according to the method described in the examples described later.

[0140] [Surface thickness of ultra-high molecular weight polyethylene powder]

[0141] The surface wall thickness of the ultrahigh molecular weight polyethylene powder of this embodiment is, for example, 3 μm to 60 μm, preferably 5 μm to 50 μm, more preferably 5 μm to 40 μm, further preferably 5 μm to 35 μm, and most preferably 5 μm to 30 μm.

[0142] By adjusting the surface wall thickness to 3 μm or more, the powders can be prevented from fusing together with the melting of the powder surface, and a uniform gel with no entanglement can be produced. In addition, by adjusting the surface wall thickness to 60 μm or less, liquid paraffin can be introduced into the powder in a short time, and a uniform gel with no entanglement can be produced.

[0143] It should be noted that the surface thickness is calculated according to the method described in the examples described later.

[0144] [Connecting pore diameter of ultra-high molecular weight polyethylene powder]

[0145] The connected pore diameter of the ultrahigh molecular weight polyethylene powder of this embodiment is, for example, 3 μm to 30 μm, preferably 4 μm to 30 μm, more preferably 6 μm to 30 μm, further preferably 8 μm to 30 μm, and most preferably 10 μm to 30 μm.

[0146] By adjusting the diameter of the connecting pores to 30 μm or less, liquid paraffin can be introduced into the powder by capillary action, and a uniform gel with no entanglement can be produced. In addition, by adjusting the diameter of the connecting pores to 3 μm or more, a sufficient amount of liquid paraffin can be introduced into the powder, and a uniform gel with no entanglement can be produced.

[0147] It should be noted that the communicating hole diameter is calculated according to the method described in the examples described later.

[0148] There are no particular restrictions on the method for controlling the ratio of connected pores, surface wall thickness, and connected pore diameter of ultra-high molecular weight polyethylene powder within the above ranges, and examples thereof include: a method in which a polymer obtained by prepolymerization is used as a prepolymerization catalyst and polymerization is carried out under high pressure conditions (hereinafter also referred to as control method 3).

[0149] The mechanism by which the ratio of interconnected pores, surface wall thickness, and interconnected pore diameter of ultrahigh molecular weight polyethylene powder can be controlled within the above ranges by the above method is not clear, but the present inventors speculate as follows, but are not limited thereto.

[0150] Regarding the method of the above-mentioned control method 3, the reason is not clear, but it is not limited to the following reasons. By using a prepolymerization catalyst (low temperature (5°C or more and 20°C or less) for a short time (0.5 hours or more and 2 hours or less), polymerization is carried out under high pressure (0.5MPa or more and 1.0MPa or less), polymerization can be carried out in a state where the initial polymerization activity is high. It is believed that, therefore, a large amount of polymerization heat energy is generated in the polymerization process, and in the process of dissipating this heat energy from the center of the powder to the outside, a connecting hole extending from the center of the powder to the surface is formed, and by further adjusting this heat energy, the diameter of the connecting hole can be controlled.

[0151] [Titanium (Ti) and aluminum (Al) content in ultra-high molecular weight polyethylene powder]

[0152] The content of titanium (Ti) and aluminum (Al) in the ultra-high molecular weight polyethylene powder of the present embodiment is, for example, 5 ppm or less, preferably 4 ppm or less, and more preferably 3 ppm or less. Generally, due to the large amount of metal from the catalyst residue remaining in the ultra-high molecular weight polyethylene powder, the thickness of the molded body tends to be uneven. The ultra-high molecular weight polyethylene powder of the present embodiment has a tendency to have excellent quality by adjusting the content of titanium (Ti) and aluminum (Al) to 5 ppm or less. In addition, when used as a battery, there is a tendency to improve safety.

[0153] It should be noted that the content of titanium (Ti) and aluminum (Al) in the ultra-high molecular weight polyethylene powder can be controlled by the productivity of the ethylene homopolymer or ethylene-based polymer per unit catalyst. The productivity of ethylene homopolymer or ethylene-based polymer can be controlled by the polymerization temperature, polymerization pressure, and slurry concentration of the reactor during manufacturing. That is, in order to improve the productivity of the ethylene homopolymer or ethylene-based polymer used in the present embodiment, there is no particular restriction, for example, can be cited: increase polymerization temperature, increase polymerization pressure, and / or, increase slurry concentration. As other methods, it is also possible to select the type of co-catalyst component when polymerization obtains ethylene homopolymer or ethylene-based polymer, reduce the concentration of co-catalyst component, utilize acid or alkali to clean ethylene homopolymer or ethylene-based polymer to control.

[0154] It should be noted that the measurement of the contents of titanium (Ti) and aluminum (Al) is not particularly limited, and can be carried out, for example, by the method described in the Examples described later.

[0155] [Method for producing ultra-high molecular weight polyethylene powder]

[0156] Hereinafter, the method for producing the ultra-high molecular weight polyethylene powder according to the present embodiment will be described in detail.

[0157] (Catalyst component)

[0158] The catalyst component used for producing the ultra-high molecular weight polyethylene powder according to the present embodiment is not particularly limited, and examples thereof include general Ziegler-Natta catalysts and metallocene catalysts.

[0159] <Ziegler-Natta catalyst>

[0160] As the Ziegler-Natta catalyst, a catalyst for olefin polymerization comprising a solid catalyst component [A] and an organometallic compound component [B] is preferred, wherein the solid catalyst component [A] is produced by reacting an organomagnesium compound (A-1) soluble in an inert hydrocarbon solvent and represented by the following formula 1 with a titanium compound (A-2) represented by the following formula 2.

[0161] (A-1): (M 1 ) α (Mg) β (R 2 ) a (R 3 ) b (Y 1 ) c ……Formula 1

[0162] (In Formula 1, M 1 is a metal atom belonging to the group consisting of Group 12, Group 13 and Group 14 of the periodic table, R2 and R 3 is a hydrocarbon group having 2 or more and 20 or less carbon atoms, Y 1 Alkoxy, silyloxy, allyloxy, amino, amide, -N=CR 4 ,R 5 、-SR 6 (Here, R 4 , R 5 and R 6 represents a hydrocarbon group having 1 to 20 carbon atoms. When c is 2, Y 1 α, β, a, b and c are real numbers satisfying the following relationship: 0≤α, 0<β, 0≤a, 0≤b, 0≤c, 0<a+b, 0≤c / (α+β)≤2, nα+2β=a+b+c (here, n represents M 1 valence.

[0163] (A-2): Ti(OR 7 ) d X 1 (4-d) ……Formula 2

[0164] (In Formula 2, d is a real number greater than or equal to 0 and less than or equal to 4, R 7 is a hydrocarbon group having 1 to 20 carbon atoms, X 1 is a halogen atom.)

[0165] It should be noted that the inert hydrocarbon solvent used in the reaction of (A-1) and (A-2) is not particularly limited, and specific examples thereof include aliphatic hydrocarbons such as pentane, hexane, and heptane; aromatic hydrocarbons such as benzene and toluene; and alicyclic hydrocarbons such as cyclohexane and methylcyclohexane.

[0166] First, (A-1) is described. (A-1) is represented in the form of an organic magnesium complex soluble in an inert hydrocarbon solvent, including all dihydrocarbyl magnesium compounds and complexes of the compound with other metal compounds. The relationship between the symbols α, β, a, b, and c is nα+2β=a+b+c, which represents the valence of the metal atom and the stoichiometry of the substituent.

[0167] In formula 1, as R 2 and R 3 The hydrocarbon group having 2 or more and 20 or less carbon atoms is not particularly limited. Specifically, it can be alkyl, cycloalkyl or aryl, for example, ethyl, propyl, butyl, pentyl, hexyl, octyl, decyl, cyclohexyl, phenyl, etc. Among them, alkyl is preferred. In the case of α>0, the metal atom M 1Metal atoms belonging to the group consisting of Group 12, Group 13 and Group 14 of the periodic table can be used without particular limitation, and examples thereof include zinc, boron, aluminum, etc. Among them, aluminum and zinc are preferred.

[0168] For magnesium relative to metal atoms M 1 The ratio β / α is not particularly limited, but is preferably 0.1 to 30, more preferably 0.5 to 10. In addition, when a predetermined organomagnesium compound having α=0 is used, there is no particular limitation. For example, in R 2 In the case of 1-methylpropyl, etc., it is soluble in an inert hydrocarbon solvent, and such a compound also brings a preferred result to this embodiment. In Formula 1, it is recommended that R 2 , R 3 Satisfies any one of the following three groups: (1), (2), and (3).

[0169] Group (1): R 2 , R 3 At least one of them is a secondary or tertiary alkyl group having 4 or more and 6 or less carbon atoms, preferably R 2 , R 3 All of them are alkyl groups having 4 to 6 carbon atoms, and at least one of them is a secondary alkyl group or a tertiary alkyl group.

[0170] Group (2): R 2 and R 3 are alkyl groups with different carbon number, preferably R 2 is an alkyl group having 2 or 3 carbon atoms, and R 3 It is an alkyl group having 4 or more carbon atoms.

[0171] Group (3): R 2 , R 3 At least one of them is a hydrocarbon group having 6 or more carbon atoms, preferably R 2 , R 3 The total number of carbon atoms contained in the alkyl group is 12 or more.

[0172] These groups are specifically shown below. In group (1), the secondary alkyl group or tertiary alkyl group having 4 to 6 carbon atoms is not particularly limited, and specifically, for example, 1-methylpropyl group, 2-methylpropyl group, 1,1-dimethylethyl group, 2-methylbutyl group, 2-ethylpropyl group, 2,2-dimethylpropyl group, 2-methylpentyl group, 2-ethylbutyl group, 2,2-dimethylbutyl group, 2-methyl-2-ethylpropyl group, etc. Among them, 1-methylpropyl group is particularly preferred.

[0173] In addition, in group (2), the alkyl group having 2 or 3 carbon atoms is not particularly limited, and specific examples thereof include ethyl, 1-methylethyl, and propyl. Among them, ethyl is particularly preferred. In addition, the alkyl group having 4 or more carbon atoms is not particularly limited, and specific examples thereof include butyl, pentyl, hexyl, heptyl, and octyl. Among them, butyl and hexyl are particularly preferred.

[0174] In group (3), the hydrocarbon group having 6 or more carbon atoms is not particularly limited, and specific examples thereof include hexyl, heptyl, octyl, nonyl, decyl, phenyl, and 2-naphthyl. Among the hydrocarbon groups, alkyl groups are preferred, and among the alkyl groups, hexyl and octyl groups are particularly preferred.

[0175] Generally speaking, when the number of carbon atoms contained in the alkyl group increases, it tends to be easily dissolved in an inert hydrocarbon solvent and the viscosity of the solution tends to increase. Therefore, from an operational point of view, it is preferred to use an appropriate long-chain alkyl group. It should be noted that the above-mentioned organomagnesium compound can be used after being diluted with an inert hydrocarbon solvent, and even if a trace amount of Lewis basic compounds such as ether, ester, amine, etc. is contained or remains in the solution, it can be used without any influence.

[0176] Next, for Y 1 In Formula 1, Y 1 Alkoxy, silyloxy, allyloxy, amino, amide, -N=CR 4 ,R 5 、-SR 6 (Here, R 4 , R 5 and R 6 Each independently represents any one of a hydrocarbon group having 2 to 20 carbon atoms) and a β-keto acid residue.

[0177] In formula 1, as R 4 , R 5 and R 6 The hydrocarbon group represented by is preferably an alkyl group or an aryl group having 1 to 12 carbon atoms, and particularly preferably an alkyl group or an aryl group having 3 to 10 carbon atoms. There are no particular restrictions, and examples thereof include methyl, ethyl, propyl, 1-methylethyl, butyl, 1-methylpropyl, 1,1-dimethylethyl, pentyl, hexyl, 2-methylpentyl, 2-ethylbutyl, 2-ethylpentyl, 2-ethylhexyl, 2-ethyl-4-methylpentyl, 2-propylheptyl, 2-ethyl-5-methyloctyl, octyl, nonyl, decyl, phenyl, naphthyl, etc. Among them, butyl, 1-methylpropyl, 2-methylpentyl and 2-ethylhexyl are particularly preferred.

[0178] In addition, in Formula 1, Y 1Preferably, it is an alkoxy group or a siloxy group. As an alkoxy group, there is no particular limitation, and specifically, for example, preferably, a methoxy group, an ethoxy group, a propoxy group, a 1-methylethoxy group, a butoxy group, a 1-methylpropoxy group, a 1,1-dimethylethoxy group, a pentoxy group, a hexoxy group, a 2-methylpentoxy group, a 2-ethylbutoxy group, a 2-ethylpentoxy group, a 2-ethylhexyloxy group, a 2-ethyl-4-methylpentoxy group, a 2-propylheptyloxy group, a 2-ethyl-5-methyloctyloxy group, an octyloxy group, a phenoxy group, a naphthoxy group. Among them, butoxy group, a 1-methylpropoxy group, a 2-methylpentyloxy group, and a 2-ethylhexyloxy group are more preferred. As a siloxy group, there is no particular limitation, and specifically, for example, preferably, a hydrogen dimethyl siloxy group, an ethyl hydrogen methyl siloxy group, a diethyl hydrogen siloxy group, a trimethyl siloxy group, an ethyl dimethyl siloxy group, a diethyl methyl siloxy group, a triethyl siloxy group, etc. Among them, more preferred are hydrogendimethylsiloxy, ethylhydrogenmethylsiloxy, diethylhydrogensiloxy, and trimethylsiloxy.

[0179] In this embodiment, there is no particular limitation on the method for synthesizing (A-1). For example, the synthesis method can be performed by making a compound having the formula R 2 MgX 1 Japanese R 2 Mg(R 2 For the above meaning, X 1 The organic magnesium compound of the group consisting of halogen) and the organic magnesium compound of the formula M 1 R 3 n and M 1 R 3 (n-1) H(M 1 and R 3 For the above meaning, n represents M 1 The organic metal compound of the group consisting of (a) is reacted in an inert hydrocarbon solvent at a temperature of 25° C. to 150° C., and then, if necessary, the organic metal compound of the formula Y is reacted in an inert hydrocarbon solvent at a temperature of 25° C. to 150° C. 1 -H(Y 1 The compound represented by Y 1 The organic magnesium compound and / or organic aluminum compound having a functional group represented by the formula Y are reacted to synthesize the organic magnesium compound and / or organic aluminum compound having a functional group represented by the formula Y. 1 In the case of reacting a compound represented by -H, there is no particular limitation on the order of the reaction. For example, the organic magnesium compound can be added with a compound represented by formula Y 1 -H represented by the method of the compound represented by formula Y 1 Any method of adding an organomagnesium compound to a compound represented by -H or a method of adding both of them simultaneously.

[0180] In this embodiment, Y in (A-1) 1 The molar composition ratio c / (α+β) relative to all metal atoms is 0≤c / (α+β)≤2, preferably 0≤c / (α+β)<1. 1 When the molar composition ratio relative to all metal atoms is 2 or less, the reactivity between (A-1) and (A-2) tends to increase.

[0181] Next, (A-2) is described. (A-2) is a titanium compound represented by Formula 2.

[0182] (A-2): Ti(OR 7 ) d X 1 (4-d) ……Formula 2

[0183] (In Formula 2, d is a real number greater than or equal to 0 and less than or equal to 4, R 7 is a hydrocarbon group having 1 to 20 carbon atoms, X 1 is a halogen atom.)

[0184] In the above formula 2, d is preferably 0 or more and 1 or less, and more preferably 0. In formula 2, as R 7 The hydrocarbon group represented by is not particularly limited, and specifically, for example, aliphatic hydrocarbon groups such as methyl, ethyl, propyl, butyl, pentyl, hexyl, 2-ethylhexyl, heptyl, octyl, decyl, and allyl; alicyclic hydrocarbon groups such as cyclohexyl, 2-methylcyclohexyl, and cyclopentyl; and aromatic hydrocarbon groups such as phenyl and naphthyl. Among them, aliphatic hydrocarbon groups are preferred. 1 The halogen represented by may be, for example, chlorine, bromine, and iodine. Among them, chlorine is preferred. In the present embodiment, (A-2) is particularly preferably titanium tetrachloride. In the present embodiment, two or more compounds selected from the above substances may be mixed and used.

[0185] Next, the reaction of (A-1) and (A-2) is described. The reaction is preferably carried out in an inert hydrocarbon solvent, and more preferably in an aliphatic hydrocarbon solvent such as hexane or heptane. There is no particular restriction on the molar ratio of (A-1) to (A-2) in the reaction, and the molar ratio (Ti / Mg) of the Ti atoms contained in (A-2) relative to the Mg atoms contained in (A-1) is preferably 0.1 or more and 10 or less, and more preferably 0.3 or more and 3 or less. There is no particular restriction on the reaction temperature, and it is preferably carried out in the range of -80°C or more and 150°C or less, and more preferably in the range of -40°C or more and 100°C or less. There is no particular restriction on the order of addition of (A-1) and (A-2), and it can be any method of adding (A-2) after (A-1), adding (A-1) after (A-2), and adding (A-1) and (A-2) simultaneously, and the method of adding (A-1) and (A-2) simultaneously is preferred. In the present embodiment, the solid catalyst component [A] obtained by the above reaction is used in the form of a slurry solution using an inert hydrocarbon solvent.

[0186] As another example of the Ziegler-Natta catalyst component used in the present embodiment, the following olefin polymerization catalyst is preferred, which comprises a solid catalyst component [C] and an organic metal compound component [B], wherein the solid catalyst component [C] is produced by supporting an organic magnesium compound (C-4) represented by Formula 5 and a titanium compound (C-5) represented by Formula 6, which are soluble in an inert hydrocarbon solvent, on a carrier (C-3) prepared by reacting an organic magnesium compound (C-1) represented by Formula 3 and a chlorinating agent (C-2) represented by Formula 4.

[0187] (C-1): (M 2 ) γ (Mg) δ (R 8 ) e (R 9 ) f (OR 10 ) g ……Formula 3

[0188] (In Formula 3, M 2 is a metal atom belonging to the group consisting of Group 12, Group 13 and Group 14 of the periodic table, R 8 , R 9 and R 10 Each is a hydrocarbon group having 1 to 20 carbon atoms, and γ, δ, e, f, and g are real numbers satisfying the following relationship: 0≤γ, 0<δ, 0≤e, 0≤f, 0≤g, 0<e+f, 0≤g / (γ+δ)≤2, kγ+2δ=e+f+g (here, k represents M 2valence.

[0189] (C-2): H h SiCl i R 11 (4-(h+i)) ……Formula 4

[0190] (In Formula 4, R 11 is a hydrocarbon group having 1 or more and 12 or less carbon atoms, and h and i are real numbers satisfying the following relationship: 0<h, 0<i, 0<h+i≤4)

[0191] (C-4): (M 1 ) α (Mg) β (R 2 ) a (R 3 ) b Y 1 c ……Formula 5

[0192] (In Formula 5, M 1 is a metal atom belonging to the group consisting of Group 12, Group 13 and Group 14 of the periodic table, R 2 and R 3 is a hydrocarbon group having 2 or more and 20 or less carbon atoms, Y 1 Alkoxy, silyloxy, allyloxy, amino, amide, -N=CR 4 ,R 5 、-SR 6 (Here, R 4 , R 5 and R 6 represents a hydrocarbon group having 1 to 20 carbon atoms. When c is 2, Y 1 α, β, a, b and c are real numbers satisfying the following relationship: 0≤α, 0<β, 0≤a, 0≤b, 0≤c, 0<a+b, 0≤c / (α+β)≤2, nα+2β=a+b+c (here, n represents M 1 valence.

[0193] (C-5): Ti(OR 7 ) d X 1 (4-d) ……Formula 6

[0194] (In Formula 6, d is a real number greater than or equal to 0 and less than or equal to 4, R 7 is a hydrocarbon group having 1 to 20 carbon atoms, X 1 is a halogen atom.)

[0195] First, (C-1) is described. (C-1) is represented in the form of an organic magnesium complex soluble in an inert hydrocarbon solvent, but includes all dihydrocarbyl magnesium compounds and complexes of the compound with other metal compounds. The relationship between the symbols γ, δ, e, f and g in formula 3, kγ+2δ=e+f+g, represents the valence of the metal atom and the stoichiometry of the substituent.

[0196] In the above formula 3, R 8 or R 9 The hydrocarbon group represented by is not particularly limited, and specifically, each is an alkyl group, a cycloalkyl group or an aryl group, and examples thereof include methyl, ethyl, propyl, butyl, pentyl, hexyl, octyl, decyl, cyclohexyl, and phenyl. Among them, R is preferably 8 and R 9 Each is an alkyl group. In the case of α>0, the metal atom M 2 Metal atoms belonging to the group consisting of Group 12, Group 13 and Group 14 of the periodic table can be used without particular limitation, and examples thereof include zinc, boron, aluminum, etc. Among them, aluminum and zinc are particularly preferred.

[0197] For magnesium relative to metal atoms M 2 The ratio δ / γ is not particularly limited, but is preferably 0.1 to 30, and more preferably 0.5 to 10. In addition, when a predetermined organomagnesium compound having γ=0 is used, for example, in R 8 In the case of 1-methylpropyl, etc., it is soluble in an inert hydrocarbon solvent, and such a compound also brings a preferred result to this embodiment. In Formula 3, it is recommended that R 8 , R 9 Satisfies any one of the following three groups: (1), (2), and (3).

[0198] Group (1): R 8 , R 9 At least one of them is a secondary or tertiary alkyl group having 4 to 6 carbon atoms, preferably R 8 , R 9 All of them are alkyl groups having 4 to 6 carbon atoms, and at least one of them is a secondary alkyl group or a tertiary alkyl group.

[0199] Group (2): R 8 and R 9 are alkyl groups with different carbon number, preferably R 8 is an alkyl group having 2 or 3 carbon atoms, and R 9 It is an alkyl group having 4 or more carbon atoms.

[0200] Group (3): R 8 , R 9At least one of them is a hydrocarbon group having 6 or more carbon atoms, preferably R 8 , R 9 The total number of carbon atoms contained in the alkyl group is 12 or more.

[0201] These groups are specifically shown below. In group (1), as the secondary alkyl group or tertiary alkyl group having 4 to 6 carbon atoms, specifically, for example, 1-methylpropyl, 2-methylpropyl, 1,1-dimethylethyl, 2-methylbutyl, 2-ethylpropyl, 2,2-dimethylpropyl, 2-methylpentyl, 2-ethylbutyl, 2,2-dimethylbutyl, 2-methyl-2-ethylpropyl, etc. can be used. Among them, 1-methylpropyl is particularly preferred.

[0202] In addition, in group (2), the alkyl group having 2 or 3 carbon atoms is not particularly limited, and examples thereof include ethyl, 1-methylethyl, propyl, etc. Among them, ethyl is particularly preferred. In addition, the alkyl group having 4 or more carbon atoms is not particularly limited, and specific examples thereof include butyl, pentyl, hexyl, heptyl, octyl, etc. Among them, butyl and hexyl are particularly preferred.

[0203] In group (3), the hydrocarbon group having 6 or more carbon atoms is not particularly limited, and specific examples thereof include hexyl, heptyl, octyl, nonyl, decyl, phenyl, and 2-naphthyl. Among the hydrocarbon groups, alkyl groups are preferred, and among the alkyl groups, hexyl and octyl groups are particularly preferred.

[0204] Generally speaking, when the number of carbon atoms contained in the alkyl group increases, it tends to be easily dissolved in an inert hydrocarbon solvent and has a tendency to increase the viscosity of the solution. Therefore, from an operational point of view, it is preferred to use an appropriate long-chain alkyl group. It should be noted that the above-mentioned organomagnesium compound is used in the form of an inert hydrocarbon solution, and even if a trace amount of Lewis basic compounds such as ether, ester, amine, etc. is contained or remains in the solution, it can be used without any influence.

[0205] Next, the alkoxy group (OR 10 ) is explained. 10 The hydrocarbon group represented by is preferably an alkyl group or aryl group having 1 to 12 carbon atoms, and particularly preferably an alkyl group or aryl group having 3 to 10 carbon atoms. 10 , there are no particular restrictions, and specifically, for example, methyl, ethyl, propyl, 1-methylethyl, butyl, 1-methylpropyl, 1,1-dimethylethyl, pentyl, hexyl, 2-methylpentyl, 2-ethylbutyl, 2-ethylpentyl, 2-ethylhexyl, 2-ethyl-4-methylpentyl, 2-propylheptyl, 2-ethyl-5-methyloctyl, octyl, nonyl, decyl, phenyl, naphthyl, etc. Among them, butyl, 1-methylpropyl, 2-methylpentyl and 2-ethylhexyl are particularly preferred.

[0206] In this embodiment, there is no particular limitation on the synthesis method of (C-1), but it is preferred to use a compound represented by the formula R 8 MgX 1 Japanese R 8 Mg(R 8 For the above meaning, X 1 The organic magnesium compound of the group consisting of halogen atoms and the organic magnesium compound of the formula M 2 R 9 k Japanese M 2 R 9 (k-1) H(M 2 , R 9 and k are the above-mentioned meanings) in an inert hydrocarbon solvent at a temperature of 25° C. to 150° C., and then, if necessary, with a 9 (R 9 The above meaning) represents a hydrocarbon alcohol or a hydrocarbon alcohol soluble in an inert hydrocarbon solvent having a 9 A method for reacting a hydrocarbon group with an alkoxymagnesium compound and / or an alkoxyaluminum compound.

[0207] When the organomagnesium compound soluble in an inert hydrocarbon solvent is reacted with an alcohol, the order of the reaction is not particularly limited, and any of a method of adding alcohol to the organomagnesium compound, a method of adding the organomagnesium compound to the alcohol, or a method of adding both simultaneously can be used. In the present embodiment, the reaction ratio of the organomagnesium compound soluble in an inert hydrocarbon solvent and the alcohol is not particularly limited, and as a result of the reaction, the molar composition ratio of the alkoxy group in the obtained organomagnesium compound containing an alkoxy group to all metal atoms g / (γ+δ) is 0≤g / (γ+δ)≤2, preferably 0≤g / (γ+δ)<1.

[0208] Next, (C-2) is described. (C-2) is a silicon chloride compound represented by Formula 4 having at least one Si—H bond.

[0209] (C-2): H h SiCl i R 11 (4-(h+i)) ……Formula 4

[0210] (In Formula 4, R 11 is a hydrocarbon group having 1 or more and 12 or less carbon atoms, and h and i are real numbers satisfying the following relationship: 0<h, 0<i, 0<h+i≤4)

[0211] In formula 4, R 11The hydrocarbon group represented by is not particularly limited, and specifically, it is an aliphatic hydrocarbon group, an alicyclic hydrocarbon group, or an aromatic hydrocarbon group, for example, methyl, ethyl, propyl, 1-methylethyl, butyl, pentyl, hexyl, octyl, decyl, cyclohexyl, phenyl, etc. Among them, an alkyl group having 1 to 10 carbon atoms is preferred, and an alkyl group having 1 to 3 carbon atoms, such as methyl, ethyl, propyl, 1-methylethyl, is more preferred. In addition, h and i are numbers that satisfy the relationship of h+i≤4 and are greater than 0, and i is preferably 2 to 3.

[0212] There are no particular limitations on these compounds, but specific examples thereof include: HSiCl 3 , HSiCl 2 CH 3 , HSiCl 2 C 2 H 5 , HSiCl 2 (C 3 H 7 )、HSiCl 2 (2-C 3 H 7 )、HSiCl 2 (C 4 H 9 )、HSiCl 2 (C 6 H 5 )、HSiCl 2 (4-Cl-C 6 H 4 )、HSiCl 2 (CH=CH 2 )、HSiCl 2 (CH 2 C 6 H 5 )、HSiCl 2 (1-C 10 H 7 )、HSiCl 2 (CH 2 CH=CH 2 ), H 2 SiCl(CH 3 ), H 2 SiCl(C 2 H 5 )、HSiCl(CH 3 ) 2 、HSiCl(C 2 H 5 ) 2 、HSiCl(CH 3 )(2-C 3 H7 )、HSiCl(CH 3 )(C 6 H 5 )、HSiCl(C 6 H 5 ) 2 etc. A silicon chloride compound containing these compounds or a mixture of two or more selected from these compounds can be used. Among them, HSiCl is preferred 3 , HSiCl 2 CH 3 、HSiCl(CH 3 ) 2 , HSiCl 2 (C 3 H 7 ), more preferably HSiCl 3 , HSiCl 2 CH 3 .

[0213] Next, the reaction of (C-1) and (C-2) is described. During the reaction, it is preferred to pre-dilute (C-2) using an inert hydrocarbon solvent, chlorinated hydrocarbons such as 1,2-dichloroethane, o-dichlorobenzene, and dichloromethane; an ether medium such as ether and tetrahydrofuran; or a mixed medium thereof. Among them, inert hydrocarbon solvents are more preferred from the perspective of catalyst performance. There is no particular restriction on the reaction ratio of (C-1) to (C-2), and the silicon atoms contained in (C-2) are preferably 0.01 moles or more and 100 moles or less, and more preferably 0.1 moles or more and 10 moles or less, relative to 1 mole of magnesium atoms contained in (C-1).

[0214] There is no particular limitation on the reaction method of (C-1) and (C-2). Any of the following methods can be used: a method in which (C-1) and (C-2) are simultaneously introduced into a reactor and reacted simultaneously; a method in which (C-2) is introduced into the reactor beforehand; or a method in which (C-1) is introduced into the reactor beforehand. Among them, a method in which (C-2) is introduced into the reactor beforehand and (C-1) is introduced into the reactor is preferred. The carrier (C-3) obtained by the above reaction is preferably separated by filtration or decantation and then fully washed with an inert hydrocarbon solvent to remove unreacted substances or by-products.

[0215] There is no particular limitation on the reaction temperature of (C-1) and (C-2), but it is preferably 25°C to 150°C, more preferably 30°C to 120°C, and even more preferably 40°C to 100°C. In a method in which (C-1) and (C-2) are simultaneously introduced into a reactor and added while reacting, it is preferred to adjust the temperature of the reactor to a prescribed temperature in advance, and adjust the temperature in the reactor to a prescribed temperature while adding them simultaneously, thereby adjusting the reaction temperature to a prescribed temperature. In a method in which (C-2) is introduced into the reactor in advance and then (C-1) is introduced into the reactor, it is preferred to adjust the temperature of the reactor into which (C-2) has been introduced to a prescribed temperature, and adjust the temperature in the reactor to a prescribed temperature while (C-1) is introduced into the reactor, thereby adjusting the reaction temperature to a prescribed temperature. In the method of introducing (C-2) into the reactor after (C-1) is previously charged into the reactor, it is preferred to adjust the temperature of the reactor into which (C-1) has been charged to a predetermined temperature, and to adjust the temperature inside the reactor to a predetermined temperature simultaneously with the introduction of (C-2) into the reactor, thereby adjusting the reaction temperature to a predetermined temperature.

[0216] Next, the organomagnesium compound (C-4) is described. As (C-4), the compound represented by the above formula 5 is preferred.

[0217] (C-4): (M 1 ) α (Mg) β (R 2 ) a (R 3 ) b Y 1 c ……Formula 5

[0218] (In Formula 5, M 1 is a metal atom belonging to the group consisting of Group 12, Group 13 and Group 14 of the periodic table, R 2 and R 3 is a hydrocarbon group having 2 or more and 20 or less carbon atoms, Y 1 Alkoxy, silyloxy, allyloxy, amino, amide, -N=CR 4 ,R 5 、-SR 6 (Here, R 4 , R 5 and R 6 represents a hydrocarbon group having 1 to 20 carbon atoms. When c is 2, Y 1α, β, a, b and c are real numbers satisfying the following relationship: 0≤α, 0<β, 0≤a, 0≤b, 0<a+b, 0≤c / (α+β)≤2, nα+2β=a+b+c (here, n represents M 1 valence.

[0219] The amount of (C-4) used is preferably 0.1 to 10, more preferably 0.5 to 5, in terms of the molar ratio of the magnesium atoms contained in (C-4) to the titanium atoms contained in (C-5).

[0220] The reaction temperature of (C-4) and (C-5) is not particularly limited, but is preferably -80°C to 150°C, more preferably -40°C to 100°C.

[0221] The concentration of (C-4) when used is not particularly limited, but is preferably 0.1 mol / L or more and 2 mol / L or less, and more preferably 0.5 mol / L or more and 1.5 mol / L or less, based on the titanium atom contained in (C-4). It should be noted that an inert hydrocarbon solvent is preferably used in the dilution of (C-4).

[0222] There is no particular restriction on the order of adding (C-4) and (C-5) to (C-3), and any of the methods of adding (C-5) after (C-4), adding (C-4) after (C-5), and adding (C-4) and (C-5) simultaneously may be used. Among them, the method of adding (C-4) and (C-5) simultaneously is preferred. The reaction of (C-4) and (C-5) is carried out in an inert hydrocarbon solvent, preferably an aliphatic hydrocarbon solvent such as hexane or heptane. The catalyst thus obtained is used in the form of a slurry solution using an inert hydrocarbon solvent.

[0223] Next, (C-5) is described. In the present embodiment, (C-5) is a titanium compound represented by the above formula 6.

[0224] (C-5): Ti(OR 7 ) d X 1 (4-d) ……Formula 6

[0225] (In Formula 6, d is a real number greater than or equal to 0 and less than or equal to 4, R 7 is a hydrocarbon group having 1 to 20 carbon atoms, X 1 is a halogen atom.)

[0226] In Formula 6, as R 7The hydrocarbon group represented by is not particularly limited, and specifically, for example, aliphatic hydrocarbon groups such as methyl, ethyl, propyl, butyl, pentyl, hexyl, 2-ethylhexyl, heptyl, octyl, decyl, and allyl; alicyclic hydrocarbon groups such as cyclohexyl, 2-methylcyclohexyl, and cyclopentyl; and aromatic hydrocarbon groups such as phenyl and naphthyl. Among them, aliphatic hydrocarbon groups are preferred. 1 The halogen represented by is not particularly limited, and specific examples thereof include chlorine, bromine, and iodine. Among them, chlorine is preferred. The (C-5) selected from the above may be used alone or in combination of two or more.

[0227] The amount of (C-5) used is not particularly limited, but is preferably 0.01 to 20, particularly preferably 0.05 to 10, in terms of the molar ratio of the titanium atoms contained in the titanium compound (C-5) to the magnesium atoms contained in the carrier (C-3).

[0228] The reaction temperature of (C-5) is not particularly limited, but is preferably in the range of -80°C to 150°C, and more preferably in the range of -40°C to 100°C.

[0229] In this embodiment, there is no particular limitation on the method for supporting (C-5) on (C-3). A method of reacting an excess amount of (C-5) relative to (C-3), a method of efficiently supporting (C-5) by using a third component, and a method of supporting (C-5) by reacting (C-5) with an organomagnesium compound (C-4) are preferred.

[0230] Next, the organometallic compound component [B] used in the present embodiment is described. The solid catalyst component used in the present embodiment becomes a highly active polymerization catalyst by combining with the organometallic compound component [B]. The organometallic compound component [B] is sometimes also referred to as a "co-catalyst". As the organometallic compound component [B], a compound containing a metal belonging to the group consisting of Group 1, Group 2, Group 12 and Group 13 of the periodic table is preferred, and an organoaluminum compound and / or an organomagnesium compound are particularly preferred.

[0231] As the organic aluminum compound, it is preferred to use a compound represented by the following Formula 7 alone or in combination.

[0232] AHr 12 j Z 1 (3-j) ……Formula 7

[0233] (In Formula 7, R 12 is a hydrocarbon group having 1 to 20 carbon atoms, Z 1is a group belonging to the group consisting of hydrogen, halogen, alkoxy, allyloxy, and siloxy, and j is a number of 2 to 3.)

[0234] In the above formula 7, R 12 The hydrocarbon group having 1 or more and 20 or less carbon atoms represented by is not particularly limited, and specifically includes aliphatic hydrocarbon groups, aromatic hydrocarbon groups, and alicyclic hydrocarbon groups, for example, preferably trialkylaluminum such as trimethylaluminum, triethylaluminum, tripropylaluminum, tributylaluminum, tri(2-methylpropyl)aluminum (or triisobutylaluminum), tripentylaluminum, tri(3-methylbutyl)aluminum, trihexylaluminum, trioctylaluminum, and tridecylaluminum; aluminum halide compounds such as diethylaluminum chloride, ethylaluminum dichloride, bis(2-methylpropyl)aluminum chloride, ethylaluminum sesquichloride, and diethylaluminum bromide; alkoxyaluminum compounds such as ethoxydiethylaluminum and butoxydi(2-methylpropyl)aluminum; siloxyaluminum compounds such as dimethylhydrogensilyloxydimethylaluminum, ethylmethylhydrogensilyloxydiethylaluminum, and ethyldimethylsilyloxydiethylaluminum; and mixtures thereof. Among them, trialkylaluminum compounds are particularly preferred.

[0235] As the organic magnesium compound, an organic magnesium compound represented by the above-mentioned Formula 3 and soluble in an inert hydrocarbon solvent is preferred.

[0236] (M 2 ) γ (Mg) δ (R 8 ) e (R 9 ) f (OR 10 ) g ……Formula 3

[0237] (In Formula 3, M 2 is a metal atom belonging to the group consisting of Group 12, Group 13 and Group 14 of the periodic table, R 8 , R 9 and R 10 Each is a hydrocarbon group having 1 to 20 carbon atoms, and γ, δ, e, f, and g are real numbers satisfying the following relationship: 0≤γ, 0<δ, 0≤e, 0≤f, 0≤g, 0<e+f, 0≤g / (γ+δ)≤2, kγ+2δ=e+f+g (here, k represents M 2 valence.

[0238] The organomagnesium compound is represented as an organomagnesium complex soluble in an inert hydrocarbon solvent, but includes all dihydrocarbyl magnesium compounds and complexes of the compound with other metal compounds. 2 , R 8 , R 9 , OR10 As already described, since the solubility of the organomagnesium compound in the inert hydrocarbon solvent is preferably high, it is preferred that δ / γ is in the range of 0.5 or more and 10 or less. In addition, it is further preferred that M 2 Aluminum compounds.

[0239] The combination ratio of the solid catalyst component and the organometallic compound component [B] is not particularly limited, but the organometallic compound component [B] is preferably 1 mmol or more and 3000 mmol or less per 1 g of the solid catalyst component.

[0240] <Metallocene Catalyst>

[0241] As an example of using a metallocene catalyst, a general transition metal compound can be used. There is no particular limitation on the method for producing a metallocene catalyst, and for example, the method described in Japanese Patent No. 4868853 can be cited. Such a metallocene catalyst is composed of two catalyst components: (a) a transition metal compound having a cyclic η-bonding anionic ligand and (b) an activator that can react with the transition metal compound to form a complex that exhibits catalyst activity.

[0242] The transition metal compound having a cyclic η-bonding anionic ligand used in the present embodiment can be represented by the following formula 8, for example.

[0243] L 1 j W k M 3 X 2 p X 3 q ……Formula 8

[0244] In formula 8, L 1 Each independently represents an n-bonded cyclic anionic ligand selected from the group consisting of a cyclopentadienyl group, an indenyl group, a tetrahydroindenyl group, a fluorenyl group, a tetrahydrofluorenyl group and an octahydrofluorenyl group, and the ligand has 1 to 8 substituents depending on the situation, and the substituents are each independently a substituent having 20 or less non-hydrogen atoms selected from the group consisting of a hydrocarbon group having 1 to 20 carbon atoms, a halogen atom, a halogenated hydrocarbon group having 1 to 12 carbon atoms, an aminohydrocarbon group having 1 to 12 carbon atoms, a hydrocarbonoxy group having 1 to 12 carbon atoms, a dihydrocarbonamino group having 1 to 12 carbon atoms, a hydrocarbon phosphino group having 1 to 12 carbon atoms, a silyl group, an aminosilyl group, a hydrocarbonoxysilyl group having 1 to 12 carbon atoms and a halogenated silyl group.

[0245] In formula 8, M 3represents a transition metal selected from the group of transition metals belonging to Group 4 of the Periodic Table of Elements having a formal oxidation number of +2, +3 or +4, and having at least one ligand L 1 Conducted 5 Bonded transition metals.

[0246] In Formula 8, W represents a carbon atom having 50 or less non-hydrogen atoms and having the same 1 and M 3 Each of them is bonded with a monovalent valence, thereby bonding with L 1 and M 3 Together, they form a divalent substituent of a metal ring compound, X 2 Each independently represents a monovalent anionic σ-bonding type ligand selected from M 3 Divalently bonded divalent anionic σ-bonded ligands and L 1 and M 3 Anionic sigma-bonded ligands having 60 or less non-hydrogen atoms in the group consisting of divalent anionic sigma-bonded ligands each bonded with a univalent valence.

[0247] In formula 8, X 2 Each independently represents a neutral Lewis base coordination compound having 40 or less non-hydrogen atoms, X 3 Represents a neutral Lewis base coordination compound.

[0248] j is 1 or 2, wherein when j is 2, the two ligands L 1 The divalent groups are mutually bonded via a divalent group having 20 or less non-hydrogen atoms, wherein the divalent group is a group selected from the group consisting of a hydrocarbon diyl group having 1 to 20 carbon atoms, a halogenated hydrocarbon diyl group having 1 to 12 carbon atoms, an alkyleneoxy group having 1 to 12 carbon atoms, an alkyleneamino group having 1 to 12 carbon atoms, a silanediyl group, a halogenated silanediyl group, and a silyleneamino group.

[0249] k is 0 or 1, p is 0, 1 or 2, where 2 is a monovalent anionic σ-bonded ligand or 1 and M 3 In the case of a divalent anionic σ-bonded ligand, p is a ratio of M 3 The oxidation number of the form is an integer less than 1 or more, and in X 2 For only with M 3 In the case of a divalent anionic σ-bonded ligand, p is a ratio of M 3 The oxidation number of is an integer greater than (j+1), and q is 0, 1 or 2.

[0250] As the ligand X in the compound of the above formula 8 2Examples include halogen ions, hydrocarbon groups having 1 to 60 carbon atoms, hydrocarbonoxy groups having 1 to 60 carbon atoms, hydrocarbonamino groups having 1 to 60 carbon atoms, hydrocarbonphosphino groups having 1 to 60 carbon atoms, hydrocarbonthio groups having 1 to 60 carbon atoms, silyl groups, and composite groups thereof.

[0251] As the neutral Lewis base coordination compound X in the compound of the above formula 8 3 Examples of the group include phosphines, ethers, amines, olefins having 2 to 40 carbon atoms, dienes having 3 to 40 carbon atoms, and divalent groups derived from these compounds.

[0252] In this embodiment, as the transition metal compound having a cyclic η-bonding anionic ligand, a transition metal compound represented by the above formula 8 (wherein j is 1) is preferred. As a preferred example of the compound represented by the above formula 8 (wherein j is 1), a compound represented by the following formula 9 can be cited.

[0253] ……Formula 9

[0254] In formula 9, M 4 represents a transition metal selected from the group consisting of titanium, zirconium, nickel and hafnium and having a formal oxidation number of +2, +3 or +4, R 13 Each independently represents a substituent having 20 or less non-hydrogen atoms selected from the group consisting of a hydrogen atom, a hydrocarbon group having 1 to 8 carbon atoms, a silyl group, a germyl group, a cyano group, a halogen atom, and a composite group thereof, wherein when the substituent R 13 When it is a hydrocarbon group having 1 to 8 carbon atoms, a silyl group or a germyl group, two adjacent substituents R 13 bonded to each other to form a divalent group, thereby being able to bond to the two adjacent substituents R 13 The bonds between the two carbon atoms of the cyclopentadienyl ring to which each is bonded together form a ring.

[0255] In formula 9, X 4 Each independently represents a substituent having 20 or less non-hydrogen atoms selected from the group consisting of a halogen ion, a hydrocarbon group having 1 to 20 carbon atoms, a hydrocarbonoxy group having 1 to 18 carbon atoms, a hydrocarbonamino group having 1 to 18 carbon atoms, a silyl group, a hydrocarbonamide group having 1 to 18 carbon atoms, a hydrocarbonphosphine group having 1 to 18 carbon atoms, a hydrocarbonthio group having 1 to 18 carbon atoms, and a composite group thereof, wherein two substituents X may be present in some cases. 4 They can form together a neutral conjugated diene or a divalent group having 4 to 30 carbon atoms.

[0256] In formula 9, Y 2 Indicates -O-, -S-, -NR *-or-PR * -, where R * It represents a hydrogen atom, a hydrocarbon group having 1 to 12 carbon atoms, a hydrocarbonoxy group having 1 to 8 carbon atoms, a silyl group, a halogenated alkyl group having 1 to 8 carbon atoms, a halogenated aryl group having 6 to 20 carbon atoms, or a composite group thereof.

[0257] In formula 9, Z 2 SiR * 2 , CR * 2 、SiR * 2 S i * 2 , CR * 2 CR * 2 , CR * =CR * , CR * 2 S i * 2 or GeR * 2 , where R * The definition of is as above, and n is 1, 2 or 3.

[0258] As the transition metal compound with cyclic η-bonding anionic ligand used in the present embodiment, the compounds shown below can be cited. As zirconium-based compounds, there are no particular restrictions, and specifically, for example, bis(methylcyclopentadienyl) zirconium dimethyl, bis(n-butylcyclopentadienyl) zirconium dimethyl, bis(indenyl) zirconium dimethyl, bis(1,3-dimethylcyclopentadienyl) zirconium dimethyl, (pentamethylcyclopentadienyl)(cyclopentadienyl) zirconium dimethyl, bis(cyclopentadienyl) zirconium dimethyl, bis(pentamethylcyclopentadienyl) zirconium dimethyl, bis(fluorenyl) zirconium dimethyl, ethylenebis(indenyl) zirconium dimethyl, ethylenebis(4,5,6,7-tetrahydro-1-indenyl) zirconium dimethyl, ethylenebis(4-methyl-1-indenyl) zirconium dimethyl, ethylenebis(5-methyl-1-indenyl) zirconium dimethyl Methyl zirconium, ethylenebis(6-methyl-1-indenyl)dimethyl zirconium, ethylenebis(7-methyl-1-indenyl)dimethyl zirconium, ethylenebis(5-methoxy-1-indenyl)dimethyl zirconium, ethylenebis(2,3-dimethyl-1-indenyl)dimethyl zirconium, ethylenebis(4,7-dimethyl-1-indenyl)dimethyl zirconium, ethylenebis(4,7-dimethoxy-1-indenyl)dimethyl zirconium, methylenebis(cyclopentadienyl)dimethyl zirconium, isopropylidene(cyclopentadienyl)dimethyl zirconium, isopropylidene(cyclopentadienyl-fluorenyl)dimethyl zirconium, silylenebis(cyclopentadienyl)dimethyl zirconium, dimethylsilylene(cyclopentadienyl)dimethyl zirconium, etc.

[0259] The titanium-based compound is not particularly limited, and specific examples thereof include: [(N-tert-butylamino)(tetramethyl-η 5 -cyclopentadienyl)-1,2-ethanediyl] dimethyltitanium, [(N-tert-butylamino)(tetramethyl-η 5 -cyclopentadienyl)dimethylsilane]dimethyltitanium, [(N-methylamino)(tetramethyl-η 5 -cyclopentadienyl)dimethylsilane]dimethyltitanium, [(N-phenylamino)(tetramethyl-η 5 -cyclopentadienyl)dimethylsilane]dimethyltitanium, [(N-benzylamino)(tetramethyl-η 5 -cyclopentadienyl)dimethylsilane]dimethyltitanium, [(N-tert-butylamino) (η 5 -cyclopentadienyl)-1,2-ethanediyl]dimethyltitanium, [(N-tert-butylamino) (η 5 -cyclopentadienyl)dimethylsilane]dimethyltitanium, [(N-methylamino) (η 5 -cyclopentadienyl)-1,2-ethanediyl] dimethyltitanium, [(N-methylamino) (η 5 -cyclopentadienyl)dimethylsilane]dimethyltitanium, [(N-tert-butylamino) (η 5-indenyl)dimethylsilane]dimethyltitanium, [(N-benzylamino) (η 5 -indenyl)dimethylsilane]dimethyltitanium, etc.

[0260] The nickel-based compound and the palladium-based compound are not particularly limited, and specific examples thereof include dibromobis(triphenylphosphine)nickel, dichlorobis(triphenylphosphine)nickel, dibromodiacetonitrile nickel, dibromodibenzonitrile nickel, dibromo(1,2-bis(diphenylphosphino)ethane)nickel, dibromo(1,3-bis(diphenylphosphino)propane)nickel, dibromo(1,1'-bis(diphenylphosphino)ferrocene)nickel, dimethylbis(diphenylphosphine)nickel, dimethyl(1,2-bis(diphenylphosphino)ethane)nickel, methyl(1,2-bis(diphenylphosphino)ethane)nickel tetrafluoroborate, (2-diphenylphosphino-1-phenylethyleneoxy)phenylpyridine nickel, dichlorobis(triphenylphosphine)palladium, dichlorodibenzonitrile palladium, dichlorodiacetonitrile palladium, dichloro(1,2-bis(diphenylphosphino)ethane)palladium, and bis(triphenylphosphine)palladium bistetrafluoroborate.

[0261] The hafnium-based compound is not particularly limited, and specific examples thereof include: [(N-tert-butylamino)(tetramethyl-η 5 -cyclopentadienyl)-1,2-ethanediyl] dimethyl hafnium, [(N-tert-butylamino)(tetramethyl-η 5 -cyclopentadienyl)dimethylsilane]dimethyl hafnium, [(N-methylamino)(tetramethyl-η 5 -cyclopentadienyl)dimethylsilane]dimethyl hafnium, [(N-phenylamino) (tetramethyl-η 5 -cyclopentadienyl)dimethylsilane]dimethyl hafnium, [(N-benzylamino)(tetramethyl-η 5 -cyclopentadienyl)dimethylsilane]dimethyl hafnium, [(N-tert-butylamino) (η 5 -cyclopentadienyl)-1,2-ethanediyl]dimethyl hafnium, [(N-tert-butylamino) (η 5 -cyclopentadienyl)dimethylsilane]dimethyl hafnium, [(N-methylamino) (η 5 -cyclopentadienyl)-1,2-ethanediyl]dimethyl hafnium, [(N-methylamino) (η 5 -cyclopentadienyl)dimethylsilane]dimethyl hafnium, [(N-tert-butylamino) (η 5 -indenyl)dimethylsilane]dimethyl hafnium, [(N-benzylamino) (η 5 -indenyl)dimethylsilane]dimethylhafnium, etc.

[0262] As specific examples of the transition metal compound having a cyclic η-bonding anionic ligand used in the present embodiment, there can be mentioned a compound having a "dimethyl" portion (which is the portion in the middle of the name of each compound, i.e., the portion immediately preceding the portion called "zirconium" or "titanium") in the name of each zirconium-based compound and titanium-based compound listed above, which is the same as X in the above formula 9. 4 The names corresponding to the parts of the formula (e.g., "dichloro", "dichloro", "diiodo", "diethyl", "dibutyl", "diphenyl", "dibenzyl", "2-(N,N-dimethylamino)benzyl", "2-butene-1,4-diyl", "s-trans-η 4 -1,4-diphenyl-1,3-butadiene", "s-trans-η 4 -3-methyl-1,3-pentadiene", "s-trans-η 4 -1,4-dibenzyl-1,3-butadiene", "s-trans-η 4 -2,4-hexadiene", "s-trans-η 4 -1,3-pentadiene", "s-trans-η 4 -1,4-dimethylbenzene-1,3-butadiene", "s-trans-η 4 -1,4-bis(trimethylsilyl)-1,3-butadiene", "s-cis-η 4 -1,4-diphenyl-1,3-butadiene", "s-cis-η 4 -3-methyl-1,3-pentadiene", "s-cis-η 4 -1,4-dibenzyl-1,3-butadiene", "s-cis-η 4 -2,4-hexadiene", "s-cis-η 4 -1,3-pentadiene", "s-cis-η 4 -1,4-dimethylbenzene-1,3-butadiene", "s-cis-η 4 -1,4-bis(trimethylsilyl)-1,3-butadiene" etc.

[0263] The transition metal compound having a cyclic η-bonding anionic ligand used in the present embodiment can generally be synthesized by a known method. In the present embodiment, these transition metal compounds can be used alone or in combination.

[0264] Next, the activator (hereinafter also simply referred to as “activator”) used in the present embodiment and capable of reacting with b) the transition metal compound to form a complex exhibiting catalytic activity will be described.

[0265] As the activator used in this embodiment, for example, a compound defined by the following formula 10 can be mentioned.

[0266] [L 2 -H] d+ [M 5 m Q p ] d- ……Formula 10

[0267] (In formula 10, [L 2 -H] d+ represents a proton-donating Bronsted acid, where L 2 represents a neutral Lewis base, d is an integer from 1 to 7; [M 5 m Q p ] d- represents a coexistent non-coordinating anion, where M 5 represents a metal or metalloid belonging to any one of Groups 5 to 15 of the periodic table, Q is independently selected from the group consisting of a hydride ion, a halogen ion, a dialkylamino group having 2 to 20 carbon atoms, a alkyloxy group having 1 to 30 carbon atoms, a alkyl group having 1 to 30 carbon atoms, and a substituted alkyl group having 1 to 40 carbon atoms, wherein the number of Q as a halogen ion is 1 or less, m is an integer of 1 to 7, p is an integer of 2 to 14, d is as defined above, and pm=d.)

[0268] The non-coordinating anion is not particularly limited, and specific examples thereof include tetraphenyl boride, tri(p-tolyl)(phenyl) boride, tri(pentafluorophenyl)(phenyl) boride, tri(2,4-dimethylphenyl)(hydroxyphenyl) boride, tri(3,5-dimethylphenyl)(phenyl) boride, tri(3,5-di(trifluoromethyl)phenyl)(phenyl) boride, tri(pentafluorophenyl)(cyclohexyl) boride, tri(pentafluorophenyl)(naphthyl) boride, tetrakis(pentafluorophenyl) boride, triphenyl(hydroxyphenyl) boride, diphenyldi(hydroxyphenyl) boride, triphenyl(2,4-dihydroxyphenyl) boride, ) boride, tris(p-tolyl)(hydroxyphenyl) boride, tris(pentafluorophenyl)(hydroxyphenyl) boride, tris(2,4-dimethylphenyl)(hydroxyphenyl) boride, tris(3,5-dimethylphenyl)(hydroxyphenyl) boride, tris(3,5-di(trifluoromethyl)phenyl)(hydroxyphenyl) boride, tris(pentafluorophenyl)(2-hydroxyethyl) boride, tris(pentafluorophenyl)(4-hydroxybutyl) boride, tris(pentafluorophenyl)(4-hydroxycyclohexyl) boride, tris(pentafluorophenyl)(4-(4'-hydroxyphenyl)phenyl) boride, tris(pentafluorophenyl)(6-hydroxy-2-naphthyl) boride, and the like.

[0269] Other preferred examples of non-coordinating anions include boride compounds in which the hydroxyl group of the above-exemplified boride compounds is replaced by an NHR group. Here, R is preferably a methyl group, an ethyl group or a tert-butyl group.

[0270] In addition, the proton-donating Bronsted acid is not particularly limited, and specific examples thereof include: trialkyl-substituted ammonium cations such as triethylammonium, tripropylammonium, tri-n-butylammonium, trimethylammonium, tributylammonium, and tri-n-octylammonium; N,N-dimethylanilinium, N,N-diethylanilinium, N,N,2,4,6-pentamethylanilinium, and N,N-dimethylbenzylanilinium; dialkylammonium cations such as di(isopropyl)ammonium and dicyclohexylammonium; triphenylammonium; , tri(methylphenyl) 、Tris(dimethylphenyl) isotriaryl cation; or dimethylsulfonium, diethylsulfonium, diphenylsulfonium, etc.

[0271] In addition, in the present embodiment, an organic metal oxide compound having a unit represented by the following formula 11 can also be used as the activator.

[0272] ……Formula 11

[0273] (Here, in Formula 11, M 6 is a metal or metalloid of Group 13 to Group 15 of the Periodic Table, R 14 Each independently represents a hydrocarbon group or a substituted hydrocarbon group having 1 to 12 carbon atoms, and n represents a metal M 6 valence, m is an integer greater than 2. )

[0274] A preferred example of the activator used in the present embodiment is an organic aluminum oxy-compound including a unit represented by Formula 12 below.

[0275] ……Formula 12

[0276] (Here, in Formula 12, R 15 is an alkyl group having 1 to 8 carbon atoms, and m is an integer of 2 to 60.

[0277] A more preferable example of the activator used in the present embodiment is, for example, methylaluminoxane including a unit represented by Formula 13 below.

[0278] ……Formula 13

[0279] (Here, in Formula 13, m is an integer from 2 to 60.)

[0280] In this embodiment, the activator components may be used alone or in combination.

[0281] In the present embodiment, these catalyst components can be supported on solid components and used as supported catalysts. As such solid components, there is no particular limitation, specifically, for example, porous polymer materials such as copolymers of polyethylene, polypropylene or styrene-divinylbenzene can be cited; inorganic solid materials of the 2nd, 3rd, 4th, 13th and 14th group elements of the periodic table such as silicon dioxide, aluminum oxide, magnesium oxide, magnesium chloride, zirconium oxide, titanium oxide, boron oxide, calcium oxide, zinc oxide, barium oxide, vanadium pentoxide, chromium oxide and thorium oxide and their mixtures; and at least one inorganic solid material in their composite oxides.

[0282] There are no particular restrictions on the composite oxide of silicon dioxide, and specifically, for example, composite oxides of silicon dioxide and elements of Group 2 or Group 13 of the periodic table such as silicon dioxide-magnesium oxide and silicon dioxide-aluminum oxide can be cited. In addition, in this embodiment, in addition to the above two catalyst components, an organic aluminum compound can also be used as a catalyst component as needed. The organic aluminum compound that can be used in this embodiment is, for example, a compound represented by the following formula 14.

[0283] ……Formula 14

[0284] (Here, in Formula 14, R 16 is an alkyl group having 1 to 12 carbon atoms or an aryl group having 6 to 20 carbon atoms, X 5 is halogen, hydrogen or alkoxy, alkyl is straight chain alkyl, branched chain alkyl or cyclic alkyl, and n is an integer of 1 to 3.

[0285] Here, the organoaluminum compound may be a mixture of compounds represented by the above formula 14. Examples of the organoaluminum compound that can be used in this embodiment include: 16 is methyl, ethyl, butyl, isobutyl, hexyl, octyl, decyl, phenyl, tolyl, etc., and X 5 , examples include methoxy, ethoxy, butoxy, chlorine, and the like.

[0286] There are no particular restrictions on the organoaluminum compounds that can be used in this embodiment. Specifically, for example, trimethylaluminum, triethylaluminum, tributylaluminum, triisobutylaluminum, trihexylaluminum, trioctylaluminum, tridecylaluminum, etc.; or reaction products of these organoaluminums with alcohols such as methanol, ethanol, butanol, pentanol, hexanol, octanol, decanol, such as dimethyl methoxyaluminum, diethyl ethoxyaluminum, dibutyl butoxyaluminum, etc.

[0287] (Polymerization conditions)

[0288] The polymerization temperature in the method for producing the ultra-high molecular weight polyethylene powder of the present embodiment is usually 30° C. or higher and 100° C. or lower. When the polymerization temperature is 30° C. or higher, there is a tendency that more efficient production can be performed industrially. On the other hand, when the polymerization temperature is 100° C. or lower, there is a tendency that more stable operation can be performed continuously. In addition, regarding the intrinsic viscosity IV of the ultra-high molecular weight polyethylene powder, there is a tendency that the higher the polymerization temperature, the lower the intrinsic viscosity IV, and there is a tendency that the lower the polymerization temperature, the higher the intrinsic viscosity IV.

[0289] In addition, the polymerization pressure in the method for producing the ultra-high molecular weight polyethylene powder of the present embodiment is usually above normal pressure and below 2 MPa. The polymerization pressure is preferably above 0.1 MPa, more preferably above 0.12 MPa, and the polymerization pressure is preferably below 1.5 MPa, more preferably below 1.0 MPa. When the polymerization pressure is above normal pressure, there is a tendency that more efficient production can be performed industrially, and when the polymerization pressure is below 2 MPa, there is a tendency that local heat generation caused by the rapid polymerization reaction when the catalyst is introduced can be suppressed, and polyethylene can be stably produced.

[0290] The polymerization reaction can be carried out in any method of batch (intermittent), semi-continuous, and continuous. From the viewpoint of controlling the pore portion of the ultra-high molecular weight polyethylene powder of the present embodiment within the above-mentioned range, batch (intermittent) is preferred. On the other hand, from the viewpoint of making the polymerization system more uniform, continuous is preferred. By continuously supplying ethylene gas, solvent, catalyst, etc. into the polymerization system, and continuously discharging together with the generated polyethylene, the local high temperature state caused by the rapid reaction of ethylene can be suppressed, making the polymerization system more stable. When ethylene reacts in a uniform state in the system, the generation of side chains, double bonds, etc. in the polymer chain is suppressed, and the low molecular weight and crosslinking of polyethylene are not easy to occur, so the residual unmelted material is reduced when the ultra-high molecular weight polyethylene powder is melted or dissolved, coloring is suppressed, and the problems such as mechanical properties reduction are not easy to occur.

[0291] In addition, polymerization can also be divided into two or more stages with different reaction conditions. In addition, for example, as described in the specification of German Patent Application Publication No. 3127133, the intrinsic viscosity of the polyethylene obtained can also be regulated by making hydrogen exist in the polymerization system or changing the polymerization temperature. By adding hydrogen as a chain transfer agent in the polymerization system, the intrinsic viscosity can be controlled within an appropriate range. By adding a chain transfer agent, there is a tendency that the intrinsic viscosity IV of the ultra-high molecular weight polyethylene generated at the same polymerization temperature also decreases. When hydrogen is added in the polymerization system, the molar fraction of hydrogen is preferably 0 mol % or more and 30 mol % or less, more preferably 0 mol % or more and 25 mol % or less, further preferably 0 mol % or more and 20 mol % or less. It should be noted that in the present embodiment, in addition to each component as described above, other known components useful to the manufacture of polyethylene can also be included.

[0292] In addition, as described above, for the ultra-high molecular weight polyethylene powder of the present embodiment, it is important to immerse the powder in liquid paraffin, and while applying a temperature (50°C to 100°C) at which the powder does not melt and the molecular chains can move, place it under vacuum (300Pa to 400Pa) for 1 hour to 6 hours, so that the liquid paraffin fully enters the inside of the powder pores and gradually untangles the molecular chains. Then, the powder is immersed in hexane for 5 hours to 24 hours, the liquid paraffin is extracted from the powder, and dried at a temperature of 25°C to 50°C for 24 hours, thereby obtaining a powder with a short dissolution time (5 seconds to 80 seconds) (control method 1).

[0293] In addition, a polymer obtained by adding 55% to 70% by mass of liquid paraffin to a polymerization solvent during prepolymerization and performing polymerization is used as a prepolymerization catalyst for main polymerization, and the liquid paraffin is removed from the powder after the polymerization is completed, thereby obtaining a powder with a short dissolution time (more than 5 seconds and less than 80 seconds) (control method 2).

[0294] In addition, by using a prepolymerization catalyst (low temperature (5°C or more and 20°C or less) short time (0.5 hour or more and 2 hours or less) polymerization, ethylene input amount is 5NL or more and 20NL or less) and polymerization is carried out under high pressure (0.5MPa or more and 1.0MPa or less), polymerization can be carried out in a state where the initial polymerization activity is high. Therefore, in the polymerization process, a large amount of polymerization heat energy is generated, and in the process of dissipating this heat energy from the center of the powder to the outside, a connecting hole extending from the center of the powder to the surface is formed, and by further adjusting this heat energy, the connecting hole diameter can be controlled (control method 3).

[0295] When the ultra-high molecular weight polyethylene powder of the present embodiment is obtained by polymerization, in order to suppress the electrostatic adhesion of polymer to the polymerization reactor, antistatic agents such as Stadis and STATSAFE manufactured by Innospec (agent Maruwa Products) can also be used. For antistatic agents such as Stadis and STATSAFE, it is also possible to utilize pumps etc. to add the antistatic agent diluted in an inert hydrocarbon medium to the polymerization reactor. In the method of pre-adding to the solid catalyst, adding to the polymerization reactor, relative to the production of ethylene-based polymers per unit time, the addition at this time is preferably more than 1ppm and less than 500ppm, more preferably more than 10ppm and less than 100ppm.

[0296] [additive]

[0297] Additives such as a lubricant, a neutralizer, an antioxidant, a light stabilizer, an antistatic agent, and a pigment may be added to the ultra-high molecular weight polyethylene powder of the present embodiment as required.

[0298] There are no particular restrictions on the lubricant or neutralizer, and examples thereof include aliphatic hydrocarbons, higher fatty acids, higher fatty acid metal salts, fatty acid esters of alcohols, waxes, higher fatty acid amides, silicone oils, rosin, etc. Specifically, there are no particular restrictions, and examples thereof include calcium stearate. There are no particular restrictions on the content of the lubricant or neutralizer, and it is preferably 5000 ppm or less, more preferably 4000 ppm or less, and further preferably 3000 ppm or less.

[0299] The antioxidant is not particularly limited, and preferably a phenolic compound or a phenolic phosphorus-containing compound. Specifically, phenolic antioxidants such as 2,6-di-tert-butyl-4-methylphenol (butylhydroxytoluene), 3-(4-hydroxy-3,5-di-tert-butylphenyl) propionate, and tetrakis(methylene(3,5-di-tert-butyl-4-hydroxyhydrocinnamate))methane; phenolic phosphorus-containing antioxidants such as 6-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propoxy]-2,4,8,10-tetra-tert-butyldibenzo[d,f][1,3,2]dioxaphosphophetidine; and phosphorus-containing antioxidants such as 4,4'-biphenylene diphosphite tetrakis(2,4-di-tert-butylphenyl) ester, tris(2,4-di-tert-butylphenyl) phosphite, and cyclic neopentane tetraylbis(2,4-tert-butylphenyl phosphite).

[0300] In the ultra-high molecular weight polyethylene powder of the present embodiment, when the total amount of the ultra-high molecular weight polyethylene powder and the liquid paraffin is 100 parts by mass, the amount of the antioxidant is preferably 5 parts by mass or less, more preferably 4 parts by mass or less, further preferably 3 parts by mass or less, and particularly preferably 2 parts by mass or less. When the antioxidant is 5 parts by mass or less, the deterioration of the polyethylene is suppressed, so that embrittlement, discoloration, reduction in mechanical properties, etc. are not likely to occur, and the long-term stability is more excellent.

[0301] The light stabilizer is not particularly limited, and examples thereof include benzotriazole-based light stabilizers such as 2-(5-methyl-2-hydroxyphenyl)benzotriazole and 2-(3-tert-butyl-5-methyl-2-hydroxyphenyl)-5-chlorobenzotriazole; and hindered amine-based light stabilizers such as bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate and poly[{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl}{(2,2,6,6-tetramethyl-4-piperidinyl)imino)hexamethylene}{(2,2,6,6-tetramethyl-4-piperidinyl)imino}]. The content of the light stabilizer is not particularly limited, but is 5000 ppm or less, preferably 3000 ppm or less, and more preferably 2000 ppm or less.

[0302] The antistatic agent is not particularly limited, and examples thereof include aluminosilicate, kaolin, clay, natural silica, synthetic silica, silicates, talc, diatomaceous earth, fatty acid glycerides, and the like.

[0303] As the method for separating the solvent in the polymerization step of the polyethylene powder of the present embodiment, any method such as decantation, centrifugation, or filtration can be applied, but filtration is preferred because it is simple to separate the ethylene polymer from the solvent.

[0304] The method for deactivating the catalyst used in the polymerization step of the ethylene polymer constituting the polyethylene powder of the present embodiment is not particularly limited, but the deactivation of the catalyst is preferably carried out after the ethylene polymer is separated from the solvent.

[0305] By introducing a chemical agent for deactivating the catalyst after separating the polyethylene powder from the solvent, it is possible to suppress precipitation of low molecular weight components, catalyst components, etc. contained in the solvent into the ethylene-based polymer.

[0306] The chemical agent for deactivating the catalyst is not particularly limited, and examples thereof include oxygen, water, alcohols, glycols, phenols, carbon monoxide, carbon dioxide, ethers, carbonyl compounds, and alkynes.

[0307] In the method for producing polyethylene powder of the present embodiment, after separating the ethylene polymer from the solvent, a drying step is preferably performed. In the drying step, a rotary kiln, a paddle type, a fluidized dryer, etc. are preferably used. In addition, the drying temperature is preferably 30° C. or more and 150° C. or less.

[0308] In addition, it is also effective to introduce an inert gas such as nitrogen into the dryer to promote drying. In this case, it is also more effective to add water vapor or the like as a chemical agent to deactivate the catalyst.

[0309] After the ethylene-based polymer constituting the polyethylene powder of the present embodiment is dried, it may be sieved to remove coarse powder.

[0310] The polyethylene powder of the present embodiment may be a mixture of a plurality of polyethylene powders containing an ethylene-based polymer obtained by the above-mentioned production method.

[0311] [Molding body]

[0312] The ultra-high molecular weight polyethylene powder of the present embodiment can be molded by various methods. In addition, the molded body of the present embodiment is obtained by molding the above-mentioned ultra-high molecular weight polyethylene powder. The molded body of the present embodiment can be used for various purposes. As a specific example of the molded body of the present embodiment, there is no restriction, for example, it can be listed: secondary battery separator (such as microporous membrane), fiber (such as high-strength fiber), wherein, it is suitable as a microporous membrane for lithium ion secondary battery separator, high-strength fiber.

[0313] As a method for producing the molded body of the present embodiment, a conventionally known method can be used, and such a method is not particularly limited, and examples thereof include compression molding (press molding), extrusion molding, stretch molding, etc. In addition, the method for producing the molded body in the case of a secondary battery separator or fiber is as follows.

[0314] There are no particular restrictions on the method for manufacturing a secondary battery separator (e.g., a microporous membrane), and examples thereof include: a processing method of extruding, stretching, extracting, and drying using an extruder equipped with a T-die in a wet method using a solvent. Specifically, there are no particular restrictions, and examples thereof include: the following manufacturing methods under general swelling conditions and manufacturing methods under low-temperature swelling conditions.

[0315] (Swelling conditions)

[0316] Ultra-high molecular weight polyethylene powder, liquid paraffin and additives such as antioxidants as needed are mixed, and the mixture is heated to a temperature lower than the melting point (T m2 ) was stirred at a temperature of 35° C. to prepare a slurry-like liquid.

[0317] The obtained slurry-like liquid is put into a kneading machine, kneaded at a certain temperature, and then hot pressed and then cold pressed to form a gel sheet. It should be noted that the thickness of the gel sheet is adjusted by using a metal frame.

[0318] The gel sheet is stretched using a synchronous biaxial stretching machine, and then the stretched film is cut out and fixed on a metal frame. Then, it is immersed in hexane to extract and remove the liquid paraffin, and then dried. Further heat setting is performed to obtain a microporous membrane for a secondary battery separator.

[0319] There are no particular restrictions on the method for producing the fiber (e.g., high-strength fiber), and for example, a method of mixing liquid paraffin and the ultra-high molecular weight polyethylene powder and then heating and stretching them can be cited. Specifically, there are no particular restrictions, and for example, the following production methods under general swelling conditions and production methods under low-temperature swelling conditions can be cited.

[0320] (Swelling conditions)

[0321] Ultra-high molecular weight polyethylene powder, liquid paraffin and additives such as antioxidants as needed are mixed, and the mixture is heated to a temperature lower than the melting point (T m2 ) was stirred at a temperature of 35° C. to prepare a slurry-like liquid.

[0322] Next, the slurry-like liquid is put into a kneading machine and kneaded at a certain temperature.

[0323] Then, the filament was spun by passing through a spinneret installed on a Capilograph 1D.

[0324] At this time, the discharged filaments containing liquid paraffin are wound at a position away from the spinneret.

[0325] Next, in order to remove the liquid paraffin from the wound silk, the silk was immersed in hexane and extracted, and then dried.

[0326] The obtained yarn is drawn once in a thermostatic chamber, and then drawn twice in the thermostatic chamber until the yarn is about to break, thereby obtaining a high-strength fiber (drawn yarn).

[0327] [High-strength fiber]

[0328] Specific examples of the method for producing high-strength fibers include a method comprising a slurry step, a gelling step, an optional kneading step, an optional extrusion preparation step, an extrusion step, an optional quenching step, an extraction step, and a raw yarn drawing step.

[0329] (Slurry process)

[0330] The slurry step is a step of mixing the ultra-high molecular weight polyethylene powder and the first liquid paraffin, and stirring the mixture at a temperature below the melting point of the ultra-high molecular weight polyethylene powder to obtain a slurry.

[0331] The stirring temperature is preferably 25°C to 120°C, more preferably 50°C to 115°C, further preferably 80°C to 110°C, particularly preferably 90°C to 105°C.

[0332] By setting the stirring temperature to 25° C. or higher, the liquid paraffin can be more effectively impregnated into the pores of the ultra-high molecular weight polyethylene powder. In addition, by setting the stirring temperature to 120° C. or lower, the melting of the surface of the ultra-high molecular weight polyethylene powder can be suppressed, and the fusion of the powders can be prevented, thereby obtaining a uniform gel in which the entanglement of the molecular chains is untangled.

[0333] (Gelation process)

[0334] The gelling step is a step of mixing the slurry with a second liquid paraffin having a temperature of 150° C. to 300° C. to obtain a raw yarn gel having a temperature of 140° C. to 200° C.

[0335] By adjusting the temperature of the precursor gel to 140°C or higher, a uniform gel with untangled molecular chains can be obtained in a short time. In addition, by adjusting the temperature of the precursor gel to 200°C or lower, a significant decrease in molecular weight due to thermal decomposition can be suppressed.

[0336] The temperature of the second liquid paraffin is preferably 150°C to 250°C, more preferably 150°C to 200°C, and even more preferably 150°C to 180°C.

[0337] The temperature of the gel for the raw fibers is preferably 140° C. or higher and 190° C. or lower, more preferably 140° C. or higher and 180° C. or lower, and even more preferably 140° C. or higher and 170° C. or lower.

[0338] The polyethylene concentration of the precursor gel is preferably 3% by mass to 20% by mass, more preferably 3% by mass to 15% by mass, further preferably 3% by mass to 10% by mass, particularly preferably 3% by mass to 8% by mass.

[0339] By adjusting the polyethylene concentration of the precursor gel to 3% by mass or more, a precursor with a small uneven diameter can be stably spun. In addition, by adjusting the polyethylene concentration of the precursor gel to 20% by mass or less, a precursor with untangled molecular chains can be obtained.

[0340] (Mixing process)

[0341] The kneading step is a step of kneading the raw yarn gel.

[0342] The kneading temperature is preferably 140°C to 200°C, more preferably 140°C to 180°C, further preferably 140°C to 170°C, particularly preferably 150°C to 160°C.

[0343] By setting the kneading temperature to 140° C. or higher, a uniform gel in which the molecular chains are untangled can be obtained. In addition, by setting the kneading temperature to 200° C. or lower, a significant decrease in molecular weight due to thermal decomposition can be suppressed.

[0344] The kneading time is preferably 5 minutes to 180 minutes, more preferably 10 minutes to 150 minutes, further preferably 15 minutes to 90 minutes, particularly preferably 30 minutes to 60 minutes.

[0345] By setting the kneading time to 5 minutes or more, a uniform gel in which the molecular chains are untangled can be obtained. In addition, by setting the kneading time to 180 minutes or less, a significant decrease in molecular weight due to thermal decomposition can be suppressed.

[0346] The rotation speed of kneading is preferably 3 rpm to 50 rpm, more preferably 3 rpm to 30 rpm, further preferably 3 rpm to 20 rpm, particularly preferably 3 rpm to 10 rpm.

[0347] By setting the kneading speed to 3 rpm or more, a uniform gel in which the molecular chains are untangled can be obtained. In addition, by setting the kneading speed to 50 rpm or less, a significant decrease in molecular weight due to thermal decomposition can be suppressed.

[0348] (Extrusion preparation process)

[0349] The extrusion preparation step is a step of preparing the gel for the precursor yarn before extruding it. Specific examples of the extrusion preparation include temperature adjustment and degassing of the gel for the precursor yarn.

[0350] The temperature in the extrusion preparation step is preferably 140°C to 200°C, more preferably 140°C to 190°C, further preferably 140°C to 180°C, particularly preferably 150°C to 180°C.

[0351] By setting the temperature of the extrusion preparation process to 140°C or higher, liquid paraffin can be prevented from flowing out of the raw yarn gel, and the change of gel concentration can be suppressed, thereby stably obtaining raw yarn. In addition, by setting the temperature of the extrusion preparation process to 200°C or lower, a significant decrease in molecular weight caused by thermal decomposition can be suppressed.

[0352] The time for the extrusion preparation step (for example, the degassing time) is preferably 5 minutes to 90 minutes, more preferably 5 minutes to 60 minutes, further preferably 15 minutes to 60 minutes, particularly preferably 30 minutes to 60 minutes.

[0353] By setting the time of the extrusion preparation process to more than 5 minutes, the degassing of the precursor gel can be fully carried out, and the precursor can be stably obtained. In addition, by setting the time of the extrusion preparation process to less than 90 minutes, the significant molecular weight reduction caused by thermal decomposition can be suppressed.

[0354] (Extrusion process)

[0355] The extrusion step is a step of extruding the above-mentioned precursor gel to obtain a precursor.

[0356] The extrusion speed is preferably 5 mm / min to 20 mm / min, more preferably 5 mm / min to 15 mm / min, further preferably 7.5 mm / min to 12 mm / min, particularly preferably 7.5 mm / min to 10 mm / min.

[0357] By setting the extrusion speed to 5 mm / min or more, the raw yarn can be recovered without applying tension to the raw yarn, and in the raw yarn drawing process, it can be stretched to a high multiple, and a highly oriented (high strength) yarn can be obtained. In addition, by setting the extrusion speed to 20 mm / min or less, the discharge amount can be stabilized, and raw yarns with small uneven yarn diameters can be stably obtained.

[0358] The winding speed is preferably 200 mm / min to 1600 mm / min, more preferably 200 mm / min to 1400 mm / min, further preferably 250 mm / min to 1000 mm / min, particularly preferably 500 mm / min to 800 mm / min.

[0359] By setting the winding speed to 200 mm / min or more, the raw yarn can be recovered without applying tension to the raw yarn, and in the raw yarn drawing process, it can be stretched to a high multiple, and a highly oriented (high strength) yarn can be obtained. In addition, by setting the winding speed to 1600 mm / min or less, the discharge amount can be stabilized, and raw yarn with small yarn diameter unevenness can be stably obtained.

[0360] The discharge amount is preferably 0.2 g / min to 1.5 g / min, more preferably 0.2 g / min to 1.2 g / min, further preferably 0.2 g / min to 1.0 g / min, particularly preferably 0.3 g / min to 0.8 g / min.

[0361] By setting the discharge rate to 0.2 g / min or more, the raw yarn can be recovered without applying tension to the raw yarn, and in the raw yarn drawing process, it can be stretched to a high multiple, and a highly oriented (high strength) yarn can be obtained. In addition, by setting the discharge rate to 1.5 g / min or less, melt fracture can be suppressed, and raw yarn with small yarn diameter unevenness can be stably obtained.

[0362] The spinning hole diameter is preferably 0.8 mm to 1.5 mm, more preferably 0.8 mm to 1.2 mm, further preferably 0.8 mm to 1.0 mm, particularly preferably 0.9 mm to 1.0 mm.

[0363] By setting the spinning hole diameter to be above 0.8 mm, the diameter of the raw yarn after extracting the liquid paraffin can be adjusted to a certain degree of thickness, and in the raw yarn drawing process, it can be stretched to a high multiple, thereby obtaining a highly oriented (high strength) yarn. In addition, by setting the spinning hole diameter to be below 1.5 mm, the time for extracting the liquid paraffin from the raw yarn can be shortened, and the extraction operation can be completed efficiently.

[0364] (quick cooling process)

[0365] The rapid cooling step is a step of rapidly cooling the raw yarn. The rapid cooling method is not particularly limited, and an example thereof includes a method of passing the raw yarn through a water bath.

[0366] The time from the extrusion step to the rapid cooling step (for example, the time until the extruded raw yarn enters the water bath) is preferably 0 seconds to 10 seconds, more preferably 0 seconds to 5 seconds, and even more preferably 0 seconds to 2 seconds.

[0367] By setting the time from the extrusion step to the rapid cooling step to 10 seconds or less, the molten yarn can be rapidly cooled and solidified, and the variation in the yarn diameter can be minimized.

[0368] In the rapid cooling process, when the raw yarn is passed through a water bath, the distance from the spinning nozzle to the water surface of the water bath is preferably greater than 0 cm and less than 10 cm, more preferably greater than 1 cm and less than 8 cm, further preferably greater than 1 cm and less than 5 cm, and particularly preferably greater than 1 cm and less than 3 cm.

[0369] By setting the distance from the spinning nozzle to the water surface of the water bath to 10 cm or less, the molten precursor fibers can be rapidly cooled and solidified, and the variation in the diameter of the precursor fibers can be minimized.

[0370] The temperature of the rapid cooling step is preferably 5°C to 30°C, more preferably 5°C to 25°C, further preferably 5°C to 20°C, particularly preferably 5°C to 15°C.

[0371] By setting the quenching temperature to 5°C or higher, cooling costs can be reduced and efficient production can be achieved. In addition, by setting the quenching temperature to 30°C or lower, the molten raw yarn can be quenched and solidified, and the unevenness of the raw yarn diameter can be minimized.

[0372] (Extraction process)

[0373] The extraction step is a step of extracting the first liquid paraffin and the second liquid paraffin from the raw yarn to obtain the raw yarn for drawing.

[0374] In order to extract the liquid paraffin, it is preferable to use an extraction solvent. The extraction solvent is not particularly limited, and examples thereof include hexane and dichloromethane.

[0375] The extraction method is not particularly limited, and an example thereof includes a method of immersing the raw silk in an extraction solvent.

[0376] The extraction time is preferably 3 hours to 24 hours, more preferably 3 hours to 20 hours, further preferably 5 hours to 20 hours, particularly preferably 10 hours to 20 hours.

[0377] By setting the extraction time to more than 3 hours, liquid paraffin can be extracted to a range where there is no problem as a stretching precursor. When the amount of liquid paraffin remaining in the stretching precursor is large, when heated in the precursor stretching process, the mobility of the molecular chain is high, and it is easy to carry out high orientation, but it is difficult to maintain this state (easy to return to the state before high orientation). Therefore, it is difficult to obtain high-strength silk. In addition, by setting the extraction time to less than 24 hours, the stretching precursor can be efficiently obtained without reducing productivity.

[0378] (Yarn stretching process)

[0379] The raw yarn stretching step is a step of heating and stretching the raw yarn for stretching.

[0380] The stretching is preferably multi-stage stretching, more preferably two-stage stretching. The two-stage stretching preferably includes a primary stretching step and a secondary stretching step.

[0381] (First stretching process)

[0382] The delivery speed is preferably 50 mm / min to 200 mm / min, more preferably 50 mm / min to 150 mm / min, further preferably 50 mm / min to 120 mm / min, particularly preferably 50 mm / min to 100 mm / min.

[0383] The winding speed is preferably 1000 mm / min to 4000 mm / min, more preferably 1000 mm / min to 3500 mm / min, further preferably 1500 mm / min to 3500 mm / min, particularly preferably 2000 mm / min to 3000 mm / min.

[0384] It should be noted that the stretching ratio is controlled by adjusting the feeding speed and the winding speed, and is set in consideration of productivity.

[0385] The stretching temperature is preferably 110°C to 155°C, more preferably 110°C to 150°C, further preferably 115°C to 145°C, particularly preferably 120°C to 140°C.

[0386] By setting the stretching temperature to 110°C or higher, stretching can be performed with high molecular chain mobility, and high orientation can be achieved. In addition, by setting the stretching temperature to 155°C or lower, stretching can be performed without melting the stretching yarn.

[0387] (Secondary stretching process)

[0388] The delivery speed is preferably 50 mm / min to 200 mm / min, more preferably 50 mm / min to 150 mm / min, further preferably 50 mm / min to 120 mm / min, particularly preferably 50 mm / min to 100 mm / min.

[0389] The winding speed is preferably 100 mm / min to 500 mm / min, more preferably 100 mm / min to 450 mm / min, further preferably 150 mm / min to 400 mm / min, particularly preferably 200 mm / min to 300 mm / min.

[0390] It should be noted that the stretching ratio is controlled by adjusting the feeding speed and the winding speed, and is set in consideration of productivity.

[0391] The stretching temperature is preferably 130°C to 155°C, more preferably 130°C to 150°C, further preferably 135°C to 150°C, particularly preferably 140°C to 150°C.

[0392] By setting the stretching temperature to 130°C or higher, stretching can be performed with high molecular chain mobility, and high orientation can be achieved. In addition, by setting the stretching temperature to 155°C or lower, stretching can be performed without melting the primary stretched yarn.

[0393] [Microporous membrane]

[0394] As a specific method for producing the microporous membrane, for example, there can be mentioned a method comprising a slurry step, a gelling step, an optional kneading step, a pressing step, a membrane stretching step, and an extraction step.

[0395] (Slurry process)

[0396] The slurry step is a step of mixing the ultra-high molecular weight polyethylene powder and the first liquid paraffin, and stirring the mixture at a temperature below the melting point of the ultra-high molecular weight polyethylene powder to obtain a slurry.

[0397] The stirring temperature is preferably 25°C to 120°C, more preferably 50°C to 115°C, further preferably 80°C to 110°C, particularly preferably 90°C to 105°C.

[0398] By setting the stirring temperature to 25° C. or higher, the liquid paraffin can be efficiently impregnated into the pores of the ultra-high molecular weight polyethylene powder. In addition, by setting the stirring temperature to 120° C. or lower, the melting of the surface of the ultra-high molecular weight polyethylene powder can be suppressed, and the fusion of the powders can be prevented, thereby obtaining a uniform gel in which the entanglement of the molecular chains is untangled.

[0399] (Gelation process)

[0400] The gelling step is a step of mixing the slurry with a second liquid paraffin having a temperature of 150° C. to 300° C. to obtain a gel for pressing having a temperature of 140° C. to 200° C.

[0401] By adjusting the temperature of the gel for pressing to 140° C. or higher, a uniform gel with untangled molecular chains can be obtained in a short time. In addition, by adjusting the temperature of the gel for pressing to 200° C. or lower, a significant decrease in molecular weight due to thermal decomposition can be suppressed.

[0402] The temperature of the second liquid paraffin is preferably 160°C to 210°C, more preferably 170°C to 200°C, and further preferably 180°C to 200°C.

[0403] The polyethylene concentration of the gel for pressing is preferably 20% by mass to 55% by mass, more preferably 20% by mass to 50% by mass, further preferably 20% by mass to 40% by mass, particularly preferably 20% by mass to 30% by mass.

[0404] By adjusting the polyethylene concentration of the pressing gel to 20% by mass or more, a pressed sheet with less uneven thickness can be stably produced. In addition, by adjusting the polyethylene concentration of the pressing gel to 55% by mass or less, a pressed sheet with untangled molecular chains can be obtained.

[0405] (Mixing process)

[0406] The kneading step is a step of kneading the above-mentioned gel for pressing.

[0407] The kneading temperature is preferably 140°C to 250°C, more preferably 150°C to 240°C, further preferably 160°C to 230°C, particularly preferably 180°C to 220°C.

[0408] By setting the kneading temperature to 140° C. or higher, a uniform gel in which the molecular chains are untangled can be obtained. In addition, by setting the kneading temperature to 250° C. or lower, a significant decrease in molecular weight due to thermal decomposition can be suppressed.

[0409] The kneading time is preferably 5 minutes to 60 minutes, more preferably 5 minutes to 40 minutes, further preferably 5 minutes to 30 minutes, particularly preferably 5 minutes to 20 minutes.

[0410] By setting the kneading time to 5 minutes or more, a uniform gel in which the molecular chains are untangled can be obtained. In addition, by setting the kneading time to 60 minutes or less, a significant decrease in molecular weight due to thermal decomposition can be suppressed.

[0411] The rotation speed of kneading is preferably 30 rpm to 100 rpm, more preferably 30 rpm to 80 rpm, further preferably 30 rpm to 70 rpm, particularly preferably 30 rpm to 60 rpm.

[0412] By setting the kneading rotation speed to 30 rpm or more, a uniform gel in which the molecular chains are untangled can be obtained. In addition, by setting the kneading rotation speed to 100 rpm or less, a significant decrease in molecular weight due to thermal decomposition can be suppressed.

[0413] (Pressing process)

[0414] The pressing step is a step of hot-pressing the gel for pressing to obtain a gel sheet.

[0415] In the pressing process, it is preferred to use a 1.0 mm metal frame so that the thickness of the gel sheet is 1.0 mm.

[0416] In the pressing step, it is preferred to adjust the temperature and pressure in multiple stages (preferably three stages) to perform the pressing. For example, it is preferred that:

[0417] In the first stage, heating is performed at a temperature of 180°C or less and 220°C or less, a pressure of 1 MPa, and a time of 3 minutes;

[0418] In the first stage, heating is performed at a temperature of 180°C or less and 220°C or less, a pressure of 10 MPa, and a time of 2 minutes;

[0419] In the third stage, cooling was performed under the conditions of a temperature of 20° C. or lower and 35° C. or lower, a pressure of 10 MPa, and a time of 5 minutes.

[0420] (Film stretching process)

[0421] The film stretching step is a step of stretching the gel sheet to obtain a stretched film.

[0422] The stretching is preferably simultaneous biaxial stretching.

[0423] The stretching temperature is preferably 110°C or higher and 130°C or lower.

[0424] By setting the stretching temperature to 110° C. or higher, stretching can be performed with high mobility of the molecular chains, and high orientation can be achieved. In addition, by setting the stretching temperature to 130° C. or lower, stretching can be performed without melting the gel sheet.

[0425] The stretching ratio in the longitudinal direction is preferably 5 times or more and 20 times or less, more preferably 7 times or more and 18 times or less, and further preferably 10 times or more and 16 times or less.

[0426] The stretching ratio in the transverse direction is preferably 5 times or more and 20 times or less, more preferably 7 times or more and 18 times or less, and further preferably 10 times or more and 16 times or less.

[0427] In addition, the stretching ratio is set in consideration of the strength and productivity of the film.

[0428] (Extraction process)

[0429] The extraction step is a step of extracting the first liquid paraffin and the second liquid paraffin from the stretched film.

[0430] In order to extract the liquid paraffin, it is preferable to use an extraction solvent. The extraction solvent is not particularly limited, and examples thereof include hexane and dichloromethane.

[0431] The extraction method is not particularly limited, and examples thereof include a method of immersing the stretched film in an extraction solvent.

[0432] The extraction time is preferably 3 hours to 24 hours, more preferably 3 hours to 20 hours, further preferably 5 hours to 20 hours, particularly preferably 10 hours to 20 hours.

[0433] Example

[0434] Hereinafter, the present invention will be described in more detail using Examples and Comparative Examples, but the present invention is not limited to the following Examples at all.

[0435] Here, ethylene and hexane used in Examples and Comparative Examples were dehydrated using MS-3A (manufactured by Showa Union), and hexane was further deoxygenated by degassing under reduced pressure using a vacuum pump before use.

[0436] The liquid paraffin used in the examples and comparative examples is liquid paraffin manufactured by MORESCO Co., Ltd. (product name: SMOIL P-350P). Representative properties are: Density 15°C: 0.866 g / cm 3 , pour point: -10℃, kinematic viscosity at 40℃: 68.00mm 2 / sec (cSt), kinematic viscosity 100℃: 9.188mm 2 / second (cSt), ring analysis Cn: 30%, Cp: 70%, average molecular weight: 489g / mole.

[0437] [Measurement method and conditions]

[0438] The physical properties of the ultra-high molecular weight polyethylene powders of Examples and Comparative Examples were measured by the following methods.

[0439] (Measurement 1) Intrinsic viscosity IV

[0440] The intrinsic viscosity IV of the ultra-high molecular weight polyethylene powder obtained in the Examples and Comparative Examples was measured as follows in accordance with ISO 1628-3 (2010).

[0441] Weigh 4.0 mg to 4.5 mg of polyethylene powder, degassing with a vacuum pump and replacing with nitrogen, 20 mL of decalin (added with 1 g / L of 2,6-di-tert-butyl-4-methylphenol, hereinafter referred to as decalin) as a solvent, in a dissolving tube after degassing the air inside with a vacuum pump and replacing with nitrogen, stirring at 150°C for 90 minutes to dissolve it, thereby obtaining a solution. As a viscosity tube, a Cannon-Fenske viscometer (manufactured by Shibata Scientific Instruments Co., Ltd.: Product No. -100) was used. Repeat this operation 5 times, calculate the average value of the three points after removing the maximum and minimum values, and calculate the final intrinsic viscosity.

[0442] (Measurement 2) Dissolution time

[0443] The dissolution time of the ultra-high molecular weight polyethylene powder obtained in Examples and Comparative Examples was calculated by sequentially performing the following steps 1 and 2.

[0444] [Step 1: Calculation of D50]

[0445] The particle size of the ultra-high molecular weight polyethylene powder as the object was measured using a laser particle size distribution instrument (manufactured by Shimadzu Corporation, SALD-2100) with methanol as the dispersion medium, and the cumulative particle size distribution from the small particle size side was prepared based on the measurement, and the particle size when the accumulation reached 50% was taken as D50. This operation was repeated 5 times, and the average value of the three points after removing the maximum and minimum values ​​was calculated, and the final D50 was calculated.

[0446] [Step 2: Calculation of dissolution time]

[0447] Calculate the dissolution time of the powder with a particle size of D50. First, while confirming the long axis diameter and the short axis diameter (for the plane figure of the particle observed using an optical microscope, the distance between the parallel lines with the shortest interval is the short axis diameter of the particle, and the distance between the parallel lines with the longest interval in the perpendicular direction is the long axis diameter of the particle) in the range of D50±10% by using an optical microscope, arbitrarily select one ultra-high molecular weight polyethylene powder. The selected one ultra-high molecular weight polyethylene powder (hereinafter also recorded as "measurement particle") is set on a slide, 0.05mL of liquid paraffin is dripped onto the measurement particle using a 1mL syringe, and then a cover glass is placed and the measurement particle is clamped. Then, the slide is set on a heating table and heated from room temperature to 150°C under the following heating conditions. The appearance of the measurement particle during heating is photographed every 5 seconds using an optical microscope with a camera. The equivalent circle diameter of the measurement particle is calculated from each observed image obtained, and the time from the state with the largest equivalent circle diameter to the disappearance of the powder is taken as the dissolution time. This operation was repeated 10 times, and the average value of 8 points after removing the maximum and minimum values ​​was calculated, and the final dissolution time was calculated.

[0448] (Temperature rising conditions)

[0449] Heating rate from room temperature to 35°C: 5°C / min

[0450] Heating rate within the range of 35℃~80℃: 8℃ / min

[0451] Heating rate within the range of 80℃~150℃: 5℃ / min

[0452] (Measurement 3) Ratio of interconnected pores in powder with a particle size of D50

[0453] The ratio of the interconnected pores of the ultra-high molecular weight polyethylene powders obtained in Examples and Comparative Examples was calculated by the following step 3.

[0454] [Step 3: Ratio of connected pores]

[0455] Select 5 particles of ultra-high molecular weight polyethylene powder whose major axis diameter and minor axis diameter (for the plane figure of the particles observed using an optical microscope, the distance between the shortest parallel lines is taken as the minor axis diameter of the particle, and the distance between the longest parallel lines in the perpendicular direction is taken as the major axis diameter of the particle) within the range of D50±10%, stick double-sided tape on the sample table, and place 5 particles of powder on it.

[0456] Next, the powder was irradiated with X-rays using nano3DX (manufactured by Rigaku Corporation) to capture three-dimensional image data, and then image analysis software was used to process the image to calculate the ratio of the interconnected pores. The X-ray conditions and the capturing conditions were as follows.

[0457] [X-ray conditions] X-ray target: Cu

[0458] X-ray tube voltage / tube current: 40kV / 30mA

[0459] [Shooting conditions] Rotate 180°

[0460] Number of projections: 1000 pieces

[0461] Exposure time: 10 seconds / film

[0462] Spatial resolution: 0.54μm / pix

[0463] Then, the captured images are analyzed using analysis software. The captured images and their tomographic images are displayed on Figure 1 and Figure 2 middle.

[0464] [Analysis scope]

[0465] The range in which the powder does not contact the adhesive substance of the double-sided tape in the direction perpendicular to the horizontal surface of the sample stage is defined as the analysis range.

[0466] [Resin area detection steps]

[0467] Noise Removal 1

[0468] 1. Apply ImageJ's Median3D to X-ray CT images.

[0469] The parameters are set to x=2, y=2, Z=2.

[0470] 2. Apply Morphological Filters (3D) of MorphLibJ to the result of 1.

[0471] The parameters are set to operation=Closing, element=Ball, x-radius=2, y-radius=2, z-radius=2.

[0472] 3. Apply Gaussian Blur3D of ImageJ to the result of step 2.

[0473] The parameters are set to x=2, y=2, Z=2.

[0474] Binarization

[0475] 4. For the result of 3, voxels with brightness values ​​exceeding the threshold are set to white, and voxels with brightness values ​​below the threshold are set to black. The threshold is estimated using the method of moments implemented in ImageJ.

[0476] Noise Removal 2

[0477] 5. For the result of 4, divide the white voxels into blocks of continuous voxels, and change the blocks with less than 1000 voxels to black. The block division process uses 3D Simple Segmentation of 3D Suite ImageJ.

[0478] The black and white voxel data obtained by the process of step 5 is referred to as P. In addition, the white area in P is referred to as the resin area (A).

[0479] [Steps for detecting closed cell areas]

[0480] 6. Apply 3D Fill Holes of 3D Suite ImageJ to P.

[0481] 7. Set the voxel of the result of 6 that is located at the same position as the white voxel of P to black.

[0482] The black and white voxel data obtained by the process of step 7 is referred to as Q. In addition, the white area in Q is referred to as the closed cell area (B).

[0483] [Particle shape detection steps]

[0484] 8. Use 3D DistanceMap of 3D Suite ImageJ to find the distance to the nearest white voxel for each voxel of P.

[0485] The parameters are set as map=EDT, mask=None, threshold=1, inverse.

[0486] 9. Reset the voxels whose result of 8 is less than 20 to white, and set the other voxels to black.

[0487] 10. Apply ImageJ's 2D Fill Holes to the bottom slice in the analysis range.

[0488] 11. Apply 3D Fill Holes of 3D Suite ImageJ to the whole.

[0489] 12. Use 3D DistanceMap of 3D Suite ImageJ to find the distance to the nearest black voxel for each voxel of the result of 11.

[0490] The parameters are set as map=EDT, mask=None, threshold=1, inverse.

[0491] 13. Reset the voxels whose result of 12 is less than 20 to black, and set the other voxels to white.

[0492] The black and white voxel data of the result of 13 is defined as R. In addition, the white area in R is defined as the outer shape of the particle (C).

[0493] [Step of detecting the area of ​​the communicating hole]

[0494] 14. Set the voxels of R located at the same position as the white voxels of Q to black.

[0495] 15. Set the voxel of the result of 14 located at the same position as the white voxel of P to black.

[0496] The black and white voxel data of the result of 15 is defined as S. In addition, the white area in S is defined as the area of ​​the communicating hole (D).

[0497] [Connected pore area (D)] = [Particle shape (C)] - [Closed pore area (B)] - [Resin area (A)]

[0498] [Ratio of connected pores]

[0499] Ratio of connected holes = total number of white voxels in S / total number of white voxels in R

[0500] This series of operations was performed on five powder grains, and the average value was taken as the final ratio of communicating pores.

[0501] (Measurement 4) Wall thickness of powder surface with particle size D50

[0502] The wall thickness of the surface of the ultra-high molecular weight polyethylene powder obtained in the examples and comparative examples was calculated by the following step 4.

[0503] [Step 4: Wall thickness of powder surface]

[0504] 16. Use BoneJ to calculate the thickness of P.

[0505] 17. The median thickness of voxels with thickness greater than 0 is taken as the wall thickness.

[0506] This series of operations was performed on five particles of powder, and the average value was taken as the final wall thickness of the powder surface.

[0507] (Measurement 5) Diameter of connected pores of powder with particle size D50

[0508] The continuous pore diameter of the ultra-high molecular weight polyethylene powder obtained in Examples and Comparative Examples was calculated by the following step 5.

[0509] [Step 5: Connecting hole diameter]

[0510] 18. Use BoneJ to calculate the thickness of S.

[0511] 19. The median thickness of voxels with thickness greater than 0 is taken as the diameter of the connected hole.

[0512] This series of operations was performed on five particles of powder, and the average value was taken as the final communicating pore diameter.

[0513] (Measurement 6) Ti and Al content in ultra-high molecular weight polyethylene powder

[0514] The ultra-high molecular weight polyethylene powder obtained in the examples and comparative examples was pressure-decomposed using a microwave decomposition device (model ETHOS TC, manufactured by Milestone General), and the element concentrations of titanium (Ti) and aluminum (Al) as metal-containing elements in the ultra-high molecular weight polyethylene powder were measured by the internal standard method using ICP-MS (inductively coupled plasma mass spectrometer, model X series X7, manufactured by Thermo Fisher Scientific).

[0515] (Measurement 7) Average particle size (D50) of ultra-high molecular weight polyethylene powder

[0516] The particle size of the ultra-high molecular weight polyethylene powder obtained in the examples and comparative examples was measured using a laser particle size distribution analyzer (manufactured by Shimadzu Corporation, SALD-2100). Methanol was used as a dispersion medium for measurement, and based on the measurement, a cumulative particle size distribution from the small particle size side was prepared, and the particle size when the accumulation reached 50% was taken as the average particle size D50. This operation was repeated 5 times, and the average value of the three points after removing the maximum and minimum values ​​was calculated, and the final D50 was calculated.

[0517] (Method 1-1 for producing molded article) Method for producing a separator (microporous membrane) for a secondary battery at a high polymer concentration

[0518] Using the ultra-high molecular weight polyethylene powders obtained in Examples and Comparative Examples, secondary battery separators were produced as follows.

[0519] When the total amount of the ultra-high molecular weight polyethylene powder and the liquid paraffin is 100 parts by mass, 45 parts by mass of the ultra-high molecular weight polyethylene powder, 55 parts by mass of liquid paraffin (manufactured by MORESCO Co., Ltd., liquid paraffin (product name: SMOIL P-350P)) and 1 part by mass of an antioxidant (manufactured by Oko Chemical Co., Ltd., tetrakis[methylene(3,5-di-tert-butyl-4-hydroxyhydrocinnamate)]methane (product name: ANOX20)) are blended and the mixture is stirred at a temperature lower than the melting point (T m2) was stirred at a temperature of 35° C. for 30 minutes, thereby preparing a slurry-like liquid.

[0520] The obtained slurry-like liquid was put into Labo Plastomill (main body model: 4C150-01) manufactured by Toyo Seiki Co., Ltd., and kneaded at a constant temperature of 200°C for 10 minutes and a screw speed of 50 rpm, and then hot pressed at 180°C / 1MPa / 3 minutes, and further hot pressed at 180°C / 10MPa / 2 minutes, and then cold pressed at 25°C / 10MPa / 5 minutes to form a gel sheet. It should be noted that the thickness of the gel sheet was adjusted to 1.0 mm by using a metal frame with a thickness of 1.0 mm.

[0521] The gel sheet was stretched to 7×7 times at 115°C using a synchronous biaxial stretching machine, and then the stretched film was cut into about 30 cm squares and fixed on a metal frame with an inner size of 25 cm square. Then, it was immersed in hexane to extract and remove the liquid paraffin, and then dried for more than 24 hours. It was further heat-set at 134°C for 1 minute to obtain a secondary battery separator.

[0522] (Method 1-2 for producing molded article) Method for producing a separator (microporous membrane) for a secondary battery at a high polymer concentration

[0523] Using the ultra-high molecular weight polyethylene powders obtained in Examples and Comparative Examples, secondary battery separators were produced as follows.

[0524] When the total amount of the ultra-high molecular weight polyethylene powder and the liquid paraffin is 100 parts by mass, 55 parts by mass of the ultra-high molecular weight polyethylene powder, 45 parts by mass of liquid paraffin (manufactured by MORESCO Co., Ltd., liquid paraffin (product name: SMOIL P-350P)) and 1 part by mass of an antioxidant (manufactured by Oko Chemical Japan Co., Ltd., tetrakis[methylene(3,5-di-tert-butyl-4-hydroxyhydrocinnamate)]methane (product name: ANOX20)) are blended and the mixture is stirred at a temperature lower than the melting point (T m2 ) was stirred at a temperature of 35° C. for 60 minutes, thereby preparing a slurry-like liquid.

[0525] Next, the slurry-like liquid was poured into liquid paraffin (manufactured by MORESCO CORPORATION, liquid paraffin (product name: SMOIL P-350P)) at 180° C. and stirred for 2 minutes to prepare a gel having a polymer concentration of 45 parts by mass.

[0526] The obtained gel was put into Labo Plastomill (main body model: 4C150-01) manufactured by Toyo Seiki Co., Ltd., and kneaded at a constant temperature of 200°C for 10 minutes and a screw speed of 50 rpm, and then hot pressed at 180°C / 1MPa / 3 minutes, further hot pressed at 180°C / 10MPa / 2 minutes, and then cold pressed at 25°C / 10MPa / 5 minutes to form a gel sheet. It should be noted that the thickness of the gel sheet was adjusted to 1.0 mm by using a metal frame with a thickness of 1.0 mm.

[0527] The gel sheet was stretched at 115°C to a limit of film rupture within a range of 7×7 times or more and 20×20 times or less using a synchronous biaxial stretching machine, and then the stretched film was cut into about 30 cm squares and fixed on a metal frame with an inner size of 25 cm square. Then, it was immersed in hexane, the liquid paraffin was extracted and removed, and then dried for more than 24 hours. It was further heat-set at 134°C for 1 minute to obtain a secondary battery separator.

[0528] (Method 2-1 for producing molded article) Method for producing a secondary battery separator at a general polymer concentration

[0529] When the total amount of ultra-high molecular weight polyethylene powder and liquid paraffin is set to 100 parts by mass, 25 parts by mass of ultra-high molecular weight polyethylene powder and 75 parts by mass of liquid paraffin (manufactured by MORESCO Co., Ltd., liquid paraffin (product name: SMOIL P-350P)) and 1 part by mass of an antioxidant (manufactured by Dahu Chemical Japan Co., Ltd., tetrakis [methylene (3,5-di-tert-butyl-4-hydroxyhydrocinnamate)] methane (product name: ANOX20)) are combined, and except for this, the same operation as above (manufacturing method 1-1 of the molded body) is carried out to obtain a secondary battery separator.

[0530] (Method 2-2 for producing molded article) Method for producing a secondary battery separator at a general polymer concentration

[0531] When the total amount of ultra-high molecular weight polyethylene powder and liquid paraffin is set to 100 parts by mass, 35 parts by mass of ultra-high molecular weight polyethylene powder and 65 parts by mass of liquid paraffin (manufactured by MORESCO Co., Ltd., liquid paraffin (product name: SMOIL P-350P)) and 1 part by mass of an antioxidant (manufactured by Dahu Chemical Japan Co., Ltd., tetrakis [methylene (3,5-di-tert-butyl-4-hydroxyhydrocinnamate)] methane (product name: ANOX20)) are combined, and then the slurry liquid is put into liquid paraffin (manufactured by MORESCO Co., Ltd., liquid paraffin (product name: SMOIL P-350P)) at 180°C and stirred for 2 minutes to prepare a gel having a polymer concentration of 25 parts by mass. Except for this, the same operation as above (manufacturing method 1-2 of the molded body) is performed to obtain a secondary battery separator.

[0532] (Evaluation method 1) Number of defects in secondary battery separator

[0533] The secondary battery separator is produced by the method described in (Method 1-1 for producing a molded body), (Method 1-2 for producing a molded body), (Method 2-1 for producing a molded body) or (Method 2-2 for producing a molded body), and the microporous membrane 1 m is obtained by visual inspection or using a magnifying glass as needed. 2 The defects of 50 μm or more in (16 microporous membranes of 25 cm square) are counted. The "defects" mentioned here refer to the parts that are darker than the normal parts when the microporous membrane is observed by transmitted light (poor dispersion). Fibers and colored foreign matter are not counted as defects. Based on the number of defects obtained, the number of defects, which is one of the indicators of the quality of the microporous membrane, is evaluated according to the following evaluation criteria. The evaluation results are shown in Table 1.

[0534] (Evaluation Criteria)

[0535] ◎: Less than 15 pieces / m 2

[0536] ○: 15 or more / m 2 And less than 45 pieces / m 2

[0537] △: greater than or equal to 45 pieces / m 2 And less than 90 pieces / m 2

[0538] ×: 90 pieces / m 2 above

[0539] (Evaluation method 2) Thickness variation of secondary battery separator

[0540] The microporous membrane as a secondary battery separator is manufactured by the method described in the above (method 1-1 for preparing a molded body), (method 1-2 for preparing a molded body), (method 2-1 for preparing a molded body) or (method 2-2 for preparing a molded body), and the thickness of the obtained microporous membrane is measured using a film thickness meter based on JIS K7130. For the measurement site, a 25 cm square microporous membrane is cut into 25 5 cm square microporous membranes, the center of each is measured, and the average film thickness is calculated. Based on the average film thickness, the thickness unevenness (hereinafter also referred to as film thickness unevenness), which is one of the indicators of the quality of the microporous membrane, is evaluated based on the following evaluation criteria. The evaluation results are shown in Table 1.

[0541] (Evaluation Criteria)

[0542] ◎: The average film thickness has a deviation of less than ±1.5 μm.

[0543] ○: The film thickness has a deviation of ±1.5 μm or more and less than ±2.0 μm with respect to the average film thickness.

[0544] △: There is a deviation of ±2.0 μm or more and less than ±4.0 μm with respect to the average film thickness.

[0545] ×: There is a deviation of ±4.0 μm or more with respect to the average film thickness.

[0546] (Evaluation method 3) Puncture strength of secondary battery separator converted by unit area weight (gf / (g / m 2 ))

[0547] Using a manual compression tester "KES-G5" manufactured by Kato Tech Co., Ltd., the microporous membrane as a secondary battery separator described in the above (Method 1-1 for preparing a molded body), (Method 1-2 for preparing a molded body), (Method 2-1 for preparing a molded body) or (Method 2-2 for preparing a molded body) is fixed using a sample holder with an opening having a diameter of 10 mm. Next, a puncture test is performed on the central part of the fixed microporous membrane under the conditions of a needle tip curvature radius of 0.5 mm and a puncture speed of 10 mm / min, thereby obtaining the puncture strength (gf) as the maximum puncture load. The puncture strength converted to unit area weight (gf / (g / m 2 )). It should be noted that this operation was performed 8 times using 8 microporous membranes, and the average value of the 8 times was used as the puncture strength converted by unit area weight (gf / (g / m 2 The evaluation results are shown in Table 1.

[0548] (Evaluation Criteria)

[0549] ☆: The puncture strength calculated by unit area weight is 95gf / (g / m 2 )above.

[0550] ◎: Puncture strength calculated by unit area weight is greater than or equal to 80gf / (g / m 2 ) and less than 95gf / (g / m 2 ).

[0551] ○: Puncture strength calculated by unit area weight is greater than or equal to 70gf / (g / m 2 ) and less than 80gf / (g / m 2 ).

[0552] △: Puncture strength calculated by unit area weight is greater than or equal to 60gf / (g / m 2 ) and less than 70gf / (g / m 2 ).

[0553] ×: The puncture strength calculated by unit area weight is less than 60gf / (g / m 2 ).

[0554] (Evaluation method 4) Thermal shrinkage of secondary battery separator

[0555] When manufacturing the microporous membrane for secondary battery separator described in the above (Preparation method 1-1 of molded body), (Preparation method 1-2 of molded body), (Preparation method 2-1 of molded body) or (Preparation method 2-2 of molded body), the heat setting conditions are 130°C / 1 minute, 132°C / 1 minute, 134°C / 1 minute, and 136°C / 1 minute, and the porosity of the obtained heat-set membrane is calculated. For the porosity, a 10 cm×10 cm square sample is cut out from the microporous membrane, and its volume (cm 3 ) and mass (g), according to the volume (cm 3 ) and mass (g) and density of polyethylene (g / cm 3 ), and the porosity was calculated using the following formula.

[0556] Porosity (%) = (volume - mass / density) / volume × 100

[0557] In addition, the obtained heat-set film is sandwiched between papers one by one, and the paper bundle is placed in an envelope and heated at 120°C for 1 hour. Then, it is cooled at room temperature for 15 minutes. The length of each side of the film is measured with a square, and the average value is calculated. The shrinkage rate is calculated from the original length (10 cm), and the thermal shrinkage rate is calculated from this. Here, a graph of porosity and thermal shrinkage rate is made, and the thermal shrinkage rate when the porosity is 50% is estimated from the graph. Based on the obtained thermal shrinkage rate, the quality of the film properties is evaluated according to the following benchmarks. The evaluation results are shown in Table 1.

[0558] (Evaluation Criteria)

[0559] ☆: Less than 10%

[0560] ◎: greater than or equal to 10% and less than 20%

[0561] ○: greater than or equal to 20% and less than 25%

[0562] △: greater than or equal to 25% and less than 30%

[0563] ×:More than 30%

[0564] (Method 3-1 for producing molded article) Method for producing high-strength fiber with general kneading time

[0565] A high-strength fiber was produced as follows using ultra-high molecular weight polyethylene powder. When the total amount of ultra-high molecular weight polyethylene powder and liquid paraffin was 100 parts by mass, 15 parts by mass of ultra-high molecular weight polyethylene powder and 85 parts by mass of liquid paraffin (manufactured by MORESCO Co., Ltd., liquid paraffin (product name: SMOIL P-350P)) and 1 part by mass of an antioxidant (manufactured by Oko Chemical Co., Ltd., tetrakis[methylene(3,5-di-tert-butyl-4-hydroxyhydrocinnamate)]methane (product name: ANOX20)) were mixed and heated to 100 parts by mass. m2 ) was stirred at a temperature of 35° C. for 60 minutes, thereby preparing a slurry-like liquid.

[0566] Next, the slurry-like liquid was added to liquid paraffin (manufactured by MORESCO Co., Ltd., liquid paraffin (product name: SMOIL P-350P)) at 160° C. and stirred for 2 minutes, thereby preparing a gel having a polymer concentration of 5 parts by mass. The obtained gel was put into Labo Plastomill (main body model: 4C150-01) manufactured by Toyo Seiki Co., Ltd. and kneaded at a constant temperature of 150° C. for 180 minutes and a screw speed of 10 rpm to prepare a kneaded gel.

[0567] Next, the spinning operation was carried out using a Capilograph 1D (main model: PMD-C) manufactured by Toyo Seiki Co., Ltd. Using an orifice with an aperture of 1.0 mm, a length of 66 mm, and an inflow angle of 90°, the kneaded gel was put into a furnace set at 180°C, and then degassed for 60 minutes. Then, the extrusion speed was set to 7.5 mm / min so that the discharge amount was 0.35 g / min, and the raw yarn was recovered at a winding speed of 2.8 m / min through a water bath immediately below the front end of the orifice. It should be noted that the distance from the front end of the orifice to the water bath surface is 8 cm, and the temperature of the water bath is set to 20°C.

[0568] Then, in order to remove the liquid paraffin from the wound raw yarn, the raw yarn was immersed in hexane for extraction, and then dried for 24 hours.

[0569] The raw yarn thus obtained was stretched once at a speed of 20 mm / min in a thermostatic bath at 120°C, and then stretched twice at a speed of 10 mm / min in a thermostatic bath at 140°C until the yarn was about to break, thereby obtaining a high-strength fiber (stretched yarn). It should be noted that the temperature in the thermostatic bath is a value obtained by actually measuring the temperature of the center of the thermostatic bath using a thermometer.

[0570] (Method 3-2 for producing molded article) Method for producing high-strength fiber with general kneading time

[0571] A high-strength fiber was produced as follows using ultra-high molecular weight polyethylene powder. When the total amount of ultra-high molecular weight polyethylene powder and liquid paraffin was 100 parts by mass, 15 parts by mass of ultra-high molecular weight polyethylene powder and 85 parts by mass of liquid paraffin (manufactured by MORESCO Co., Ltd., liquid paraffin (product name: SMOIL P-350P)) and 1 part by mass of an antioxidant (manufactured by Oko Chemical Co., Ltd., tetrakis[methylene(3,5-di-tert-butyl-4-hydroxyhydrocinnamate)]methane (product name: ANOX20)) were mixed and heated to 100 parts by mass. m2 ) was stirred at a temperature of 35° C. for 60 minutes, thereby preparing a slurry-like liquid.

[0572] Next, the slurry-like liquid was added to liquid paraffin (manufactured by MORESCO Co., Ltd., liquid paraffin (product name: SMOIL P-350P)) at 180° C. and stirred for 2 minutes to prepare a gel having a polymer concentration of 5 parts by mass. The obtained gel was added to Labo Plastomill (main body model: 4C150-01) manufactured by Toyo Seiki Co., Ltd. and kneaded at a constant temperature of 150° C. for 180 minutes and a screw speed of 10 rpm to prepare a kneaded gel.

[0573] Next, the spinning operation was carried out using a Capilograph 1D (main model: PMD-C) manufactured by Toyo Seiki Co., Ltd. Using an orifice with an aperture of 1.0 mm, a length of 66 mm, and an inflow angle of 90°, the mixed gel was put into a furnace set at 180°C, and then degassed for 60 minutes. Then, the extrusion speed was set to 10 mm / min so that the discharge amount was 0.45 g / min, and the raw yarn was recovered at a winding speed of 0.8 m / min through a water bath immediately below the front end of the orifice. It should be noted that the distance from the front end of the orifice to the water bath surface is 8 cm, and the temperature of the water bath is set to 20°C.

[0574] Then, in order to remove the liquid paraffin from the wound raw yarn, the raw yarn was immersed in hexane for extraction, and then dried for 24 hours.

[0575] The raw yarn thus obtained was stretched once in a thermostatic bath at 120°C at a delivery speed of 100 mm / min and a winding speed of 3000 mm / min, and then stretched twice in a thermostatic bath at 140°C at a delivery speed of 100 mm / min and a winding speed just before the yarn breaks, thereby obtaining a high-strength fiber (stretched yarn). It should be noted that the stretching process was carried out using a heating stretching device (main body model: IMC-3F08) manufactured by Imoto Manufacturing Co., Ltd. In addition, the temperature in the thermostatic bath is a value obtained by actually measuring the temperature of the center of the thermostatic bath using a thermometer.

[0576] (Method 4-1 for producing molded article) Method for producing high-strength fiber with short kneading time

[0577] High-strength fibers were obtained in the same manner as in the above (Production Method 3-1 of Molded Article) except that the kneading time in Labo Plastomill (main body model: 4C150-01) manufactured by Toyo Seiki Co., Ltd. was set to 60 minutes.

[0578] (Method 4-2 for producing molded article) Method for producing high-strength fiber with short kneading time

[0579] High-strength fibers were obtained in the same manner as in the above (Production Method 3-2 of Molded Article) except that the kneading time in Labo Plastomill (main body model: 4C150-01) manufactured by Toyo Seiki Co., Ltd. was set to 0 minutes (kneading in Labo Plastomill was not performed).

[0580] (Evaluation method 5) Number of high-strength fiber balls

[0581] It was confirmed that several balls were produced in 10 m of high-strength fiber (drawn yarn) spun by the method described in (Method 3-1 for preparing molded body), (Method 3-2 for preparing molded body), (Method 4-1 for preparing molded body) or (Method 4-2 for preparing molded body), and the number of balls was calculated. Here, the so-called "ball" refers to a part that is locally thicker than a normal part (poor dispersion). The quality of the high-strength fiber was evaluated as follows based on the calculated number of balls. The evaluation results are shown in Table 1.

[0582] (Evaluation Criteria)

[0583] ◎: The number of balls is less than 3 / m

[0584] ○: The number of silk balls is greater than or equal to 3 and less than 6 / m

[0585] △: The number of balls is greater than or equal to 6 and less than 10 / m

[0586] ×: The number of yarn balls is 10 or more per meter

[0587] (Evaluation method 6) Uneven diameter of high-strength fibers

[0588] The yarn diameter of 10 m of high-strength fiber (drawn yarn) obtained by spinning by the method described in the above (Method 3-1 for preparing molded body), (Method 3-2 for preparing molded body), (Method 4-1 for preparing molded body) or (Method 4-2 for preparing molded body) was measured at 0.5 m intervals using an optical microscope, and the average yarn diameter was calculated. Based on the average yarn diameter, the yarn diameter unevenness, which is one of the qualities of the high-strength fiber, was evaluated based on the following evaluation criteria. The evaluation results are shown in Table 1.

[0589] (Evaluation Criteria)

[0590] ◎: The average wire diameter has a deviation of less than ±3 μm.

[0591] ○: The average wire diameter has a deviation of ±3 μm or more and less than ±5 μm.

[0592] △: There is a deviation of ±5 μm or more and less than ±10 μm with respect to the average wire diameter.

[0593] ×: There is a deviation of ±10 μm or more with respect to the average wire diameter.

[0594] (Evaluation method 7) Tensile breaking strength of high-strength fiber

[0595] 10 m of high-strength fiber (drawn fiber) obtained by spinning by the method described in (Method 3-1 for preparing molded article), (Method 3-2 for preparing molded article), (Method 4-1 for preparing molded article) or (Method 4-2 for preparing molded article) is cut at intervals of 1 m, and the obtained 10 fibers are stretched at room temperature until they break, and the average breaking strength is calculated. At this time, the breaking strength is calculated by dividing the maximum load value applied to the yarn by the fineness. Here, the fineness refers to the number of fibers per 1×10 4 The weight (g) of m yarn is calculated from the weight of 10 m high-strength fiber. The unit of fineness is expressed in dtex. It should be noted that a scale capable of measuring 0.1 mg units is used in the measurement of weight. The evaluation results are shown in Table 1. The tensile breaking strength of the high-strength fiber is evaluated according to the following criteria.

[0596] (Evaluation Criteria)

[0597] ☆: Breaking strength is 43cN / dtex or more

[0598] ◎: Breaking strength greater than or equal to 30 cN / dtex and less than 43 cN / dtex

[0599] ○: Breaking strength is greater than or equal to 25 cN / dtex and less than 30 cN / dtex

[0600] △: Breaking strength is greater than or equal to 20 cN / dtex and less than 25 cN / dtex

[0601] ×: Breaking strength less than 20 cN / dtex

[0602] (Evaluation method 8) Evaluation of high-speed winding properties of high-strength fibers

[0603] The gel obtained by kneading the gel by the method described in the above (Method 3-1 for preparing a molded body), (Method 3-2 for preparing a molded body), (Method 4-1 for preparing a molded body) or (Method 4-2 for preparing a molded body) was spun using a Capilograph 1D (main body model: PMD-C) manufactured by Toyo Seiki Co., Ltd. An orifice with an orifice diameter of 0.5 mm, a length of 5 mm and an inflow angle of 90° was used. The spinning conditions were fixed at a temperature of 200°C and an extrusion speed of 20 mm / min, and the winding speed was increased from 3 m / min to 19.7 m / min. 2 The speed at which the wire breaks when the speed is slowly increased was measured as the high-speed winding speed, and the evaluation was performed based on the average value of 5 times according to the following evaluation criteria.

[0604] (Evaluation Criteria)

[0605] ☆: High-speed winding speed is 900m / min or more.

[0606] ◎: High-speed winding speed is 700 m / min or more and less than 900 m / min.

[0607] ○: High-speed winding speed is 400 m / min or more and less than 700 m / min.

[0608] △: High-speed winding speed is 200 m / min or more and less than 400 m / min.

[0609] ×: High-speed winding speed is less than 200 m / min.

[0610] (Measurement 8) Melting point of ultra-high molecular weight polyethylene powder (T m2 )

[0611] The melting points (T) of the ultra-high molecular weight polyethylene powders obtained in the examples and comparative examples were measured using a differential scanning calorimeter (DSC) DSC8000 manufactured by Perkin Elmer as follows. m2 ).

[0612] 8.3 mg to 8.5 mg of ultra-high molecular weight polyethylene powder was weighed and placed in an aluminum sample pan. An aluminum cover was installed on the pan and set in a differential scanning calorimeter. While purging nitrogen at a flow rate of 20 mL / min, the measurement was carried out under the following conditions. Pure indium was used for temperature calibration.

[0613] 1) Maintain at 50°C for 1 minute, then increase the temperature to 180°C at a rate of 10°C / min.

[0614] 2) Maintain at 180°C for 5 minutes, then cool to 50°C at a rate of 10°C / min.

[0615] 3) Maintain at 50°C for 5 minutes, then increase the temperature to 180°C at a rate of 10°C / min.

[0616] The peak temperature of the melting curve obtained in the heating process of 3) above is taken as the melting peak temperature (T m2 ).

[0617] [Catalyst synthesis method]

[0618] [Catalyst Preparation Example 1]

[0619] (Preparation of supported metallocene catalyst component [A])

[0620] (1) Synthesis of raw material [a-1]

[0621] In a nitrogen atmosphere, at 500°C, the average particle size was 8 μm and the specific surface area was 400 m 2 / g, and the particle internal pore volume of 0.8ml / g of spherical silica was calcined for 5 hours to dehydrate. The number of silanol groups was 1.4mmol / g.

[0622] 40 g of the dehydrated silica was dispersed in 800 mL of hexane in a 1.8 L autoclave under a nitrogen atmosphere to obtain a slurry.

[0623] While the obtained slurry was maintained at 20° C. under stirring, 100 mL of a hexane solution of triethylaluminum (concentration: 1 mol / L) was added dropwise over 1 hour, and then stirred at the same temperature for 2 hours.

[0624] Then, the obtained reaction mixture was decanted to remove unreacted triethylaluminum in the supernatant. In this way, 800 mL of a hexane slurry of the silica component [a-1] treated with triethylaluminum was obtained.

[0625] (2) Preparation of raw material [a-2]

[0626] 200 mmol of [(N-tert-butylamino)(tetramethyl- 5 -cyclopentadienyl)dimethylsilane]titanium-1,3-pentadiene (hereinafter referred to as "titanium complex") was dissolved in 1250 mL of Isopar E [trade name of hydrocarbon mixture manufactured by Exxon Chemical Company (USA)], 25 mL of a commercially available 1 mol / L hexane solution of butylethylmagnesium was added in advance, and then hexane was added to adjust the titanium complex concentration to 0.1 mol / L, thereby obtaining a titanium complex [a-2].

[0627] (3) Preparation of raw material [a-3]

[0628] 5.7 g of tris(pentafluorophenyl)(4-hydroxyphenyl) boronate bis(hydrogenated tallow alkyl)methylammonium (hereinafter referred to as "boride") was added to 50 mL of toluene and dissolved to obtain a 100 mmol / L toluene solution of the boride. 5 mL of a 1 mol / L hexane solution of ethoxydiethylaluminum was added to the toluene solution of the boride at room temperature, and hexane was further added to adjust the boride concentration in the solution to 70 mmol / L. Then, the mixture was stirred at room temperature for 1 hour to obtain a reaction mixture [a-3] containing the boride.

[0629] (4) Synthesis of supported metallocene catalyst [A]

[0630] While stirring 800 mL of the silica component [a-1] slurry obtained in the above (1) at 20 ° C, 48 mL of the titanium complex [a-2] obtained in the above (2) and 69 mL of the reaction mixture [a-3] containing a boride obtained in the above (3) were added simultaneously for 1 hour, and further stirred for 1 hour at the same temperature to react the titanium complex with the boride. It should be noted that by adjusting the amount of the titanium complex [a-2] and the reaction mixture [a-3] containing a boride, the catalyst activity can be controlled. Specifically, by increasing the amount of the titanium complex [a-2] and the reaction mixture [a-3] containing a boride, there is a tendency for the catalyst activity to become larger. After the reaction is completed, the supernatant is removed and the unreacted catalyst raw material is removed using hexane, thereby obtaining a supported metallocene catalyst [A] (hereinafter also referred to as solid catalyst component [A] or solid catalyst A) having a catalyst active substance formed on the silica.

[0631] (5) Synthesis of raw material (a-4)

[0632] 1 mol / L 6[Mg(C 4 H 9 ) 2 ]・Al(C 2 H 5 ) 3 2000mL of hexane solution (equivalent to 2000 mmol in terms of magnesium and aluminum) was put into an 8L stainless steel autoclave fully purged with nitrogen, and while stirring at 80°C, 240mL of 8.33 mol / L hexane solution of methyl hydrogen polysiloxane (manufactured by Shin-Etsu Chemical Co., Ltd.) was pressure fed, and further stirred at 80°C for 2 hours. After the reaction was completed, the reaction product cooled to room temperature was used as raw material (a-4). The raw material (a-4) had a total concentration of 0.786 mol / L of magnesium and aluminum.

[0633] [Catalyst Preparation Example 2]

[0634] (Preparation of solid catalyst component [B])

[0635] (1) Synthesis of raw material (b-1)

[0636] 2000 mmol of 6[Mg(C 4 H 9 ) 2 ]・Al(C 2 H 5 ) 3The mixture was placed in an 8L stainless steel autoclave after being fully purged with nitrogen, diluted with hexane, and then 800 mmol of a hexane solution of n-butanol was added dropwise over 3 hours while stirring at 50°C. After the reaction, the line was cleaned with 300 mL of hexane. The mixture was further stirred at 50°C for 2 hours. After the reaction was completed, the reaction product was cooled to room temperature and used as raw material [b-1].

[0637] (2) Synthesis of raw material [b-2]

[0638] In an 8 L stainless steel autoclave that had been fully purged with nitrogen, 2000 mL of 1 mol / L 6[Mg(C 4 H 9 ) 2 ]・Al(C 2 H 5 ) 3 While stirring the mixture with a hexane solution of 2000 mmol in terms of magnesium and aluminum, 240 mL of a hexane solution of 8.33 mol / L methyl hydrogen polysiloxane (manufactured by Shin-Etsu Chemical Co., Ltd.) was pressure fed, and the mixture was further stirred at 80° C. for 2 hours. After the reaction was completed, the reaction product was cooled to room temperature and used as raw material [b-2]. The raw material [b-2] had a total concentration of 0.786 mol / L of magnesium and aluminum.

[0639] (3) [B-1] Synthesis of carrier

[0640] 1000 mL of a 1 mol / L hexane solution of trichlorosilane was added to an 8L stainless steel autoclave after sufficient nitrogen substitution, and a hexane solution of an organic magnesium compound of the raw material [b-1] equivalent to 943 mmol of magnesium was added dropwise at 65° C. for 3 hours, and the reaction was continued while stirring at 65° C. for 1 hour. After the reaction was completed, the supernatant was removed and washed 4 times with 1800 mL of hexane to obtain a carrier [B-1]. The carrier was analyzed, and the magnesium contained in 1 g of solid was 7.5 mmol.

[0641] (4) Preparation of solid catalyst component [B]

[0642] To 1970 mL of hexane slurry containing 110 g of the above-mentioned [B-1] carrier, 103 mL of a 1 mol / L hexane solution of titanium tetrachloride and 131 mL of the raw material [b-2] were added simultaneously over 3 hours while stirring at 10° C. After the addition, the reaction was continued at 10° C. for 1 hour. After the reaction was completed, the supernatant was removed and washed 4 times with hexane to remove the unreacted raw material components, thereby preparing a solid catalyst component [B].

[0643] [Catalyst Preparation Example 3]

[0644] (Preparation of solid catalyst component [C])

[0645] (1) Synthesis of raw material (c-1)

[0646] 1 mol / L of 6[Mg(C 4 H 9 ) 2 ]・Al(C 2 H 5 ) 3 2000 mL of a hexane solution (equivalent to 2000 mmol in terms of magnesium and aluminum) was added, and while stirring at 80° C., 240 mL of a hexane solution of 8.33 mol / L methyl hydrogen polysiloxane (manufactured by Shin-Etsu Chemical Co., Ltd.) was pressure fed, and the reaction was continued while stirring at 80° C. for 2 hours. After the reaction was completed, the reaction product cooled to room temperature was used as a raw material (c-1). The raw material (c-1) had a total concentration of 0.786 mol / L of magnesium and aluminum.

[0647] (2) Preparation of solid catalyst component [C]

[0648] 1600mL of hexane was added to an 8L stainless steel autoclave after nitrogen replacement. While stirring at 10°C, 800mL of a 1 mol / L hexane solution of titanium tetrachloride and 800mL of raw material (c-1) were added simultaneously over 5 hours. The reaction was continued at 10°C for 1 hour. After the reaction was completed, the supernatant was removed and washed 4 times with hexane to remove the unreacted raw material components, thereby preparing a solid catalyst component [C] (hereinafter also referred to as solid catalyst C). It should be noted that the catalytic activity of the catalyst can be adjusted by the polymerization pressure during polymerization.

[0649] [Co-catalyst]

[0650] As the promoter, the following promoters 1 to 3 were used.

[0651] Cocatalyst 1: a commercially available mixture of triisobutylaluminum and diisobutylaluminum hydride (a mixture of triisobutylaluminum and diisobutylaluminum hydride in a mass ratio of 9:1)

[0652] Co-catalyst 2: 6[Mg(C 4 H 9 ) 2 ]・Al(C 2 H 5 ) 3

[0653] Co-catalyst 3: the above-synthesized raw material (a-4), raw material (b-2) or raw material (c-1)

[0654] [Example 1]

[0655] The interior of a container-type 1.5L polymerization reactor with a stirring device was adjusted to vacuum, and then 500mL of dehydrated n-hexane was introduced into the polymerization reactor. Next, 0.6mL of the cocatalyst 1 was dispersed in 100mL of dehydrated n-hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor was adjusted to 80°C, and stirring was started at a speed of 1000rpm. Next, hydrogen for adjusting the intrinsic viscosity IV (molecular weight) was introduced so that the pressure in the polymerization reactor was 0.045MPa, and ethylene was further introduced so that the pressure in the polymerization reactor was 0.1MPa. Then, 5.0mg of the solid catalyst component [C] was dispersed in 200mL of dehydrated n-hexane and introduced into the polymerization reactor, and a 1.0 hour intermittent polymerization reaction was carried out. In the polymerization reaction, the pressure in the polymerization reactor was maintained by appropriately adding ethylene into the polymerization reactor. Then, the polymerization reactor was opened, and the contents were filtered under reduced pressure, thereby separating and recovering the powdered solid component. The obtained solid component was placed in a stainless steel beaker with a mouth diameter of 68 mm, and dried while stirring at 70°C at a stirring speed of 50 rpm for 2 hours, thereby obtaining an ultra-high molecular weight polyethylene powder. Next, the ultra-high molecular weight polyethylene powder was immersed in liquid paraffin adjusted to 50°C under vacuum for 3 hours, then immersed in hexane for 10 hours to extract the liquid paraffin, and dried at 25°C for 24 hours. The catalyst activity (the amount of polyethylene obtained per unit catalyst weight) of the ultra-high molecular weight polyethylene powder is 18000 (g-PE / g-catalyst). The scales and extreme coarse powders were removed using a sieve with a mesh size of 425 μm, 600 ppm of calcium stearate was added, and then the physical properties of the ultra-high molecular weight polyethylene powder were evaluated. The evaluation results of the ultra-high molecular weight polyethylene powder are shown in Table 1.

[0656] The obtained ultra-high molecular weight polyethylene powder was used to prepare a microporous membrane for a secondary battery separator by the methods described in the above (Method 1-1 for preparing a molded body), (Method 1-2 for preparing a molded body), (Method 2-1 for preparing a molded body) and (Method 2-2 for preparing a molded body), and was evaluated by the above-mentioned evaluation methods 1 to 4. The evaluation results of the obtained microporous membrane are shown in Table 1.

[0657] [Example 2]

[0658] The interior of a container-type 1.5L polymerization reactor with a stirring device is adjusted to vacuum, and then 500mL of dehydrated n-hexane is introduced into the polymerization reactor. Next, 5.0mL of cocatalyst 1 is dispersed in 100mL of dehydrated n-hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor is adjusted to 20°C, and stirring is started at a speed of 1000rpm. Then, ethylene is adjusted to 15NL using a flow meter, 750.0mg of solid catalyst component [C] is dispersed in 200mL of dehydrated n-hexane and introduced into the polymerization reactor, and a 1.0 hour intermittent prepolymerization reaction is carried out. After the reaction is completed, the obtained prepolymerization catalyst (hereinafter, also referred to as prepolymerization catalyst 2) is taken out and collected in a nitrogen glove box.

[0659] Next, main polymerization was carried out using the collected prepolymerized catalyst 2.

[0660] The inside of a container-type 1.5L polymerization reactor with a stirring device is adjusted to vacuum, and then 500mL of dehydrated n-hexane is introduced into the polymerization reactor. Then, 0.6mL of cocatalyst 1 is dispersed in 100mL of dehydrated n-hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor is adjusted to 80°C, and stirring is started at a speed of 1000rpm. Then, hydrogen for adjusting the intrinsic viscosity IV (molecular weight) is introduced so that the pressure in the polymerization reactor is 0.045MPa, and ethylene is further introduced so that the pressure in the polymerization reactor is 0.8MPa. Then, 40.0mg of prepolymerization catalyst 2 is dispersed in 200mL of dehydrated n-hexane and introduced into the polymerization reactor, and a 1.0 hour intermittent polymerization reaction is carried out. In the polymerization reaction, the pressure in the polymerization reactor is maintained by appropriately adding ethylene into the polymerization reactor. Then, the polymerization reactor is opened, and the contents are filtered under reduced pressure, thereby separating and recovering the solid component in powder form. The obtained solid component was placed in a stainless steel beaker with a mouth diameter of 68 mm, and dried while stirring at 70° C. at a stirring speed of 50 rpm for 2 hours, thereby obtaining an ultra-high molecular weight polyethylene powder. Next, the ultra-high molecular weight polyethylene powder was immersed in liquid paraffin adjusted to 50° C. under vacuum for 3 hours, then immersed in hexane for 10 hours to extract the liquid paraffin, and dried at 25° C. for 24 hours.

[0661] The catalyst activity of the ultra-high molecular weight polyethylene powder (the amount of polyethylene obtained per unit catalyst weight) was 24000 (g-PE / g-catalyst). Scaly matter and extreme coarse powder were removed using a sieve with a mesh size of 425 μm, and 600 ppm of calcium stearate was added, and then the physical properties of the ultra-high molecular weight polyethylene powder were evaluated. The evaluation results of the ultra-high molecular weight polyethylene powder are shown in Table 1.

[0662] The obtained ultra-high molecular weight polyethylene powder was used to prepare a microporous membrane for a secondary battery separator by the methods described in the above (Method 1-1 for preparing a molded body), (Method 1-2 for preparing a molded body), (Method 2-1 for preparing a molded body) and (Method 2-2 for preparing a molded body), and was evaluated by the above-mentioned evaluation methods 1 to 4. The evaluation results of the obtained microporous membrane are shown in Table 1.

[0663] [Example 3]

[0664] The interior of a container-type 1.5L polymerization reactor with a stirring device is adjusted to vacuum, and then 500mL of dehydrated n-hexane is introduced into the polymerization reactor. Next, 5.0mL of cocatalyst 1 is dispersed in 100mL of dehydrated n-hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor is adjusted to 20°C, and stirring is started at a speed of 1000rpm. Then, ethylene is adjusted to 15NL using a flow meter, 750.0mg of solid catalyst component [C] is dispersed in 200mL of dehydrated n-hexane and introduced into the polymerization reactor, and a 1.0 hour intermittent prepolymerization reaction is carried out. After the reaction is completed, the obtained prepolymerization catalyst (hereinafter, also referred to as prepolymerization catalyst 3) is taken out and collected in a nitrogen glove box.

[0665] Next, main polymerization was carried out using the collected prepolymerized catalyst 3 .

[0666] The interior of a container-type 1.5L polymerization reactor with a stirring device is adjusted to vacuum, and then 500mL of dehydrated n-hexane is introduced into the polymerization reactor. Then, 0.6mL of cocatalyst 1 is dispersed in 100mL of dehydrated n-hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor is adjusted to 80°C, and stirring is started at a speed of 1000rpm. Then, hydrogen for adjusting the intrinsic viscosity IV (molecular weight) is introduced so that the pressure in the polymerization reactor is 0.016MPa, and ethylene is further introduced so that the pressure in the polymerization reactor is 0.8MPa. Then, 40.0mg of prepolymerization catalyst 3 is dispersed in 200mL of dehydrated n-hexane and introduced into the polymerization reactor, and a 1.0 hour intermittent polymerization reaction is carried out. In the polymerization reaction, the pressure in the polymerization reactor is maintained by appropriately adding ethylene into the polymerization reactor. Then, the polymerization reactor is opened, and the contents are filtered under reduced pressure, thereby separating and recovering the powdery solid component. The obtained solid component was placed in a stainless steel beaker with a mouth diameter of 68 mm, and dried while stirring at 70° C. at a stirring speed of 50 rpm for 2 hours, thereby obtaining an ultra-high molecular weight polyethylene powder. Next, the ultra-high molecular weight polyethylene powder was immersed in liquid paraffin adjusted to 50° C. under vacuum for 3 hours, then immersed in hexane for 10 hours to extract the liquid paraffin, and dried at 25° C. for 24 hours.

[0667] The catalyst activity of the ultra-high molecular weight polyethylene powder (the amount of polyethylene obtained per unit catalyst weight) was 26500 (g-PE / g-catalyst). The scales and extreme coarse powder were removed using a sieve with a mesh size of 425 μm, and 600 ppm of calcium stearate was added, and then the physical properties of the ultra-high molecular weight polyethylene powder were evaluated. The evaluation results of the ultra-high molecular weight polyethylene powder are shown in Table 1.

[0668] The obtained ultra-high molecular weight polyethylene powder was used to prepare a microporous membrane for a secondary battery separator by the methods described in the above (Method 1-1 for preparing a molded body), (Method 1-2 for preparing a molded body), (Method 2-1 for preparing a molded body) and (Method 2-2 for preparing a molded body), and was evaluated by the above-mentioned evaluation methods 1 to 4. The evaluation results of the obtained microporous membrane are shown in Table 1.

[0669] [Example 4]

[0670] The interior of a container-type 1.5L polymerization reactor with a stirring device is adjusted to vacuum, and then 500mL of dehydrated n-hexane is introduced into the polymerization reactor. Next, 5.0mL of cocatalyst 1 is dispersed in 100mL of dehydrated n-hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor is adjusted to 15°C, and stirring is started at a speed of 1000rpm. Then, ethylene is adjusted to 15NL using a flow meter, 750.0mg of solid catalyst component [C] is dispersed in 200mL of dehydrated n-hexane and introduced into the polymerization reactor, and a 1.0 hour intermittent prepolymerization reaction is carried out. After the reaction is completed, the obtained prepolymerization catalyst (hereinafter, also referred to as prepolymerization catalyst 4) is taken out and collected in a nitrogen glove box.

[0671] Next, main polymerization was carried out using the collected prepolymerized catalyst 4 .

[0672] The inside of the container type 1.5L polymerization reactor with a stirring device is adjusted to vacuum, and then 500mL of dehydrated n-hexane is introduced into the polymerization reactor. Then, 0.6mL of cocatalyst 1 is dispersed in 100mL of dehydrated n-hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor is adjusted to 80°C, and stirring is started with a rotation speed of 1000rpm. Then, hydrogen for adjusting the intrinsic viscosity IV (molecular weight) is introduced so that the pressure in the polymerization reactor is 0.0036MPa, and ethylene is further introduced so that the pressure in the polymerization reactor is 0.8MPa. Then, 40.0mg of prepolymerization catalyst 4 is dispersed in 200mL of dehydrated n-hexane and introduced into the polymerization reactor, and a 1.0 hour intermittent polymerization reaction is carried out. In the polymerization reaction, the pressure in the polymerization reactor is maintained by appropriately adding ethylene into the polymerization reactor. Then, the polymerization reactor is opened, and the contents are filtered under reduced pressure, thereby separating and recovering the solid component in powder form. The obtained solid component was placed in a stainless steel beaker with a mouth diameter of 68 mm, and dried while stirring at 70° C. at a stirring speed of 50 rpm for 2 hours, thereby obtaining an ultra-high molecular weight polyethylene powder. Next, the ultra-high molecular weight polyethylene powder was immersed in liquid paraffin adjusted to 60° C. under vacuum for 4 hours, then immersed in hexane for 15 hours to extract the liquid paraffin, and dried at 25° C. for 24 hours.

[0673] The catalyst activity of the ultra-high molecular weight polyethylene powder (the amount of polyethylene obtained per unit catalyst weight) was 26000 (g-PE / g-catalyst). Scaly matter and extreme coarse powder were removed using a sieve with a mesh size of 425 μm, and 600 ppm of calcium stearate was added, and then the physical properties of the ultra-high molecular weight polyethylene powder were evaluated. The evaluation results of the ultra-high molecular weight polyethylene powder are shown in Table 1.

[0674] The obtained ultra-high molecular weight polyethylene powder was used to prepare a microporous membrane for a secondary battery separator by the methods described in the above (Method 1-1 for preparing a molded body), (Method 1-2 for preparing a molded body), (Method 2-1 for preparing a molded body) and (Method 2-2 for preparing a molded body), and was evaluated by the above-mentioned evaluation methods 1 to 4. The evaluation results of the obtained microporous membrane are shown in Table 1.

[0675] [Example 5]

[0676] The interior of a container-type 1.5L polymerization reactor with a stirring device is adjusted to a vacuum, and then 500mL of a mixed solvent obtained by fully mixing 45% by mass of dehydrated n-hexane and 55% by mass of liquid paraffin in advance is introduced into the polymerization reactor. Next, 5.0mL of co-catalyst 1 is dispersed in 100mL of dehydrated n-hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor is adjusted to 15°C, and stirring is started at a speed of 1000rpm. Then, ethylene is adjusted to 15NL using a flow meter, 750.0mg of solid catalyst component [C] is dispersed in 200mL of dehydrated n-hexane and introduced into the polymerization reactor, and a 1.0 hour intermittent prepolymerization reaction is carried out. After the reaction is completed, the obtained prepolymerization catalyst (hereinafter, also referred to as prepolymerization catalyst 5) is taken out and collected in a nitrogen glove box.

[0677] Next, main polymerization was carried out using the collected prepolymerized catalyst 5 .

[0678] The inside of the container type 1.5L polymerization reactor with a stirring device is adjusted to vacuum, and then 500mL of dehydrated n-hexane is introduced into the polymerization reactor. Then, 0.6mL of cocatalyst 1 is dispersed in 100mL of dehydrated n-hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor is adjusted to 80°C, and stirring is started with a rotation speed of 1000rpm. Then, hydrogen for adjusting the intrinsic viscosity IV (molecular weight) is introduced so that the pressure in the polymerization reactor is 0.0036MPa, and ethylene is further introduced so that the pressure in the polymerization reactor is 0.8MPa. Then, 40.0mg of prepolymerization catalyst 5 is dispersed in 200mL of dehydrated n-hexane and introduced into the polymerization reactor, and a 1.0 hour intermittent polymerization reaction is carried out. In the polymerization reaction, the pressure in the polymerization reactor is maintained by appropriately adding ethylene into the polymerization reactor. Then, the polymerization reactor is opened, and the contents are filtered under reduced pressure, thereby separating and recovering the solid component in powder form. The obtained solid content was placed in a stainless steel beaker having a mouth diameter of 68 mm, and dried while stirring at 70° C. at a stirring speed of 50 rpm for 2 hours, thereby obtaining an ultrahigh molecular weight polyethylene powder.

[0679] The catalyst activity of the ultra-high molecular weight polyethylene powder (the amount of polyethylene obtained per unit catalyst weight) was 24200 (g-PE / g-catalyst). The scales and extreme coarse powder were removed using a sieve with a mesh size of 425 μm, and 600 ppm of calcium stearate was added, and then the physical properties of the ultra-high molecular weight polyethylene powder were evaluated. The evaluation results of the ultra-high molecular weight polyethylene powder are shown in Table 1.

[0680] The obtained ultra-high molecular weight polyethylene powder was used to prepare a microporous membrane for a secondary battery separator by the methods described in the above (Method 1-1 for preparing a molded body), (Method 1-2 for preparing a molded body), (Method 2-1 for preparing a molded body) and (Method 2-2 for preparing a molded body), and the microporous membrane was evaluated by the above-mentioned evaluation methods 1 to 4. The evaluation results of the obtained microporous membrane are shown in Table 1.

[0681] [Example 6]

[0682] The interior of a container-type 1.5L polymerization reactor with a stirring device is adjusted to vacuum, and then 500mL of dehydrated n-hexane is introduced into the polymerization reactor. Next, 5.0mL of cocatalyst 2 is dispersed in 100mL of dehydrated n-hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor is adjusted to 10°C, and stirring is started at a speed of 1000rpm. Then, ethylene is adjusted to 10NL using a flow meter, 750.0mg of solid catalyst component [B] is dispersed in 200mL of dehydrated n-hexane and introduced into the polymerization reactor, and a 1.0 hour intermittent prepolymerization reaction is carried out. After the reaction is completed, the obtained prepolymerization catalyst (hereinafter, also referred to as prepolymerization catalyst 6) is taken out and collected in a nitrogen glove box.

[0683] Next, main polymerization was carried out using the collected prepolymerized catalyst 6 .

[0684] The inside of the container type 1.5L polymerization reactor with a stirring device is adjusted to vacuum, and then 500mL of dehydrated n-hexane is introduced into the polymerization reactor. Then, 0.6mL of cocatalyst 2 is dispersed in 100mL of dehydrated n-hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor is adjusted to 78°C, and stirring is started with a rotation speed of 1000rpm. Then, hydrogen for adjusting the intrinsic viscosity IV (molecular weight) is introduced so that the pressure in the polymerization reactor is 0.00035MPa, and ethylene is further introduced so that the pressure in the polymerization reactor is 0.8MPa. Then, 40.0mg of prepolymerization catalyst 6 is dispersed in 200mL of dehydrated n-hexane and introduced into the polymerization reactor, and a 1.0 hour intermittent polymerization reaction is carried out. In the polymerization reaction, the pressure in the polymerization reactor is maintained by appropriately adding ethylene into the polymerization reactor. Then, the polymerization reactor is opened, and the contents are filtered under reduced pressure, thereby separating and recovering the solid component in powder form. The obtained solid component was placed in a stainless steel beaker with a mouth diameter of 68 mm, and dried while stirring at 70° C. at a stirring speed of 50 rpm for 2 hours, thereby obtaining an ultra-high molecular weight polyethylene powder. Next, the ultra-high molecular weight polyethylene powder was immersed in liquid paraffin adjusted to 60° C. under vacuum for 4 hours, then immersed in hexane for 15 hours to extract the liquid paraffin, and dried at 25° C. for 24 hours.

[0685] The catalytic activity of the ultra-high molecular weight polyethylene powder (the amount of polyethylene obtained per unit catalyst weight) was 21350 (g-PE / g-catalyst). The scaly matter and the extremely coarse powder were removed using a sieve with a mesh size of 425 μm, and the physical properties of the ultra-high molecular weight polyethylene powder were evaluated. The evaluation results of the ultra-high molecular weight polyethylene powder are shown in Table 1.

[0686] Using the obtained ultrahigh molecular weight polyethylene powder, high strength fibers were produced by the methods described in the above (Method 3-1 for producing a molded article), (Method 3-2 for producing a molded article), (Method 4-1 for producing a molded article), and (Method 4-2 for producing a molded article), and were evaluated by the above-mentioned evaluation methods 5 to 8. The evaluation results of the obtained high strength fibers are shown in Table 1.

[0687] [Example 7]

[0688] The interior of a container-type 1.5L polymerization reactor with a stirring device is adjusted to a vacuum, and then 500mL of a mixed solvent obtained by fully mixing 35% by mass of dehydrated n-hexane and 65% by mass of liquid paraffin in advance is introduced into the polymerization reactor. Next, 5.0mL of co-catalyst 2 is dispersed in 100mL of dehydrated n-hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor is adjusted to 10°C, and stirring is started at a speed of 1000rpm. Then, ethylene is adjusted to 10NL using a flow meter, 750.0mg of solid catalyst component [B] is dispersed in 200mL of dehydrated n-hexane and introduced into the polymerization reactor, and a 1.0 hour intermittent prepolymerization reaction is carried out. After the reaction is completed, the obtained prepolymerization catalyst (hereinafter, also referred to as prepolymerization catalyst 7) ​​is taken out and collected in a nitrogen glove box.

[0689] Next, main polymerization was carried out using the collected prepolymerized catalyst 7 .

[0690] The inside of the container type 1.5L polymerization reactor with a stirring device is adjusted to vacuum, and then 500mL of dehydrated n-hexane is introduced into the polymerization reactor. Then, 0.6mL of cocatalyst 2 is dispersed in 100mL of dehydrated n-hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor is adjusted to 78°C, and stirring is started with a rotation speed of 1000rpm. Then, hydrogen for adjusting the intrinsic viscosity IV (molecular weight) is introduced so that the pressure in the polymerization reactor is 0.00035MPa, and ethylene is further introduced so that the pressure in the polymerization reactor is 0.7MPa. Then, 40.0mg of prepolymerization catalyst 7 is dispersed in 200mL of dehydrated n-hexane and introduced into the polymerization reactor, and a 1.0 hour intermittent polymerization reaction is carried out. In the polymerization reaction, the pressure in the polymerization reactor is maintained by appropriately adding ethylene into the polymerization reactor. Then, the polymerization reactor is opened, and the contents are filtered under reduced pressure, thereby separating and recovering the solid component in powder form. The obtained solid content was placed in a stainless steel beaker having a mouth diameter of 68 mm, and dried while stirring at 70° C. at a stirring speed of 50 rpm for 2 hours, thereby obtaining an ultrahigh molecular weight polyethylene powder.

[0691] The catalytic activity of the ultra-high molecular weight polyethylene powder (the amount of polyethylene obtained per unit catalyst weight) was 21000 (g-PE / g-catalyst). The scaly matter and the extremely coarse powder were removed using a sieve with a mesh size of 425 μm, and the physical properties of the ultra-high molecular weight polyethylene powder were evaluated. The evaluation results of the ultra-high molecular weight polyethylene powder are shown in Table 1.

[0692] Using the obtained ultrahigh molecular weight polyethylene powder, high strength fibers were produced by the methods described in the above (Method 3-1 for producing a molded article), (Method 3-2 for producing a molded article), (Method 4-1 for producing a molded article), and (Method 4-2 for producing a molded article), and were evaluated by the above-mentioned evaluation methods 5 to 8. The evaluation results of the obtained high strength fibers are shown in Table 1.

[0693] [Example 8]

[0694] The interior of a container-type 1.5L polymerization reactor with a stirring device is adjusted to vacuum, and then 500mL of dehydrated n-hexane is introduced into the polymerization reactor. Next, 5.0mL of cocatalyst 2 is dispersed in 100mL of dehydrated n-hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor is adjusted to 10°C, and stirring is started at a speed of 1000rpm. Then, ethylene is adjusted to 10NL using a flow meter, 750.0mg of solid catalyst component [B] is dispersed in 200mL of dehydrated n-hexane and introduced into the polymerization reactor, and a 1.0 hour intermittent prepolymerization reaction is carried out. After the reaction is completed, the obtained prepolymerization catalyst (hereinafter, also referred to as prepolymerization catalyst 8) is taken out and collected in a nitrogen glove box.

[0695] Next, main polymerization was carried out using the collected prepolymerized catalyst 8 .

[0696] The interior of a container-type 1.5L polymerization reactor with a stirring device was adjusted to a vacuum, and then 500mL of dehydrated n-hexane was introduced into the polymerization reactor. Next, 0.6mL of the cocatalyst 2 was dispersed in 100mL of dehydrated n-hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor was adjusted to 58°C, and stirring was started at a speed of 1000rpm. Next, ethylene gas was introduced so that the pressure in the polymerization reactor was 0.7MPa. Then, 40.0mg of the prepolymerization catalyst 8 was dispersed in 200mL of dehydrated n-hexane and introduced into the polymerization reactor, and a 1.0 hour intermittent polymerization reaction was carried out. In the polymerization reaction, the pressure in the polymerization reactor was maintained by appropriately adding ethylene into the polymerization reactor. Then, the polymerization reactor was opened, and the contents were filtered under reduced pressure, thereby separating and recovering the powdered solid components. The obtained solid component was placed in a stainless steel beaker with a mouth diameter of 68mm, and dried while stirring at 70°C for 2 hours at a stirring speed of 50rpm, thereby obtaining an ultra-high molecular weight polyethylene powder. Next, the ultra-high molecular weight polyethylene powder was immersed in liquid paraffin adjusted to 70° C. under vacuum for 4 hours, then immersed in hexane for 15 hours to extract the liquid paraffin, and then dried at 25° C. for 24 hours.

[0697] The catalytic activity of the ultra-high molecular weight polyethylene powder (the amount of polyethylene obtained per unit catalyst weight) was 19000 (g-PE / g-catalyst). The scaly matter and the extremely coarse powder were removed using a sieve with a mesh size of 425 μm, and the physical properties of the ultra-high molecular weight polyethylene powder were evaluated. The evaluation results of the ultra-high molecular weight polyethylene powder are shown in Table 1.

[0698] Using the obtained ultrahigh molecular weight polyethylene powder, high strength fibers were produced by the methods described in the above (Method 3-1 for producing a molded article), (Method 3-2 for producing a molded article), (Method 4-1 for producing a molded article), and (Method 4-2 for producing a molded article), and were evaluated by the above-mentioned evaluation methods 5 to 8. The evaluation results of the obtained high strength fibers are shown in Table 1.

[0699] [Example 9]

[0700] The interior of a container-type 1.5L polymerization reactor with a stirring device is adjusted to vacuum, and then 500mL of dehydrated n-hexane is introduced into the polymerization reactor. Next, 5.0mL of cocatalyst 3 is dispersed in 100mL of dehydrated n-hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor is adjusted to 8°C, and stirring is started at a speed of 1000rpm. Then, ethylene is adjusted to 5NL using a flow meter, 750.0mg of solid catalyst component [A] is dispersed in 200mL of dehydrated n-hexane and introduced into the polymerization reactor, and a 1.0 hour intermittent prepolymerization reaction is carried out. After the reaction is completed, the obtained prepolymerization catalyst (hereinafter, also referred to as prepolymerization catalyst 9) is taken out and collected in a nitrogen glove box.

[0701] Next, main polymerization was carried out using the collected prepolymerized catalyst 9 .

[0702] The interior of a container-type 1.5L polymerization reactor with a stirring device was adjusted to vacuum, and then 500mL of dehydrated n-hexane was introduced into the polymerization reactor. Next, 0.6mL of the cocatalyst 3 was dispersed in 100mL of dehydrated n-hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor was adjusted to 70°C, and stirring was started at a speed of 1000rpm. Next, ethylene gas was introduced so that the pressure in the polymerization reactor was 0.8MPa. Then, 40.0mg of the prepolymerization catalyst 9 was dispersed in 200mL of dehydrated n-hexane and introduced into the polymerization reactor, and a 1.0 hour intermittent polymerization reaction was carried out. In the polymerization reaction, the pressure in the polymerization reactor was maintained by appropriately adding ethylene into the polymerization reactor. Then, the polymerization reactor was opened, and the contents were filtered under reduced pressure, thereby separating and recovering the powdered solid components. The obtained solid components were placed in a stainless steel beaker with a mouth diameter of 68mm, and dried while stirring for 2 hours at 70°C at a stirring speed of 50rpm, thereby obtaining an ultra-high molecular weight polyethylene powder. Next, the ultra-high molecular weight polyethylene powder was immersed in liquid paraffin adjusted to 80° C. under vacuum for 6 hours, then immersed in hexane for 15 hours to extract the liquid paraffin, and then dried at 25° C. for 24 hours.

[0703] The catalytic activity of the ultra-high molecular weight polyethylene powder (the amount of polyethylene obtained per unit catalyst weight) was 28,000 (g-PE / g-catalyst). The scaly matter and the extremely coarse powder were removed using a sieve with a mesh size of 425 μm, and the physical properties of the ultra-high molecular weight polyethylene powder were evaluated. The evaluation results of the ultra-high molecular weight polyethylene powder are shown in Table 1.

[0704] Using the obtained ultrahigh molecular weight polyethylene powder, high strength fibers were produced by the methods described in the above (Method 3-1 for producing a molded article), (Method 3-2 for producing a molded article), (Method 4-1 for producing a molded article), and (Method 4-2 for producing a molded article), and were evaluated by the above-mentioned evaluation methods 5 to 8. The evaluation results of the obtained high strength fibers are shown in Table 1.

[0705] [Example 10]

[0706] The interior of a container-type 1.5L polymerization reactor with a stirring device is adjusted to vacuum, and then 500mL of dehydrated n-hexane is introduced into the polymerization reactor. Next, 5.0mL of cocatalyst 3 is dispersed in 100mL of dehydrated n-hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor is adjusted to 5°C, and stirring is started at a speed of 1000rpm. Then, ethylene is adjusted to 5NL using a flow meter, 750.0mg of solid catalyst component [A] is dispersed in 200mL of dehydrated n-hexane and introduced into the polymerization reactor, and a 1.0 hour intermittent prepolymerization reaction is carried out. After the reaction is completed, the obtained prepolymerization catalyst (hereinafter, also referred to as prepolymerization catalyst 10) is taken out and collected in a nitrogen glove box.

[0707] Next, main polymerization was carried out using the collected prepolymerized catalyst 10 .

[0708] The interior of a container-type 1.5L polymerization reactor with a stirring device was adjusted to vacuum, and then 500mL of dehydrated n-hexane was introduced into the polymerization reactor. Next, 0.6mL of the cocatalyst 3 was dispersed in 100mL of dehydrated n-hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor was adjusted to 60°C, and stirring was started at a speed of 1000rpm. Next, ethylene gas was introduced so that the pressure in the polymerization reactor was 0.8MPa. Then, 40.0mg of the prepolymerization catalyst 10 was dispersed in 200mL of dehydrated n-hexane and introduced into the polymerization reactor, and a 1.0 hour intermittent polymerization reaction was carried out. In the polymerization reaction, the pressure in the polymerization reactor was maintained by appropriately adding ethylene into the polymerization reactor. Then, the polymerization reactor was opened, and the contents were filtered under reduced pressure, thereby separating and recovering the powdered solid components. The obtained solid component was placed in a stainless steel beaker with a mouth diameter of 68mm, and dried while stirring for 2 hours at 70°C at a stirring speed of 50rpm, thereby obtaining an ultra-high molecular weight polyethylene powder. Next, the ultra-high molecular weight polyethylene powder was immersed in liquid paraffin adjusted to 90° C. under vacuum for 6 hours, then immersed in hexane for 15 hours to extract the liquid paraffin, and then dried at 25° C. for 24 hours.

[0709] The catalytic activity of the ultra-high molecular weight polyethylene powder (the amount of polyethylene obtained per unit catalyst weight) was 26000 (g-PE / g-catalyst). The scaly matter and the extremely coarse powder were removed using a sieve with a mesh size of 425 μm, and the physical properties of the ultra-high molecular weight polyethylene powder were evaluated. The evaluation results of the ultra-high molecular weight polyethylene powder are shown in Table 1.

[0710] Using the obtained ultrahigh molecular weight polyethylene powder, high strength fibers were produced by the methods described in the above (Method 3-1 for producing a molded article), (Method 3-2 for producing a molded article), (Method 4-1 for producing a molded article), and (Method 4-2 for producing a molded article), and were evaluated by the above-mentioned evaluation methods 5 to 8. The evaluation results of the obtained high strength fibers are shown in Table 1.

[0711] [Comparative Example 1]

[0712] The interior of a container-type 1.5L polymerization reactor with a stirring device is adjusted to vacuum, and then 500mL of dehydrated n-hexane is introduced into the polymerization reactor. Next, 5.0mL of cocatalyst 1 is dispersed in 100mL of dehydrated n-hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor is adjusted to 20°C, and stirring is started at a speed of 1000rpm. Then, ethylene is adjusted to 15NL using a flow meter, 750.0mg of solid catalyst component [C] is dispersed in 200mL of dehydrated n-hexane and introduced into the polymerization reactor, and a 1.0 hour intermittent prepolymerization reaction is carried out. After the reaction is completed, the obtained prepolymerization catalyst (hereinafter also referred to as prepolymerization catalyst H-1) is taken out and collected in a nitrogen glove box.

[0713] Next, main polymerization was carried out using the collected prepolymerized catalyst H-1.

[0714] The interior of a container-type 1.5L polymerization reactor with a stirring device is adjusted to vacuum, and then 500mL of dehydrated n-hexane is introduced into the polymerization reactor. Then, 0.6mL of cocatalyst 1 is dispersed in 100mL of dehydrated n-hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor is adjusted to 80°C, and stirring is started at a speed of 1000rpm. Then, hydrogen for adjusting the intrinsic viscosity IV (molecular weight) is introduced so that the pressure in the polymerization reactor is 0.05MPa, and ethylene is further introduced so that the pressure in the polymerization reactor is 0.8MPa. Then, 40.0mg of prepolymerization catalyst H-1 is dispersed in 200mL of dehydrated n-hexane and introduced into the polymerization reactor, and a 1.0 hour intermittent polymerization reaction is carried out. In the polymerization reaction, the pressure in the polymerization reactor is maintained by appropriately adding ethylene into the polymerization reactor. Then, the polymerization reactor is opened, and the contents are filtered under reduced pressure, thereby separating and recovering the solid components in powder form. The obtained solid component was placed in a stainless steel beaker with a mouth diameter of 68 mm, and dried while stirring at 70° C. at a stirring speed of 50 rpm for 2 hours, thereby obtaining an ultra-high molecular weight polyethylene powder. Next, the ultra-high molecular weight polyethylene powder was immersed in liquid paraffin adjusted to 50° C. under vacuum for 3 hours, then immersed in hexane for 10 hours to extract the liquid paraffin, and dried at 25° C. for 24 hours.

[0715] The catalyst activity of the ultra-high molecular weight polyethylene powder (the amount of polyethylene obtained per unit catalyst weight) was 24500 (g-PE / g-catalyst). The scales and extreme coarse powder were removed using a sieve with a mesh size of 425 μm, and 600 ppm of calcium stearate was added, and then the physical properties of the ultra-high molecular weight polyethylene powder were evaluated. The evaluation results of the ultra-high molecular weight polyethylene powder are shown in Table 1.

[0716] The obtained ultrahigh molecular weight polyethylene powder was used to produce a microporous membrane for a secondary battery separator by the methods described in (Method 1-1 for producing a molded body) and (Method 2-1 for producing a molded body), and evaluated by the above-mentioned evaluation methods 1 to 4. The evaluation results of the obtained microporous membrane are shown in Table 1.

[0717] [Comparative Example 2]

[0718] The interior of a container-type 1.5L polymerization reactor with a stirring device is adjusted to vacuum, and then 500mL of dehydrated n-hexane is introduced into the polymerization reactor. Next, 5.0mL of cocatalyst 3 is dispersed in 100mL of dehydrated n-hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor is adjusted to 5°C, and stirring is started at a speed of 1000rpm. Then, ethylene is adjusted to 5NL using a flow meter, 750.0mg of solid catalyst component [A] is dispersed in 200mL of dehydrated n-hexane and introduced into the polymerization reactor, and a 1.0 hour intermittent prepolymerization reaction is carried out. After the reaction is completed, the obtained prepolymerization catalyst (hereinafter, also referred to as prepolymerization catalyst H-2) is taken out and collected in a nitrogen glove box.

[0719] Next, main polymerization was carried out using the collected prepolymerized catalyst H-2.

[0720] The interior of a container-type 1.5L polymerization reactor with a stirring device was adjusted to vacuum, and then 500mL of dehydrated n-hexane was introduced into the polymerization reactor. Next, 0.6mL of cocatalyst 3 was dispersed in 100mL of dehydrated n-hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor was adjusted to 58°C, and stirring was started at a speed of 1000rpm. Next, ethylene gas was introduced so that the pressure in the polymerization reactor was 0.8MPa. Then, 40.0mg of prepolymerization catalyst H-2 was dispersed in 200mL of dehydrated n-hexane and introduced into the polymerization reactor, and a 1.0 hour intermittent polymerization reaction was carried out. In the polymerization reaction, the pressure in the polymerization reactor was maintained by appropriately adding ethylene into the polymerization reactor. Then, the polymerization reactor was opened, and the contents were filtered under reduced pressure, thereby separating and recovering the powdered solid components. The obtained solid component was placed in a stainless steel beaker with a mouth diameter of 68mm, and dried while stirring at 70°C for 2 hours at a stirring speed of 50rpm, thereby obtaining an ultra-high molecular weight polyethylene powder. Next, the ultra-high molecular weight polyethylene powder was immersed in liquid paraffin adjusted to 90° C. under vacuum for 6 hours, then immersed in hexane for 15 hours to extract the liquid paraffin, and then dried at 25° C. for 24 hours.

[0721] The catalytic activity of the ultra-high molecular weight polyethylene powder (the amount of polyethylene obtained per unit catalyst weight) was 22500 (g-PE / g-catalyst). The scaly matter and the extremely coarse powder were removed using a sieve with a mesh size of 425 μm, and the physical properties of the ultra-high molecular weight polyethylene powder were evaluated. The evaluation results of the ultra-high molecular weight polyethylene powder are shown in Table 1.

[0722] Using the obtained ultrahigh molecular weight polyethylene powder, high strength fibers were produced by the methods described in (Production Method 3-1 of Molded Article) and (Production Method 4-1 of Molded Article) and evaluated by the above-mentioned Evaluation Methods 5 to 8. The evaluation results of the obtained high strength fibers are shown in Table 1.

[0723] [Comparative Example 3]

[0724] The interior of a container-type 1.5L polymerization reactor with a stirring device is adjusted to vacuum, and then 500mL of dehydrated n-hexane is introduced into the polymerization reactor. Next, 0.6mL of cocatalyst 1 is dispersed in 100mL of dehydrated n-hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor is adjusted to 80°C, and stirring is started at a speed of 1000rpm. Next, hydrogen for adjusting the intrinsic viscosity IV (molecular weight) is introduced so that the pressure in the polymerization reactor is 0.016MPa, and ethylene is further introduced so that the pressure in the polymerization reactor is 0.8MPa. Then, 5.0mg of solid catalyst component [C] is dispersed in 200mL of dehydrated n-hexane and introduced into the polymerization reactor, and a 1.0 hour intermittent polymerization reaction is carried out. In the polymerization reaction, the pressure in the polymerization reactor is maintained by appropriately adding ethylene into the polymerization reactor. Then, the polymerization reactor is opened, and the contents are filtered under reduced pressure, thereby separating and recovering the powdery solid component. The obtained solid component was placed in a stainless steel beaker with a mouth diameter of 68 mm, and dried while stirring at 70°C at a stirring speed of 50 rpm for 2 hours to obtain an ultra-high molecular weight polyethylene powder. The catalyst activity (the amount of polyethylene obtained per unit catalyst weight) of the ultra-high molecular weight polyethylene powder was 27000 (g-PE / g-catalyst). The scales and extreme coarse powder were removed using a sieve with a mesh size of 425 μm, 600 ppm of calcium stearate was added, and then the physical properties of the ultra-high molecular weight polyethylene powder were evaluated. The evaluation results of the ultra-high molecular weight polyethylene powder are shown in Table 1.

[0725] The obtained ultrahigh molecular weight polyethylene powder was used to produce a microporous membrane for a secondary battery separator by the methods described in (Method 1-1 for producing a molded body) and (Method 2-1 for producing a molded body), and evaluated by the above-mentioned evaluation methods 1 to 4. The evaluation results of the obtained microporous membrane are shown in Table 1.

[0726] [Comparative Example 4]

[0727] The interior of a container-type 1.5L polymerization reactor with a stirring device was adjusted to vacuum, and then 500mL of dehydrated n-hexane was introduced into the polymerization reactor. Next, 0.6mL of cocatalyst 2 was dispersed in 100mL of dehydrated n-hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor was adjusted to 78°C, and stirring was started at a speed of 1000rpm. Next, hydrogen for adjusting the intrinsic viscosity IV (molecular weight) was introduced so that the pressure in the polymerization reactor was 0.00035MPa, and ethylene was further introduced so that the pressure in the polymerization reactor was 0.7MPa. Then, 5.0mg of solid catalyst component [B] was dispersed in 200mL of dehydrated n-hexane and introduced into the polymerization reactor, and a 1.0 hour intermittent polymerization reaction was carried out. During the polymerization reaction, the pressure in the polymerization reactor was maintained by appropriately adding ethylene into the polymerization reactor. Then, the polymerization reactor was opened, and the contents were filtered under reduced pressure, thereby separating and recovering the powdered solid component. The obtained solid component was placed in a stainless steel beaker with a mouth diameter of 68 mm, and dried while stirring at 70°C at a stirring speed of 50 rpm for 2 hours to obtain an ultra-high molecular weight polyethylene powder. The catalyst activity (the amount of polyethylene obtained per unit catalyst weight) of the ultra-high molecular weight polyethylene powder was 23500 (g-PE / g-catalyst). The scales and extreme coarse powder were removed using a sieve with a mesh size of 425 μm, and the physical properties of the ultra-high molecular weight polyethylene powder were evaluated. The evaluation results of the ultra-high molecular weight polyethylene powder are shown in Table 1.

[0728] Using the obtained ultrahigh molecular weight polyethylene powder, high strength fibers were produced by the methods described in (Production Method 3-1 of Molded Article) and (Production Method 4-1 of Molded Article) and evaluated by the above-mentioned Evaluation Methods 5 to 8. The evaluation results of the obtained high strength fibers are shown in Table 1.

[0729] [Table 1-1]

[0730]

[0731] [Table 1-2]

[0732]

[0733] [Table 1-3]

[0734]

[0735] Industrial Applicability

[0736] The ultra-high molecular weight polyethylene powder of the present invention can provide high-quality molded products such as secondary battery separators and fibers with excellent molding processability by shortening the dissolution time in liquid paraffin (the time from the start of dissolution to the end of dissolution), and has industrial applicability.

Claims

1. An ultra-high molecular weight polyethylene powder, wherein: The ultra-high molecular weight polyethylene powder has an intrinsic viscosity IV of 1.0 dL / g or more and 38.0 dL / g or less, The average particle size D50 of the ultra-high molecular weight polyethylene powder is 50 μm or more and 400 μm or less. The dissolution time of the powder having a particle size of D50 is 5 seconds or more and 80 seconds or less.

2. The ultra-high molecular weight polyethylene powder according to claim 1, wherein The intrinsic viscosity IV of the ultra-high molecular weight polyethylene powder is 13.5 dL / g or more and 38.0 dL / g or less.

3. The ultra-high molecular weight polyethylene powder according to claim 1 or 2, wherein: The dissolution time of the ultra-high molecular weight polyethylene powder is 5 seconds or more and 40 seconds or less.

4. The ultra-high molecular weight polyethylene powder according to claim 1 or 2, wherein The ratio of the communicating pores of the powder having a particle size of D50 is 3% or more and 70% or less.

5. The ultra-high molecular weight polyethylene powder according to claim 1 or 2, wherein: The surface thickness of the powder having a particle size D50 is 3 μm or more and 60 μm or less.

6. The ultra-high molecular weight polyethylene powder according to claim 1 or 2, wherein: The diameter of the communicating pores of the powder having a particle size D50 is 3 μm or more and 30 μm or less.

7. The ultra-high molecular weight polyethylene powder according to claim 1 or 2, wherein: The titanium content of the ultra-high molecular weight polyethylene powder is less than 5 ppm.

8. The ultra-high molecular weight polyethylene powder according to claim 1 or 2, wherein: The aluminum content of the ultra-high molecular weight polyethylene powder is less than 5 ppm.

9. A molded body, wherein The molded body is a molded body of the ultra-high molecular weight polyethylene powder according to claim 1 or 2.

10. The molded article according to claim 9, wherein The molded body is a separator for a secondary battery.

11. The molded article according to claim 9, wherein The shaped body is a fiber.

12. A method for producing a high-strength fiber, wherein: The method for producing the high-strength fiber comprises the following steps: a slurry step, wherein an ultra-high molecular weight polyethylene powder is mixed with a first liquid paraffin, and the mixture is stirred at a temperature below the melting point of the ultra-high molecular weight polyethylene powder to obtain a slurry; A gelling step, wherein the slurry is mixed with a second liquid paraffin having a temperature of 150° C. to 300° C., thereby obtaining a raw silk gel having a temperature of 140° C. to 200° C.; an extrusion process, wherein the precursor is extruded through the gel to obtain the precursor; an extraction step, wherein the first liquid paraffin and the second liquid paraffin are extracted from the raw yarn to obtain the raw yarn for drawing; and a raw yarn stretching step, wherein the raw yarn for stretching is heated and stretched, The ultra-high molecular weight polyethylene powder has an intrinsic viscosity IV of 13.5 dL / g or more and 38.0 dL / g or less, The average particle size D50 of the ultra-high molecular weight polyethylene powder is 50 μm or more and 400 μm or less. The dissolution time of the powder having a particle size of D50 of the ultra-high molecular weight polyethylene powder is 5 seconds to 80 seconds.

13. The method for producing a high-strength fiber according to claim 12, wherein: Prior to the extrusion step, a kneading step of kneading the raw yarn gel is provided.

14. A method for producing a microporous membrane, wherein: The method for manufacturing the microporous membrane comprises the following steps: a slurry step, wherein an ultra-high molecular weight polyethylene powder is mixed with a first liquid paraffin, and the mixture is stirred at a temperature below the melting point of the ultra-high molecular weight polyethylene powder to obtain a slurry; a gelling step, wherein the slurry is mixed with a second liquid paraffin having a temperature of 150° C. to 300° C., thereby obtaining a gel for pressing having a temperature of 140° C. to 200° C.; A pressing step, wherein the pressing gel is hot-pressed to obtain a gel sheet; a film stretching step, wherein the gel sheet is stretched to obtain a stretched film; and an extraction step, wherein the first liquid paraffin and the second liquid paraffin are extracted from the stretched film, The ultra-high molecular weight polyethylene powder has an intrinsic viscosity IV of 1.0 dL / g or more and 13.0 dL / g or less, The average particle size D50 of the ultra-high molecular weight polyethylene powder is 50 μm or more and 400 μm or less. The dissolution time of the powder having a particle size of D50 of the ultra-high molecular weight polyethylene powder is 5 seconds to 80 seconds.

15. The method for producing a microporous membrane according to claim 14, wherein: Prior to the pressing step, a kneading step of kneading the gel for pressing is performed.

Citation Information

Patent Citations

  • PROCESS FOR THE PRODUCTION OF POLYOLEFINS AND THEIR COPOLYMERISATS

    DE3127133A1

  • JP1973068853A

  • Polyethylene powder and fiber

    JP2017088773A

  • Polyethylene-based powder and manufacturing method thereof

    JP2017145306A

  • Polyethylen powder

    JP2019019265A